Restoration of a Mid-Atlantic Coastal Bay Scallop Population (Argopecten irradians) - Richard A. Snyder; Rebecca T. Smith; Darian M. Kelley; Sean Fate; Robert J. Orth; Bowdoin Lusk; Christopher J. Patrick; Stacy A. Krueger-Hadfield; Jan McDowell; Fredrick C. Holbert; John C. Lewis; John P. Richardson; et al. (Estuaries and Coasts, 2026)
We have attempted to re-establish bay scallops to the Virginia, U.S.A. coastal bays and document the dynamics of the restoration effort. Bay scallops ( Argopecten irradians ) once flourished in the eelgrass ( Zostera marina ) of the Virginia coastal bays. Eelgrass wasting disease led to declines, and both eelgrass and scallops were completely lost after a 1933 hurricane. The Virginia Institute of Marine Science (VIMS) led a successful eelgrass restoration effort beginning in 1997, with eelgrass beds expanding at 204 ha per year since 2012 and covering over 4,800 ha in 2025. From 2009 to 2025, bay scallops were brought in from North Carolina, New York, and Florida to the VIMS Eastern Shore Laboratory (VIMS ESL) in Wachapreague, VA and used to raise bay scallops for restoration. Progeny were released to the eelgrass beds and held in spawning cages. Annual census data documented low and fluctuating scallop densities from 2012 to 2018. From 2019 to 2025, we have observed continued exponential growth with a current (2024–2025) specific growth rate of µ = 0.468 year − 1 and a population doubling time of 1.48 years. The carrying capacity of the system for the new Virginia bay scallop population remains unknown with the population still in the exponential growth phase. In 2025 the annual census documented an average density of 0.114 scallops m − 2 and maximum recorded local density within 50 m − 2 sampling stations of 0.52 scallops m − 2 . Aggregation within the population was anticipated as necessary for reproductive success and was observed in population data with increasing density.

Processes affecting pollution fluxes during the coastal erosion of legacy colliery wastes - Ian T. Burke; Sebastian J. Pitman; James Hodson; Lin Niu; Fatmah Mohammed; Jenni Ilari Skakunova; Alex L. Riley; Catherine J. Gandy; Elliot Whitehead; Karen A. Hudson-Edwards; Elin Jennings; Helen Jay; et al. (Applied Geochemistry, 2026)

The role of local winds and a semi-persistent coastal front on the diurnal heat budget in an upwelling bay - April P. Thibodeau; Ryan K. Walter; Piero L.F. Mazzini; Thomas P. Connolly; Christopher A. Edwards; Ian Robbins (Continental Shelf Research, 2026)

The emerging and escalating consequences of rural depopulation in the Himalaya - Karuna Budhathoki; Bhola Bhattarai; Bed Mani Dahal; Shalini Dhyani; Ambika P. Gautam; Binita Guragain; Dibya Devi Gurung; Muhammad Ismail; Om Katel; Sarala Khaling; Kristina Marquardt; Ulrike Müller-Böker; et al. (Global Environmental Change, 2026)

Geochemical, mineralogical and particle-size controls on origin, transport and storage of sediment-associated metal(loid)s in an acid mine drainage-affected river - Elin Jennings; Patrizia Onnis; Rich Crane; William M. Mayes; Adam P. Jarvis; Karen A. Hudson-Edwards (Applied Geochemistry, 2026)

From the deep sea to the shore: Source fingerprinting and weathering of spilled oil following the 2023 MT Princess Empress oil spill (Oriental Mindoro, Philippines) - Jay Rumen U. Maglupay; Edward S. Yeo; Gerald L. Cordero; Rachel Zioness O. Diputado; Kim Christopher C. Aganda; Rodolfo A. Romarate; Julien Guyomarch; Chin-Chang Hung; Hernando P. Bacosa (Marine Pollution Bulletin, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Reflectance spectroscopy (200-4200 nm) of the red-sloped C2 carbonaceous chondrites MET 00432, Tagish Lake, Tarda, and WIS 91600 (“CT” grouplet) - Edward A. Cloutis; Devin L. Schrader; Daniel M. Applin; Tomoki Nakamura; Timothy D. Glotch; Takahiro Hiroi; Moe Matsuoka; Michael E. Zolensky; Joshua P. Emery; Kristi M. Peters (Icarus, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Spatial variability in the carbon stocks of different seagrass meadows of southern Palk Bay, India: Influence of species composition, sediment characteristics and restoration efforts - N. Gladwin Gnana Asir; G. Mathews; K. Diraviya Raj; P. Dinesh Kumar; A. Arasamuthu; R.L. Laju; Bakan Jagdish Sudhakar; J.K. Patterson Edward (Marine Pollution Bulletin, 2026)

Particulate nitrate over the Northwest Atlantic: Insights gained by comparing airborne AMS and PILS measurements - Soodabeh Namdari; Taiwo Ajayi; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Eva-Lou Edwards; Johnathan W. Hair; Christopher A. Hostetler; Simon Kirschler; John B. Nowak; Michael Shook; et al. (Atmospheric Environment, 2026)

Informing spatial conservation prioritization with species’ traits - Liam A. Trethowan; Laura Jennings; Haerul Arifin; Renata Borosova; Gemma L. C. Bramley; Marie Briggs; Osanna Chu; Ruth P. Clark; Sally Dawson; Kiran L. Dhanjal‐Adams; Yance de Freitas; James Hartup; et al. (Conservation Biology, 2026)
New Guinea, the most botanically diverse island on the planet, is the location for one of the boldest conservation initiatives. The Manokwari Declaration aims to achieve 70% conservation designation for the Bird's Head Peninsula. This is 40% higher than the 2022 Global Biodiversity Framework target. However, there is a lack of species occurrence data to support evidence of where biodiversity can be best protected. To address this, we integrated plant trait data from taxonomic descriptions in species occurrence models that can inform conservation planning. Inclusion of traits improved the performance of co‐occurrence models of ∼800 plant species across the 100,000‐km 2 landscape. Traits generally improved model performance, but not all traits contributed equally (e.g., leaf size and red flower color most improved accuracy of occurrence prediction). Likewise, trait‐parameterized models tended to be most useful with rare species occurrence prediction, but this was inconsistent among traits. Under 70% protection, three‐quarters of the areas selected conserved trait diversity. Critically, trait diversity also increased the chances that areas at high risk of deforestation were selected as conservation priorities. Overall, we found that plant species’ traits, often key parameters of ecosystem function and resilience, improved spatial conservation planning.

First record of Cassiopea xamachana ephyrae from the wild in India, with insights into its life history and development - L. Ranjith; Raju Saravanan; K.S. Sobhana; I. Jagadis; S. Ramkumar; C. Kalidas; D. Linga Prabu; M. Kavitha; P. Nevathitha; A. Mathan Babu; D. Sarathapriya; L. Loveson Edward; et al. (Regional Studies in Marine Science, 2026)

An updated Irwin sensor for measurement of surface shear velocity - Nancy P. Ziegler; Nicholas P. Webb; Brandon L. Edwards; George Nikolich; John A. Gillies; Sahil G. Patel; Brandi Wheeler; Pei Zhang; Justin W. Van Zee; Sandra L. LeGrand; Andrew C. Trautz (Aeolian Research, 2026)

A Conceptual Framework and Methods for Studying the Connectivity of Fishes - Jordanna N. Bergman; Jessica A. Robichaud; Jasper McCutcheon; Michael T. Booth; Brendan Campbell; Grace A. Casselberry; Cienna R. Cooper; Bronwyn M. Gillanders; Lucas P. Griffin; Edward Hale; Luc LaRochelle; Karen J. Murchie; et al. (Fish and Fisheries, 2026)
Connectivity is a multifaceted concept that has important implications for the management and conservation of marine and freshwater fishes. We developed a conceptual framework that encompasses multiple, interrelated categories of connectedness, including landscape (e.g., structural, functional) connectivity and ecological (e.g., trophic, genetic, demographic) connectivity, that together shape the flow of organisms, energy and information across ecosystems. We also synthesised six key methods that can be used to study connectivity of fishes: (1) telemetry, including satellite, acoustic, radio and passive integrated transponders (PIT), (2) mark‐recapture, (3) environmental tracers, including stable isotopes and otolith‐microchemistry, (4) genetics, (5) community structure analysis and (6) emerging technologies and tools (e.g., remote sensing and artificial intelligence). For each method, we describe the categories of connectivity it can assess and provide real‐world examples where they have been effectively used. We also identify limitations of each method. This article highlights the diverse and evolving toolbox of methods used to assess fish connectivity, underscoring the need for continued collaboration, innovation and integration of new approaches to refine our understanding and address remaining challenges in this critical area of aquatic ecology and fisheries management.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Uncovering UK coastal legacy wastes and their potential contaminant release risks through mineralogy and geochemistry - Patrizia Onnis; Elin Jennings; Violeta Ramos; Alex L. Riley; Catherine J. Gandy; Rich A. Crane; Ian T. Burke; Gavyn K. Rollinson; Patrick Byrne; Bryan M. Spears; Justyna P. Olszewska; Will M. Mayes; et al. (Journal of Hazardous Materials, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Seascape diversity and configuration shape habitat selection across multiple coastal ecosystems - Jesse D. Mosman; Hayden P. Borland; Ashley J. Rummell; Christopher J. Henderson; Sam Allan; Alec Bannam; Stacy L. Bierwagen; Michael J. Bradley; Alex B. Carter; Daniela M. Ceccarelli; Robert Coles; Michael J. Emslie; et al. (Biological Conservation, 2026)

Subsaturated aerosol hygroscopicity over the northwest Atlantic: Impacts of seasonal factors, offshore location, and clouds - Genevieve Rose Lorenzo; Luke D. Ziemba; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Richard A. Ferrare; Simon Kirschler; John B. Nowak; Michael A. Shook; Kenneth L. Thornhill; Christiane Voigt; et al. (Atmospheric Environment, 2026)

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

High yield stability and susceptibility to stripe rust associate with large yield gaps in rainfed winter wheat - Nicolas Giordano; Victor O. Sadras; Mary J. Guttieri; Trevor J. Hefley; Jorge A. Romero Soler; Clark Neely; Jeffrey T. Edwards; Amanda de Oliveira Silva; Allan K. Fritz; Romulo P. Lollato (Field Crops Research, 2025)

Speciation and leaching behaviour of inorganic contaminants in actively eroding historical coastal municipal solid waste landfills - Ian T. Burke; Patrizia Onnis; Alex L. Riley; Catherine J. Gandy; Violeta Ramos; Gavyn K. Rollinson; Patrick Byrne; Richard A. Crane; Karen A. Hudson-Edwards; Elin Jennings; William M. Mayes; J. Frederick W. Mosselmans; et al. (Marine Pollution Bulletin, 2025)

17Oexcess in Devils Hole calcite: an indicator of equilibrium fractionation and paleo moisture sources - Hagit P. Affek; Eugeni Barkan; Yael Tal; Simon D. Steidle; Kathleen A. Wendt; Christoph Spötl; R. Lawrence Edwards; Ekaterina Fishman; Yuri Dublyansky (Earth and Planetary Science Letters, 2025)

P18-65 Advancing the Grouping and Harmonization of Similar Key Events in the AOP Wiki: Ontology-Based Key Event Component Combinations as Catalysts for Integration - J. Filipovska; K. Audouze; J. Blum; L.-A. Clerbaux; E. Coerek; E. Demuynck; S. Edwards; E. Fritsche; L. Gerner; K. Groh; G. Hench; N. Jeliazkova; et al. (Toxicology Letters, 2025)

Association of oil spill cleanup-related hydrocarbon exposure with hypertension and blood pressure in the Gulf Long-term Follow-up Study - Opal P. Patel; Jessie K. Edwards; Anna M. Kucharska-Newton; Eric A. Whitsel; W. Braxton Jackson; Kaitlyn G. Lawrence; Patricia A. Stewart; Mark R. Stenzel; Lawrence S. Engel; Dale P. Sandler (Science of The Total Environment, 2025)

Decadal change in deep-ocean dissolved oxygen in the North Atlantic Ocean and North Pacific Ocean - Henry A. Ruhl; Christine L. Huffard; Monique Messié; Thomas P. Connolly; Thomas Soltwedel; Frank Wenzhöfer; Rodney J. Johnson; Nicholas R. Bates; Susan Hartman; Anita Flohr; Edward W. Mawji; David M. Karl; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Spatially resolved X-ray imaging and molecular characterisation of sulfur and iron in organic- and sulfur-rich hydrocarbon source mudstones - Yusuf Abubakar; Roy A. Wogelius; Victoria S. Coker; Kevin G. Taylor; Nicholas P. Edwards; Bart E. van Dongen (Chemical Geology, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Reimagining species on the move across space and time - Alexa L. Fredston; Morgan W. Tingley; Montague H.C. Neate-Clegg; Luke J. Evans; Laura H. Antão; Natalie C. Ban; I-Ching Chen; Yi-Wen Chen; Lise Comte; David P. Edwards; Birgitta Evengard; Belen Fadrique; et al. (Trends in Ecology & Evolution, 2025)

Interference of PFAS sorption on zeolites from natural water characteristics - Nathaniel P. Sheehan; Charles A. Ponge; Abe Pankratz; Justin M. Hutchison; Brian B. Laird; Nuong P. Nguyen; Mark B. Shiflett; Deepak Timalsina; Michael Zhuo Wang; Edward F. Peltier (Chemosphere, 2025)

A dynamic meshing scheme for integrated hydrologic modeling to represent evolving landscapes - Hyoun-Tae Hwang; Young-Jin Park; Steven J. Berg; Jon P. Jones; Killian L. Miller; Edward A. Sudicky (Science of The Total Environment, 2025)

Interfacial electromigration for accelerated reactions - Madison E. Edwards; Annesha Sengupta; Dallas P. Freitas; Erin A. Hirtzel; Xi Chen; Joohan J. Kim; Xin Yan (Analytica Chimica Acta, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Tropical Land‐Use Change Disrupts Zeta‐Diversity Across Taxa - Edicson Parra‐Sanchez; Guillaume Latombe; Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Diego Martinez‐Revelo; Oscar A. Perez‐Escobar; Robert W. Davies; Christopher G. Bousfield; Gianluca R. Cerullo; Jose Manuel Ochoa‐Quintero; Torbjørn Haugaasen; et al. (Global Change Biology, 2025)
Land‐use change causes community turnover via local extinction and colonisation of species, driving biotic homogenization or heterogenization at larger spatial scales. Quantification of these processes has focused on beta‐diversity metrics, which upweight rarity and overlook the role of widespread species. A key knowledge gap is understanding the impact of land‐use change on both rare and widespread species—zeta‐diversity—allowing the detection of statistical patterns and drivers based on community turnover across space. We sampled bird, dung beetle, and orchid communities in 341 plots across natural (Andean forests and paramo) and transformed habitats (pasturelands) spanning ~270 km north‐to‐south in the Colombian Andes. We detected major losses in species richness following land‐use conversion, which disrupts zeta‐diversity across elevation in two ways. First, biodiversity patterns are rewired such that bird and dung beetle communities become structured by dispersal ability, overriding the effects of natural biogeographical drivers (i.e., elevation) and landscape conditions (i.e., canopy cover). Second, land‐use change causes biotic homogenization across bird communities, with pasture retaining twice as many widespread species than natural habitats, and a four‐fold reduction in widespread dung beetle species pointing to subtractive heterogenization. Orchid communities show high community turnover in both natural and transformed habitat. Our results show that the effect of local deforestation has a doubly devastating impact simplifying communities and reducing widespread species. Transforming natural habitats into anthropogenic landscapes may substantially raise extinction risk for communities composed of both widespread and rare species, especially in orchids as the most sensitive taxon.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Photodynamic priming with red light triggers adaptive immune responses in a pancreatic cancer mouse model - Pushpamali De Silva; Mohammad A. Saad; Joseph W.R. Swain; Zhiming Mai; Madeline D. Kidd; Joanna J. Choe; Assiris P. Camargo; Sanjay Anand; Vinay Chandrasekhara; Brian W. Pogue; Kenneth K. Wang; Bryan Q. Spring; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

John Raven, FRS, FRSE: a truly great innovator in plant physiology, photosynthesis and much more - A. W. D. Larkum; P. G. Falkowski; Dianne Edwards; C. B. Osmond; H. Lambers; P. Sanchez-Baracaldo; R. J. Ritchie; J. W. Runcie; P. J. Ralph; M. Westoby; S. Maberly; H. Griffiths; et al. (Photosynthesis Research, 2025)
This is a tribute to a truly inspirational plant biologist, Prof. John A. Raven, FRS, FRSE (25th June 1941– 23rd May 2024), who died at the age of 82. He was a leader in the field of evolution and physiology of algae and land plants. His research touched on many areas including photosynthesis, ion transport, carbon utilisation, mineral use, such as silicon, iron and molybdenum, the evolution of phytoplankton, the evolution of root systems, the impact of global change, especially on the acidification of the oceans, carbon gain and water use in early land plants, and ways of detecting extraterrestrial photosynthesis. Beginning his research career in the Botany School, University of Cambridge, John studied ion uptake in a giant algal cell. This was at the time of great strides brought about by Peter Mitchell (1920–1992) in elucidating the role of energy generation in mitochondria and chloroplasts and the coupling of ion transport systems to energy generation. With Enid MacRobbie and Andrew Smith, John pioneered early work on the involvement of ion transport in the growth and metabolism of plant cells.On leaving Cambridge John took up a lectureship at the University of Dundee in 1971, where he was still attached upon his death. His primary focus over the years, with one of us (Paul Falkowski), was on phytoplankton, the photosynthetic microalgae of the oceans. Still, his publication list of 5 books and over 600 scientific papers spans a very broad range. The many highly cited papers (see Table 1) attest to an outstanding innovator, who influenced a multitude of students and coworkers and a very wide readership worldwide. At the personal level, John Raven was a wonderful human being; he had an extraordinary memory, dredging up facts and little-known scientific papers, like a scientific magician, but at the same time making humorous jokes and involving his colleagues in fun and sympathetic appreciation. Table 1 Ten best cited articles (from google scholar) Citations Date Aquatic Photosynthesis, 3rd EditionP.G. Falkowski & J.A. RavenPrinceton University Press, 2013 3854 2013 The evolution of modern eukaryotic phytoplanktonP.G. Falkowski, M.E. Katz, A.H. Knoll, A. Quigg, J.A. Raven, et alScience 305 , 354–360 1790 2004 C O 2 concentrating mechanisms in algae:mechanisms, environmental modulation, and evolutionM. Giordano, J. Beardall & J.A. RavenAnnu. Rev. Plant Biol. 56 (1), 99–131 1648 2005 Algae as nutritional food sources: revisiting our understandingM.L. Wells, P. Potin, J.S. Craigie, J.A. Raven, S.S. Merchant, et alJournal of applied phycology 29 , 949–982 1527 2017 Plant Nutrient acquisition strategies change with soil ageH. Lambers, J.A. Raven, G.R. Shaver & S.E. SmithTrends in ecology & evolution 23 , 95–103 1488 2008 Ocean acidification due to increasing atmospheric carbon dioxideJ. Raven, K. Caldeira, H. Elderfield, O. Hoegh-Guldberg, P. Liss, et alThe Royal Society, Policy Document, June 2005 1470 2005 Phytoplankton in a changing world: cell size and elemental stoichiometryZ.V. Finkel, J. Beardall, K.J. Flynn, A. Quigg, T.A.V. Rees & J.A. RavenJournal of plankton research 32 , 119–137 1198 2010 Opportunities for improving phosphorus efficiency in crop plantsE.J. Veneklaas, H. Lambers, J. Bragg, P.M. Finnegan, C.E. Lovelock, et alNew phytologist 195 , 306–320 951 2012 Adaptation of unicellular algae to irradiance: an analysis of strategiesK. Richardson, J. Beardall & J.A. RavenNew Phytologist 93 , 157–191 914 1983 N itrogen assimilation and transport in vascular land plants in relation to Intracellular pH regulationJ.A. Raven & F.A. SmithNew Phytologist 76 , 415–431 893 1976 Temperature and algal growth J.A. Raven & R.J. GeiderNew phytologist 110 , 441–461 867 1988 The role of trace metals in photosynthetic electron transport in O 2 -evolving organismsJ.A. Raven, M.C.W. Evans & R.E. KorbPhotosynthesis Research 60 , 111–150 840 1999

Correction: Sequence Divergence in Venom Genes Within and Between Montane Pitviper (Viperidae: Crotalinae: Cerrophidion) Species is Driven by Mutation–Drift Equilibrium - Ramses Alejandro Rosales‑Garcia; Rhett M. Rautsaw; Erich P. Hofmann; Christoph I. Grünwald; Hector Franz‑Chavez; Ivan T. Ahumada‑Carrillo; Ricardo Ramirez‑Chaparro; Miguel Angel de la Torre‑Loranca; Jason L. Strickland; Andrew J. Mason; Matthew L. Holding; Miguel Borja; et al. (Journal of Molecular Evolution, 2025)

Machine Learning Predicts Non-Preferred and Preferred Vertebrate Hosts of Tsetse Flies (Glossina spp.) Based on Skin Volatile Emission Profiles - Olabimpe Y. Orubuloye; David P. Tchouassi; Abdullahi A. Yusuf; Christian W. W. Pirk; Daniel K. Masiga; Edward Kariuki; Baldwyn Torto (Journal of Chemical Ecology, 2025)
Tsetse fly vectors of African trypanosomosis preferentially feed on certain vertebrates largely determined by olfactory cues they emit. Previously, we established that three skin-derived ketones including 6-methyl-5-hepten-2-one, acetophenone and geranyl acetone accounted for avoidance of zebra by tsetse flies. Here, we tested the hypothesis that these three ketones serve as biomarkers for tsetse flies to distinguish between non-preferred- and preferred-vertebrate hosts. We used coupled gas chromatography/mass spectrometry to analyze and compare the skin volatile emissions of two non-preferred- (waterbuck and zebra) and four preferred- (buffalo, donkey, horse, warthog) vertebrate hosts in two wildlife parks in Kenya. We detected a total of 96 volatile organic compounds (VOCs) in the skin emissions composed mainly of aldehydes, ketones, alcohols, phenols and alkanes, which varied with the vertebrate host. Using random forest analysis, we found a weak correlation between the three skin-odor repellent ketones and non-preferred and preferred vertebrate hosts. However, we found that the three repellent ketones plus skin background odors may be more sensitive chemical signals for tsetse flies to discriminate vertebrate hosts. These results contribute to understanding tsetse fly vertebrate host preferences in their natural habitat across geographic scales.

Investigating stocking density, culture duration, and the combination ratio of artificial feed and fresh feed for mangrove crab Scylla serrata megalopae reared in pond-based net cages - Pedrita A. Caballero; Veronica R. Alava; Kyle Dymer L. Regatalio; Rheniel Dayrit; Joseph P. Faisan; Roger Edward P. Mamauag; Mercedes M. Pates; Gaudioso S. Pates (Aquaculture International, 2025)

Eddy dipole differentially influences particle‐associated and water column protistan community composition - Jennifer L. Beatty; Brittany P. Stewart; Lisa Y. Mesrop; Edward F. DeLong; David M. Karl; David A. Caron (Limnology and Oceanography, 2025)
Ocean eddies are mesoscale features that can extend > 100 km and maintain cohesiveness for months, impacting planktonic community structure and water column biogeochemical cycles. Standing stocks of protists in the water column and on sinking particles were investigated using microscopy, in situ imagery, and metabarcoding across an anticyclonic to cyclonic eddy dipole in the North Pacific Subtropical Gyre during July 2017. The water column was sampled from the surface to 500 m and particle interceptor traps were deployed at 150 m. Protistan assemblage composition varied substantially between sample type and analytical approach across the eddy dipole. Alveolates represented 63% of sequences from water samples. In contrast to water samples, rhizarian protists represented 79% of trap sequences obtained by metabarcoding of sediment trap material. Microscopy of trap material supported the important contribution of Rhizaria to sinking particles and revealed increased relative abundances of ciliates in the anticyclonic eddy and diatoms in the cyclonic eddy. In situ imagery confirmed the presence of relatively large Rhizaria that were not adequately assessed from water samples but contributed significantly to particle flux. Together, these data demonstrate differing perspectives of planktonic protistan community composition and contributions to sinking particles gained from the application of different sampling and analytic approaches. Our observations and analyses indicate a specific subset of the protistan community contributed disproportionately to organic matter downward export.

Non-serous ovarian cancer in PTEN Hamartoma Tumor Syndrome: additional evidence for increased risk - Ane J. Schei-Andersen; Vera M. Witjes; Janet R. Vos; Arjen R. Mensenkamp; Anne van Altena; Jolanda Schieving; Michiel Simons; Janneke H. M. Schuurs-Hoeijmakers; Muriel A. Adank; Liselotte P. van Hest; Yvette van Ierland; Mirjam de Jong; et al. (Familial Cancer, 2025)
Increased hereditary cancer risk is one of the hallmarks of PTEN Hamartoma Tumor Syndrome (PHTS) which is caused by a pathogenic germline variant in PTEN . Case reports and some cohort studies have described ovarian cancer (OC) in PHTS patients. Previously, we observed an enrichment of non-serous OC in PHTS compared to sporadic cases (3% vs 1%). However, ovarian cancer is currently not considered a PHTS-related cancer. The aim of this study was to describe five PHTS patients with a pathogenic germline variant in PTEN with non-serous OC. Three of the non-serous OCs were mucinous carcinomas (49, 51 and 52 years) and two were malignant germ cell tumors (8 and 15 years) and all were diagnosed before genetic testing and PHTS diagnosis. In addition to OC, the described patients developed other PHTS-related benign and malignant lesions. We provide further evidence that non-serous ovarian cancer, especially mucinous, endometrioid and malignant germ cell tumors should be further investigated as potential PHTS-related cancers.

Spatial variability of metal(loid) leaching from coastal colliery wastes under freshwater and saline water conditions - Catherine J. Gandy; Ian T. Burke; Patrick Byrne; Nick Cooper; Richard A. Crane; Karen A. Hudson-Edwards; William M. Mayes; Patrizia Onnis; Alex L. Riley; Adam P. Jarvis (Journal of Environmental Management, 2025)

Effects of the invasive aquatic snail Potamopyrgus antipodarum (Gray, 1853) on ecosystem properties and services - Álvaro Alonso; Gonzalo A. Collado; Claudia Gérard; Edward P. Levri; Rodrigo B. Salvador; Pilar Castro-Díez (Hydrobiologia, 2025)
Ecosystems provide benefits to humans, including provisioning, regulating, and cultural services. However, invasive species can threaten ecosystem well-functioning and services provided. One invasive species with such potential is the New Zealand mud snail (NZMS) Potamopyrgus antipodarum . The aims of this study are focused on the quantitative review of (1) the NZMS impacts on ecosystem properties and their direct links with ecosystem services, and (2) the ecosystem services that can be affected by the NZMS. The high density reached by this species in most of the invaded ecosystems and its highly competitive ability affect ecosystem structure and functioning. However, some facilitation processes on native species may result in an improvement of some services. The NZMS tends to positively affect cultural services (88% positive cases) but negatively to provisioning services (77% of cases). Regarding, regulating and maintenance services, the proportions of positive and negative effects were similar (45% vs 36%, respectively). Therefore, the NZMS is a species with numerous negative impacts on ecosystem services. However, ecosystem services related to health (e.g., dilution effect against parasites) and research (e.g., biomonitoring) are cultural services that the NZMS can improve. No economic assessment of the impacts of the NZMS is available in the literature.

Spatial and temporal (annual and decadal) trends of metal(loid) concentrations and loads in an acid mine drainage-affected river - Elin Jennings; Patrizia Onnis; Rich Crane; Sean D.W. Comber; Patrick Byrne; Alex L. Riley; William M. Mayes; Adam P. Jarvis; Karen A. Hudson-Edwards (Science of The Total Environment, 2025)

Role of Lactic Acid Bacteria in Insecticide Residue Degradation - K. Kiruthika; A. Suganthi; Y.S. Johnson Thangaraj Edward; R. Anandham; P. Renukadevi; M. Murugan; Bimal Kumar Sahoo; Mohammad Ikram; P.G. Kavitha; M. Jayakanthan (Probiotics and Antimicrobial Proteins, 2025)

Ecosystem Changes Caused by Hydrological Change are Associated with Population Decline in a Formerly-Common Grazing Herbivore - W. J. Blaser-Hart; G. K. Shanungu; P. J. Edwards; J. Harms; S. P. H. Hart; G. A. Ellenbroek; H. A. M. J. van Gils; C. Simukonda; H. Olde Venterink (Ecosystems, 2025)
Few ecosystems are more sensitive to hydrological change than seasonally-flooded wetlands. Here, we investigate how changes in hydrological regimes caused by the construction of two dams have contributed to large changes in the structure and dynamics of the Kafue Flats, an internationally-important, partially-protected wetland ecosystem in Zambia. We use historical (1970) and contemporary (2013) data to describe changes in hydrology due to dam operations, and to compare the areal extent, distribution, and composition of the major wetland and dryland habitats in the pre- and post-dam periods. To understand the seasonal dynamics of the ecosystem and how these dynamics influence the seasonal movement and use of the ecosystem by the dominant grazing herbivore, the endangered Kafue lechwe, we combine data on annual hydrological variation with spatially- and/or temporally-explicit quantitative estimates of: (1) grass biomass and nutrient stocks, (2) distribution of lechwe across habitats, and (3) lechwe nutritional status. The operation of the dams has reduced hydrological variation, causing a loss of more than 50% of seasonally-flooded grasslands and probably promoting woody encroachment in some habitats. Our results demonstrate that Kafue lechwe is highly dependent on these seasonally-flooded grasslands during the dry season, when their nutritional status is otherwise critically low. In combination, we hypothesize that changes in the flooding regime driven by dam construction precipitated ecosystem-level changes that—together with other factors—may have contributed to a rapid historic, as well as ongoing decline in the lechwe population. Our study highlights potential consequences of the spatio-temporal homogenization of a previously highly variable ecosystem.

Improving compliance around protected areas through fair administration of rules - Harriet Ibbett; Leejiah Dorward; Julia P. G. Jones; Edward M. Kohi; Asri A. Dwiyahreni; Stephen Sankeni; Karlina Prayitno; Jesca Mchomvu; Joseph Kaduma; Andie Wijaya Saputra; Ika Yuni Agustin; Tyassanti Tryswidiarini; et al. (Conservation Biology, 2025)
Protected area management often depends heavily on law enforcement to secure compliance with rules. However, this can contribute to conflict between protected area authorities and local people, negatively affecting both human well‐being and conservation outcomes. Compliance is affected by many factors, including whether those who enforce rules are perceived to do so fairly, as well as the perceived rule‐related behavior of others. We used factorial survey experiments to explore how fair respondents living around protected areas in Indonesia and Tanzania perceive sanctions distributed by law enforcers to be. We presented scenarios to respondents to assess how crime type, offender characteristics, and corruption influenced their judgments regarding the fairness of administered sanctions. We also assessed how descriptive norms and corruption influenced individuals’ willingness to obey protected area rules. Data were collected from 229 people in Indonesia and 217 in Tanzania. Results showed that in both locations, lawful sanctions, such as arrests or warnings, were perceived as fairer, and sanctions that involved corruption were perceived as least fair. Attitudes toward protected area rules, corruption, and descriptive norms all influenced people's willingness to comply, whereas multidimensional poverty did not. Our results highlight the need for conservation policy and practice to move beyond narratives that focus on the need for more law enforcement. To improve protected area compliance and secure better outcomes for people and nature, conservation must focus on ensuring the fair administration of rules and enhancing the legitimacy of rules themselves.

A phylogenomic tree of wood-warblers (Aves: Parulidae): Dealing with good, bad, and ugly samples - Min Zhao; Jessica A. Oswald; Julie M. Allen; Hannah L. Owens; Peter A. Hosner; Robert P. Guralnick; Edward L. Braun; Rebecca T. Kimball (Molecular Phylogenetics and Evolution, 2025)

Americans’ support for climate justice - Jennifer P. Carman; Danning Lu; Matthew Ballew; Joshua Low; Marija Verner; Seth A. Rosenthal; Kristin Barendregt-Ludwig; Gerald Torres; Michel Gelobter; Kate McKenney; Irene Burga; Mark Magaña; et al. (Environmental Science & Policy, 2025)

Canopy complexity drives positive effects of tree diversity on productivity in two tree diversity experiments - Catherine Fahey; Dennis Choi; Jianmin Wang; Grant M. Domke; Joseph D. Edwards; Songlin Fei; Stephanie N. Kivlin; Elizabeth A. LaRue; Melissa K. McCormick; William J. McShea; Richard P. Phillips; Jamie Pullen; et al. (Ecology, 2025)
Forest canopy complexity (i.e., the three‐dimensional structure of the canopy) is often associated with increased species diversity as well as high primary productivity across natural forests. However, canopy complexity, tree diversity, and productivity are often confounded in natural forests, and the mechanisms of these relationships remain unclear. Here, we used two large tree diversity experiments in North America to assess three hypotheses: (1) increasing tree diversity leads to increased canopy complexity, (2) canopy complexity is positively related to tree productivity, and (3) the relationship between tree diversity and tree productivity is indirect and driven by the positive effects of canopy complexity. We found that increasing tree diversity from monocultures to mixtures of 12 species increases canopy complexity and productivity by up to 71% and 73%, respectively. Moreover, structural equation modeling indicates that the effects of tree diversity on productivity are indirect and mediated primarily by changes in internal canopy complexity. Ultimately, we suggest that increasing canopy complexity can be a major mechanism by which tree diversity enhances productivity in young forests.

Controls on spatial variation in porewater methane concentrations across United States tidal wetlands - Erika L. Koontz; Sarah M. Parker; Alice E. Stearns; Brian J. Roberts; Caitlin M. Young; Lisamarie Windham-Myers; Patricia Y. Oikawa; J. Patrick Megonigal; Genevieve L. Noyce; Edward J. Buskey; R. Kyle Derby; Robert P. Dunn; et al. (Science of The Total Environment, 2024)

A comprehensive analysis of new particle formation across the northwest Atlantic: Analysis of ACTIVATE airborne data - Soodabeh Namdari; Taiwo Ajayi; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Simon Kirschler; Hongyu Liu; John B. Nowak; Michael A. Shook; Cassidy Soloff; Kenneth L. Thornhill; et al. (Atmospheric Environment, 2024)

A Transcriptomic Comparative Study of Cranial Vasculature - Jianing Zhang; Jee-Yeon Ryu; Selena-Rae Tirado; Lawrence D. Dickinson; Aviva Abosch; M. Ali Aziz-Sultan; Alan S. Boulos; Daniel L. Barrow; H. Hunt Batjer; Tamar R. Binyamin; Spiros L. Blackburn; Edward F. Chang; et al. (Translational Stroke Research, 2024)

An evaluation of different approaches for estimating shear velocity in aeolian research studies - Pei Zhang; Brandon L. Edwards; Nicholas P. Webb; Andrew Trautz; John A. Gillies; Nancy P. Ziegler; Justin W. Van Zee (Aeolian Research, 2024)

Water sources and threshold behaviors of streamflow generation in a mountain headwater catchment - Xuegao Chen; Zhongbo Yu; Peng Yi; Peng Chen; Hyoun-Tae Hwang; Edward A. Sudicky; Slobodan P. Simonovic (Journal of Hydrology, 2024)

Unravelling the toxicity of carbon nanomaterials – From cellular interactions to mechanistic understanding - Bveledzani P. Makhado; Adewale O. Oladipo; Nozipho N. Gumbi; Lueta A. De Kock; Charlene Andraos; Mary Gulumian; Edward N. Nxumalo (Toxicology in Vitro, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Bioenergetic mapping of ‘healthy microbiomes’ via compound processing potential imprinted in gut and soil metagenomes - Craig Liddicoat; Robert A. Edwards; Michael Roach; Jake M. Robinson; Kiri Joy Wallace; Andrew D. Barnes; Joel Brame; Anna Heintz-Buschart; Timothy R. Cavagnaro; Elizabeth A. Dinsdale; Michael P. Doane; Nico Eisenhauer; et al. (Science of The Total Environment, 2024)

Remote sensing-based mangrove blue carbon assessment in the Asia-Pacific: A systematic review - Abhilash Dutta Roy; Pavithra S. Pitumpe Arachchige; Michael S. Watt; Apoorwa Kale; Mollie Davies; Joe Eu Heng; Redeat Daneil; G.A. Pabodha Galgamuwa; Lara G. Moussa; Kausila Timsina; Ewane Basil Ewane; Kerrylee Rogers; et al. (Science of The Total Environment, 2024)

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)

Environmental behaviour of iron and steel slags in coastal settings - Alex L. Riley; James Cameron; Ian T. Burke; Patrizia Onnis; John M. MacDonald; Catherine J. Gandy; Richard A. Crane; Patrick Byrne; Sean Comber; Adam P. Jarvis; Karen A. Hudson-Edwards; William M. Mayes (Environmental Science and Pollution Research, 2024)
Iron and steel slags have a long history of both disposal and beneficial use in the coastal zone. Despite the large volumes of slag deposited, comprehensive assessments of potential risks associated with metal(loid) leaching from iron and steel by-products are rare for coastal systems. This study provides a national-scale overview of the 14 known slag deposits in the coastal environment of Great Britain (those within 100 m of the mean high-water mark), comprising geochemical characterisation and leaching test data (using both low and high ionic strength waters) to assess potential leaching risks. The seaward facing length of slag deposits totalled at least 76 km, and are predominantly composed of blast furnace (iron-making) slags from the early to mid-20th Century. Some of these form tidal barriers and formal coastal defence structures, but larger deposits are associated with historical coastal disposal in many former areas of iron and steel production, notably the Cumbrian coast of England. Slag deposits are dominated by melilite phases (e.g. gehlenite), with evidence of secondary mineral formation (e.g. gypsum, calcite) indicative of weathering. Leaching tests typically show lower element (e.g. Ba, V, Cr, Fe) release under seawater leaching scenarios compared to deionised water, largely ascribable to the pH buffering provided by the former. Only Mn and Mo showed elevated leaching concentrations in seawater treatments, though at modest levels (<3 mg/L and 0.01 mg/L, respectively). No significant leaching of potentially ecotoxic elements such as Cr and V (mean leachate concentrations <0.006 mg/L for both) were apparent in seawater, which micro-X-Ray Absorption Near Edge Structure (μXANES) analysis show are both present in slags in low valence (and low toxicity) forms. Although there may be physical hazards posed by extensive erosion of deposits in high-energy coastlines, the data suggest seawater leaching of coastal iron and steel slags in the UK is likely to pose minimal environmental risk.

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Heavy rains and hydrogeological disasters on February 18th–19th, 2023, in the city of São Sebastião, São Paulo, Brazil: from meteorological causes to early warnings - Jose A. Marengo; Ana P. Cunha; Marcelo E. Seluchi; Pedro I. Camarinha; Giovanni Dolif; Vinicius B. Sperling; Enner H. Alcântara; Andrea M. Ramos; Marcio M. Andrade; Rodrigo A. Stabile; José Mantovani; Edward Park; et al. (Natural Hazards, 2024)

Quantification of age-related changes in the structure and mechanical function of skin with multiscale imaging - Alan E. Woessner; Nathan J. Witt; Jake D. Jones; Edward A. Sander; Kyle P. Quinn (GeroScience, 2024)
The mechanical properties of skin change during aging but the relationships between structure and mechanical function remain poorly understood. Previous work has shown that young skin exhibits a substantial decrease in tissue volume, a large macro-scale Poisson’s ratio, and an increase in micro-scale collagen fiber alignment during mechanical stretch. In this study, label-free multiphoton microscopy was used to quantify how the microstructure and fiber kinematics of aged mouse skin affect its mechanical function. In an unloaded state, aged skin was found to have less collagen alignment and more non-enzymatic collagen fiber crosslinks. Skin samples were then loaded in uniaxial tension and aged skin exhibited a lower mechanical stiffness compared to young skin. Aged tissue also demonstrated less volume reduction and a lower macro-scale Poisson’s ratio at 10% uniaxial strain, but not at 20% strain. The magnitude of 3D fiber realignment in the direction of loading was not different between age groups, and the amount of realignment in young and aged skin was less than expected based on theoretical fiber kinematics affine to the local deformation. These findings provide key insights on how the collagen fiber microstructure changes with age, and how those changes affect the mechanical function of skin, findings which may help guide wound healing or anti-aging treatments.

Adapting the Marine Stewardship Council risk-based framework to estimate impacts on seabirds, marine mammals, marine turtles and sea snakes - Stephanie D. Good; Kate Dewar; Polly Burns; Keith Sainsbury; Richard A. Phillips; Bryan P. Wallace; Caterina Fortuna; Vinay Udyawer; Bruce Robson; Edward F. Melvin; Rohan J.C. Currey (Marine Policy, 2024)

Long- and short-term soil storage methods other than freezing can be useful for DNA-based microbial community analysis - Joseph D. Edwards; Sarah J. Love; Richard P. Phillips; Songlin Fei; Grant Domke; John D. Parker; Melissa McCormick; Elizabeth A. LaRue; Jennifer A. Schweitzer; Joseph K. Bailey; James Fordyce; Stephanie N. Kivlin (Soil Biology and Biochemistry, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Mineral dust optical properties for remote sensing and global modeling: A review - Patricia Castellanos; Peter Colarco; W. Reed Espinosa; Scott D. Guzewich; Robert C. Levy; Ron L. Miller; Mian Chin; Ralph A. Kahn; Osku Kemppinen; Hans Moosmüller; Edward P. Nowottnick; Adriana Rocha-Lima; et al. (Remote Sensing of Environment, 2024)

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

Temperature Thresholds for Leaf Damage from Two Extreme Freeze Events (2018 and 2021) Near the Northern Range Limit of Black Mangroves (Avicennia germinans) in Southeastern North America - Simen Kaalstad; Michael J. Osland; Donna J. Devlin; C. Edward Proffitt; Laura C. Feher; Anna R. Armitage; Richard H. Day; Kathleen M. Swanson; Gordon H. Anderson; Brigid Berger; Just Cebrian; Karen L. Cummins; et al. (Estuaries and Coasts, 2024)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Neonicotinoid mixture alters trophic interactions in a freshwater aquatic invertebrate community - Claire Duchet; Fan Hou; Cailin A. Sinclair; Zhenyu Tian; Alyssa Kraft; Vojtech Kolar; Edward P. Kolodziej; Jenifer K. McIntyre; John D. Stark (Science of The Total Environment, 2023)

LP-25: The curious case of Adverse Outcome Pathways: the stressor agnostic approach bridging disciplines by embracing evidence from diverse initiating factors - J. Filipovska; L.-A. Clerbaux; A. Carusi; M.-J. Amorim; P. Nymark; V. Chauhan; M. Sachana; A. Beronius; S.W. Edwards; C. Wittwehr (Toxicology Letters, 2023)

John Squire: a leader and seminal contributor to experimental and theoretical muscle research for over 50 years - Pradeep K. Luther; Edward P. Morris; David A.D. Parry; Kenneth A. Taylor (Journal of Muscle Research and Cell Motility, 2023)

Bioanalytical and non-targeted mass spectrometric screening for contaminants of emerging concern in Southern California bight sediments - Alvine C. Mehinto; Bowen Du; Ellie Wenger; Zhenyu Tian; Edward P. Kolodziej; Dennis Apeti; Keith A. Maruya (Chemosphere, 2023)

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Sequence Divergence in Venom Genes Within and Between Montane Pitviper (Viperidae: Crotalinae: Cerrophidion) Species is Driven by Mutation–Drift Equilibrium - Ramses Alejandro Rosales-García; Rhett M. Rautsaw; Erich P. Hofmann; Christoph I. Grünwald; Hector Franz-Chavez; Ivan T. Ahumada-Carrillo; Ricardo Ramirez-Chaparro; Miguel Angel de la Torre-Loranca; Jason L. Strickland; Andrew J. Mason; Matthew L. Holding; Miguel Borja; et al. (Journal of Molecular Evolution, 2023)

Phylogeography of the Asian green mussel, Perna viridis: pronounced regional genetic differentiation is explained by major freshwater input into the Bay of Bengal - Jonathan P. A. Gardner; Jamila Patterson; Edward J. K. Patterson (Frontiers in Marine Science, 2023)
The Asian green mussel (AGM), Perna viridis , is a mussel of ecological and economic importance throughout much of the tropical and subtropical regions of Asia, from China and Korea in the east to Oman on the Arabian Peninsula in the west. We collated published DNA sequence data and then analysed 467 bp of cytochrome c oxidase I gene (COI) sequence variation from 649 mussels (576 from SE Asia and 73 from India) to test for regional differentiation. Analysis of molecular variation, a haplotype network and a neighbour-joining tree all revealed significant differentiation between mussels from India and those from SE Asia. We observed a greater number of segregating sites (haplotypes) and private haplotypes than expected for Indian mussels compared to SE Asian mussels, based on the respective sample sizes. Tests of neutrality revealed population expansion or a recent selective sweep for only the mussels from India. We suggest that the differentiation of the Indian from the SE Asian mussels is explained by the pronounced seasonal input of freshwater into the northern Bay of Bengal area, which acts as a (semi-permeable) barrier to gene flow between the two regions (i.e., east versus west of the Bay). This suggestion is based on the oceanography of the region and is consistent with the biogeography and reports of genetic breaks in a range of taxa in this region. Further targetted sampling of AGMs from the east coast of India, Bangladesh and Myanmar is required to test this hypothesis, and additional sampling of AGMs from west of India (e.g., Pakistan, Iran, the Arabian Peninsula) will also be informative. Finally, this study is based on the analysis of a single marker (COI) because this is all that is presently available from published sources but we note that the application of new molecular markers such as single nucleotide polymorphisms to newly collected mussel samples will greatly advance our understanding of the AGM genetic discontinuity and its age, and help test its geographical location and its nature (e.g., a steep/shallow cline or a stepped cline).

An improved method for determining frequency of multiple variants of SARS-CoV-2 in wastewater using qPCR assays - Meghan Fuzzen; Nathanael B.J. Harper; Hadi A. Dhiyebi; Nivetha Srikanthan; Samina Hayat; Leslie M. Bragg; Shelley W. Peterson; Ivy Yang; J.X. Sun; Elizabeth A. Edwards; John P. Giesy; Chand S. Mangat; et al. (Science of The Total Environment, 2023)

Greener residential environment is associated with increased bacterial diversity in outdoor ambient air - Jennifer N. Styles; Andrey I. Egorov; Shannon M. Griffin; Jo Klein; J.W. Scott; Elizabeth A. Sams; Edward Hudgens; Chris Mugford; Jill R. Stewart; Kun Lu; Ilona Jaspers; Scott P. Keely; et al. (Science of The Total Environment, 2023)

Rapidly Changing Range Limits in a Warming World: Critical Data Limitations and Knowledge Gaps for Advancing Understanding of Mangrove Range Dynamics in the Southeastern USA - Rémi Bardou; Michael J. Osland; Steven Scyphers; Christine Shepard; Karen E. Aerni; Jahson B. Alemu I; Robert Crimian; Richard H. Day; Nicholas M. Enwright; Laura C. Feher; Sarah L. Gibbs; Kiera O’Donnell; et al. (Estuaries and Coasts, 2023)
Climate change is altering species’ range limits and transforming ecosystems. For example, warming temperatures are leading to the range expansion of tropical, cold-sensitive species at the expense of their cold-tolerant counterparts. In some temperate and subtropical coastal wetlands, warming winters are enabling mangrove forest encroachment into salt marsh, which is a major regime shift that has significant ecological and societal ramifications. Here, we synthesized existing data and expert knowledge to assess the distribution of mangroves near rapidly changing range limits in the southeastern USA. We used expert elicitation to identify data limitations and highlight knowledge gaps for advancing understanding of past, current, and future range dynamics. Mangroves near poleward range limits are often shorter, wider, and more shrublike compared to their tropical counterparts that grow as tall forests in freeze-free, resource-rich environments. The northern range limits of mangroves in the southeastern USA are particularly dynamic and climate sensitive due to abundance of suitable coastal wetland habitat and the exposure of mangroves to winter temperature extremes that are much colder than comparable range limits on other continents. Thus, there is need for methodological refinements and improved spatiotemporal data regarding changes in mangrove structure and abundance near northern range limits in the southeastern USA. Advancing understanding of rapidly changing range limits is critical for foundation plant species such as mangroves, as it provides a basis for anticipating and preparing for the cascading effects of climate-induced species redistribution on ecosystems and the human communities that depend on their ecosystem services.

Sparing old-growth maximises conservation outcomes within selectively logged Amazonian rainforest - Gianluca Cerullo; Filipe França; Tom Finch; Philip Erm; Hannah Griffiths; Julio Louzada; Chris G. Bousfield; Mike R. Massam; Carlos A. Peres; Jos Barlow; Rhys E. Green; David P. Edwards; et al. (Biological Conservation, 2023)

Updated guidelines for gene nomenclature in wheat - S. A. Boden; R. A. McIntosh; C. Uauy; S. G. Krattinger; J. Dubcovsky; W. J. Rogers; X. C. Xia; E. D. Badaeva; A. R. Bentley; G. Brown-Guedira; M. Caccamo; L. Cattivelli; et al. (Theoretical and Applied Genetics, 2023)
Key message Here, we provide an updated set of guidelines for naming genes in wheat that has been endorsed by the wheat research community. Abstract The last decade has seen a proliferation in genomic resources for wheat, including reference- and pan-genome assemblies with gene annotations, which provide new opportunities to detect, characterise, and describe genes that influence traits of interest. The expansion of genetic information has supported growth of the wheat research community and catalysed strong interest in the genes that control agronomically important traits, such as yield, pathogen resistance, grain quality, and abiotic stress tolerance. To accommodate these developments, we present an updated set of guidelines for gene nomenclature in wheat. These guidelines can be used to describe loci identified based on morphological or phenotypic features or to name genes based on sequence information, such as similarity to genes characterised in other species or the biochemical properties of the encoded protein. The updated guidelines provide a flexible system that is not overly prescriptive but provides structure and a common framework for naming genes in wheat, which may be extended to related cereal species. We propose these guidelines be used henceforth by the wheat research community to facilitate integration of data from independent studies and allow broader and more efficient use of text and data mining approaches, which will ultimately help further accelerate wheat research and breeding.

Plant phenology drives seasonal changes in shear stress partitioning in a semi-arid rangeland - Nancy P. Ziegler; Nicholas P. Webb; John A. Gillies; Brandon L. Edwards; George Nikolich; Justin W. Van Zee; Brad F. Cooper; Dawn M. Browning; Ericha M. Courtright; Sandra L. LeGrand (Agricultural and Forest Meteorology, 2023)

Plant defense synergies and antagonisms affect performance of specialist herbivores of common milkweed - Collin B. Edwards; Stephen P. Ellner; Anurag A. Agrawal (Ecology, 2023)
As a general rule, plants defend against herbivores with multiple traits. The defense synergy hypothesis posits that some traits are more effective when co‐expressed with others compared to their independent efficacy. However, this hypothesis has rarely been tested outside of phytochemical mixtures, and seldom under field conditions. We tested for synergies between multiple defense traits of common milkweed ( Asclepias syriaca ) by assaying the performance of two specialist chewing herbivores on plants in natural populations. We employed regression and a novel application of random forests to identify synergies and antagonisms between defense traits. We found the first direct empirical evidence for two previously hypothesized defense synergies in milkweed (latex by secondary metabolites, latex by trichomes) and identified numerous other potential synergies and antagonisms. Our strongest evidence for a defense synergy was between leaf mass per area and low nitrogen content; given that these “leaf economic” traits typically covary in milkweed, a defense synergy could reinforce their co‐expression. We report that each of the plant defense traits showed context‐dependent effects on herbivores, and increased trait expression could well be beneficial to herbivores for some ranges of observed expression. The novel methods and findings presented here complement more mechanistic approaches to the study of plant defense diversity and provide some of the best evidence to date that multiple classes of plant defense synergize in their impact on insects. Plant defense synergies against highly specialized herbivores, as shown here, are consistent with ongoing reciprocal evolution between these antagonists.

A roadmap for ladybird conservation and recovery - António O. Soares; Danny Haelewaters; Olga M. C. C. Ameixa; Isabel Borges; Peter M. J. Brown; Pedro Cardoso; Michiel D. de Groot; Edward W. Evans; Audrey A. Grez; Axel Hochkirch; Milada Holecová; Alois Honěk; et al. (Conservation Biology, 2023)
Ladybirds (Coleoptera: Coccinellidae) provide services that are critical to food production, and they fulfill an ecological role as a food source for predators. The richness, abundance, and distribution of ladybirds, however, are compromised by many anthropogenic threats. Meanwhile, a lack of knowledge of the conservation status of most species and the factors driving their population dynamics hinders the development and implementation of conservation strategies for ladybirds. We conducted a review of the literature on the ecology, diversity, and conservation of ladybirds to identify their key ecological threats. Ladybird populations are most affected by climate factors, landscape composition, and biological invasions. We suggest mitigating actions for ladybird conservation and recovery. Short‐term actions include citizen science programs and education, protective measures for habitat recovery and threatened species, prevention of the introduction of non‐native species, and the maintenance and restoration of natural areas and landscape heterogeneity. Mid‐term actions involve the analysis of data from monitoring programs and insect collections to disentangle the effect of different threats to ladybird populations, understand habitat use by taxa on which there is limited knowledge, and quantify temporal trends of abundance, diversity, and biomass along a management‐intensity gradient. Long‐term actions include the development of a worldwide monitoring program based on standardized sampling to fill data gaps, increase explanatory power, streamline analyses, and facilitate global collaborations.

Coral disease outbreak at the remote Flower Garden Banks, Gulf of Mexico - Michelle A. Johnston; Michael S. Studivan; Ian C. Enochs; Adrienne M. S. Correa; Nicole Besemer; Ryan J. Eckert; Kimberly Edwards; Ryan Hannum; Xinping Hu; Marissa Nuttall; Kelly O’Connell; Ana M. Palacio-Castro; et al. (Frontiers in Marine Science, 2023)
East and West Flower Garden Bank (FGB) are part of Flower Garden Banks National Marine Sanctuary (FGBNMS) in the northwest Gulf of Mexico. This geographically-isolated reef system contains extensive coral communities with the highest coral cover (>50%) in the continental United States due, in part, to their remoteness and depth, and have historically exhibited low incidence of coral disease and bleaching despite ocean warming. Yet in late August 2022, disease-like lesions on seven coral species were reported during routine monitoring surveys on East and West FGB (2.1–2.6% prevalence). A series of rapid response cruises were conducted in September and October 2022 focused on 1) characterizing signs and epidemiological aspects of the disease across FGB and within long-term monitoring sites, 2) treating affected coral colonies with Base 2B plus amoxicillin, and 3) collecting baseline images through photostations and photomosaics. Marginal and/or multi-focal lesions and tissue loss were observed, often associated with substantial fish and invertebrate predation, affecting the dominant coral species Pseudodiploria strigosa (7–8% lesion prevalence), Colpophyllia natans (11–18%), and Orbicella spp. (1%). Characterizing this disease event during its early epidemic phase at East and West FGB provides a critical opportunity to observe how coral disease functions in a relatively healthy coral ecosystem versus on reefs chronically affected by various stressors (e.g., Caribbean reefs adjacent to urban centers). Insights into the etiology, spread, and impacts of the disease can ultimately inform efforts to mitigate its effects on coral communities.

Molecular and morphological analysis of Biddulphia sensu lato: a new diagnosis of Biddulphia, with a description of the new genera Biddulphiella and Neobrightwellia - Patricia A. Sims; Matt P. Ashworth; Edward C. Theriot; Schonna R. Manning (Marine Micropaleontology, 2023)

Fine particulate matter and incident coronary heart disease events up to 10 years of follow-up among Deepwater Horizon oil spill workers - Dazhe Chen; Dale P. Sandler; Alexander P. Keil; Gerardo Heiss; Eric A. Whitsel; Gregory C. Pratt; Patricia A. Stewart; Mark R. Stenzel; Caroline P. Groth; Sudipto Banerjee; Tran B. Huynh; Jessie K. Edwards; et al. (Environmental Research, 2023)

High sensitivity of tropical forest birds to deforestation at lower altitudes - Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Edicson Parra; Diego E. Martínez‐Revelo; Jose Manuel Ochoa Quintero; Torbjørn Haugaasen; Robert P. Freckleton; Jos Barlow; David P. Edwards (Ecology, 2023)
Habitat conversion is a major driver of tropical biodiversity loss, but its effects are poorly understood in montane environments. While community‐level responses to habitat loss display strong elevational dependencies, it is unclear whether these arise via elevational turnover in community composition and interspecific differences in sensitivity or elevational variation in environmental conditions and proximity to thermal thresholds. Here we assess the relative importance of inter‐ and intraspecific variation across the elevational gradient by quantifying how 243 forest‐dependent bird species vary in sensitivity to landscape‐scale forest loss across a 3000‐m elevational gradient in the Colombian Andes. We find that species that live at lower elevations are strongly affected by loss of forest in the nearby landscape, while those at higher elevations appear relatively unperturbed, an effect that is independent of phylogeny. Conversely, we find limited evidence of intraspecific elevational gradients in sensitivity, with populations displaying similar sensitivities to forest loss, regardless of where they exist in a species' elevational range. Gradients in biodiversity response to habitat loss thus appear to arise via interspecific gradients in sensitivity rather than proximity to climatically limiting conditions.

Caught red handed: modeling and confirmation of the myeloperoxidase ceruloplasmin alpha-thrombin complex - Yana A. Zabrodskaya; Vladimir V. Egorov; Alexey V. Sokolov; Alexey V. Shvetsov; Yulia E. Gorshkova; Oleksandr I. Ivankov; Valeria A. Kostevich; Nikolay P. Gorbunov; Edward S. Ramsay; Natalya D. Fedorova; Andrey B. Bondarenko; Vadim B. Vasilyev (BioMetals, 2022)

Riverine drift communities during larval fish dispersal over multiple recruitment years - Joseph P. Receveur; Alberto Doretto; Edward A. Baker; Douglas L. Larson; John M. Bauman; Ryan Walquist; M. Eric Benbow; Kim T. Scribner (Hydrobiologia, 2022)

Uterine fibroid polygenic risk score (PRS) associates and predicts risk for uterine fibroid - Jacqueline A. Piekos; Jacklyn N. Hellwege; Yanfei Zhang; Eric S. Torstenson; Gail P. Jarvik; Ozan Dikilitas; Iftikhar J. Kullo; Daniel J. Schaid; David R. Crosslin; Sarah A. Pendergrass; Ming Ta Michael Lee; Dan Roden; et al. (Human Genetics, 2022)

Population genomic structure in Goodman's mouse lemur reveals long‐standing separation of Madagascar's Central Highlands and eastern rainforests - George P. Tiley; Tobias van Elst; Helena Teixeira; Dominik Schüßler; Jordi Salmona; Marina B. Blanco; José M. Ralison; Blanchard Randrianambinina; Rodin M. Rasoloarison; Amanda R. Stahlke; Paul A. Hohenlohe; Lounès Chikhi; et al. (Molecular Ecology, 2022)
Madagascar's Central Highlands are largely composed of grasslands, interspersed with patches of forest. The historical perspective was that Madagascar's grasslands had anthropogenic origins, but emerging evidence suggests that grasslands were a component of the pre‐human Central Highlands vegetation. Consequently, there is now vigorous debate regarding the extent to which these grasslands have expanded due to anthropogenic pressures. Here, we shed light on the temporal dynamics of Madagascar's vegetative composition by conducting a population genomic investigation of Goodman's mouse lemur ( Microcebus lehilahytsara ; Cheirogaleidae). These small‐bodied primates occur both in Madagascar's eastern rainforests and in the Central Highlands, making them a valuable indicator species. Population divergences among forest‐dwelling mammals will reflect changes to their habitat, including fragmentation, whereas patterns of post‐divergence gene flow can reveal formerly wooded migration corridors. To explore these patterns, we used RADseq data to infer population genetic structure, demographic models of post‐divergence gene flow, and population size change through time. The results offer evidence that open habitats are an ancient component of the Central Highlands, and that widespread forest fragmentation occurred naturally during a period of decreased precipitation near the last glacial maximum. Models of gene flow suggest that migration across the Central Highlands has been possible from the Pleistocene through the recent Holocene via riparian corridors. Though our findings support the hypothesis that Central Highland grasslands predate human arrival, we also find evidence for human‐mediated population declines. This highlights the extent to which species imminently threatened by human‐mediated deforestation may already be vulnerable from paleoclimatic conditions.

Experimental validation of specialized questioning techniques in conservation - Harriet Ibbett; Leejiah Dorward; Asri A. Dwiyahreni; Julia P. G. Jones; Joseph Kaduma; Edward M. Kohi; Jesca Mchomvu; Karlina Prayitno; Humairah Sabiladiyni; Stephen Sankeni; Andie Wijaya Saputra; Jatna Supriatna; et al. (Conservation Biology, 2022)
Conservation increasingly relies on social science tools to understand human behavior. Specialized questioning techniques (SQTs) are a suite of methods designed to reduce bias in social surveys and are widely used to collect data on sensitive topics, including compliance with conservation rules. Most SQTs have been developed in Western, industrialized, educated, rich, and democratic countries, meaning their suitability in other contexts may be limited. Whether these techniques perform better than conventional direct questioning is important for those considering their use. We designed an experiment to validate the performance of four SQTs (unmatched count technique, randomized response technique, crosswise model, and bean method) against direct questions when asking about a commonly researched sensitive behavior in conservation, wildlife hunting. We developed fictional characters, and for each method asked respondents to report the answers that each fictional character should give when asked if they hunt wildlife. We collected data from 609 individuals living close to protected areas in two different cultural and socioeconomic contexts (Indonesia and Tanzania) to quantify the extent to which respondents understood and followed SQT instructions and to explore the sociodemographic factors that influenced a correct response. Data were modeled using binomial general linear mixed models. Participants were more likely to refuse to answer questions asked using SQTs compared with direct questions. Model results suggested that SQTs were harder for participants to understand. Demographic factors (e.g., age and education level) significantly influenced response accuracy. When sensitive responses to sensitive questions were required, all SQTs (excluding the bean method) outperformed direct questions, demonstrating that SQTs can successfully reduce sensitivity bias. However, when reviewing each method, most respondents (59–89%) reported they would feel uncomfortable using them to provide information on their own hunting behavior, highlighting the considerable challenge of encouraging truthful reporting on sensitive topics. Our results demonstrate the importance of assessing the suitability of social science methods prior to their implementation in conservation contexts.

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

A New Insight Into Amicula, a Genus of Tiny Marine Benthic Diatoms With the Description of Two New Tropical Species and the Largest Mitogenome Known for a Stramenopile - Romain Gastineau; Chunlian Li; Matt P. Ashworth; Andrzej Witkowski; Monique Turmel; Ewa Górecka; Thomas A. Frankovich; Anna Wachnicka; Christopher S. Lobban; Edward C. Theriot; Christian Otis; Przemysław Dąbek; et al. (Frontiers in Marine Science, 2022)
The current article focuses on the morphological and molecular characterization of the often inconspicuous genus Amicula. This recently erected genus from brackish and marine sediments was monotypic but here we describe two new tropical species: Amicula micronesica sp. nov. and Amicula vermiculata sp. nov. Once considered an incertae sedis genus regarding its higher rank taxonomy, its position among the family Diploneidaceae is proposed here by molecular phylogenetics. The complete plastid and mitochondrial genomes of Amicula micronesica sp. nov. are also presented here. It appears that the 177614-bp long mitogenome is the biggest yet recorded among stramenopiles, due to its invasion by 57 introns. Moreover, it utilizes the genetic code 4 for translation instead of the code 1 usually found among diatoms.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Plasma Kallikrein Contributes to Intracerebral Hemorrhage and Hypertension in Stroke-Prone Spontaneously Hypertensive Rats - Jian Guan; Allen C. Clermont; Loc-Duyen Pham; Tuna Ustunkaya; Alexey S. Revenko; A. Robert MacLeod; Edward P. Feener; Fabrício Simão (Translational Stroke Research, 2022)

Global biogeographic patterns of avian morphological diversity - Emma C. Hughes; David P. Edwards; Jen A. Bright; Elliot J.R. Capp; Christopher R. Cooney; Zoë K. Varley; Gavin H. Thomas (Ecology Letters, 2022)
Understanding the biogeographical patterns, and evolutionary and environmental drivers, underpinning morphological diversity are key for determining its origins and conservation. Using a comprehensive set of continuous morphological traits extracted from museum collections of 8353 bird species, including geometric morphometric beak shape data, we find that avian morphological diversity is unevenly distributed globally, even after controlling for species richness, with exceptionally dense packing of species in hyper‐diverse tropical hotspots. At the regional level, these areas also have high morphological variance, with species exhibiting high phenotypic diversity. Evolutionary history likely plays a key role in shaping these patterns, with evolutionarily old species contributing to niche expansion, and young species contributing to niche packing. Taken together, these results imply that the tropics are both ‘cradles’ and ‘museums’ of phenotypic diversity.

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

High-Resolution Spatiotemporal Dynamics of Harmful Algae in the Indian River Lagoon (Florida)—A Case Study of Aureoumbra lagunensis, Pyrodinium bahamense, and Pseudo-nitzschia - Cary B. Lopez; Charles L. Tilney; Eric Muhlbach; Josée N. Bouchard; Maria Célia Villac; Karen L. Henschen; Laura R. Markley; Stephanie Keller Abbe; Sugandha Shankar; Colin P. Shea; Leanne Flewelling; Matthew Garrett; et al. (Frontiers in Marine Science, 2021)
The Indian River Lagoon (IRL), located on the east coast of Florida, is a complex estuarine ecosystem that is negatively affected by recurring harmful algal blooms (HABs) from distinct taxonomic/functional groups. Enhanced monitoring was established to facilitate rapid quantification of three recurrent bloom taxa, Aureoumbra lagunensis , Pyrodinium bahamense , and Pseudo-nitzschia spp., and included corroborating techniques to improve the identification of small-celled nanoplankton (<10 μm in diameter). Identification and enumeration of these target taxa were conducted during 2015–2020 using a combination of light microscopy and species-specific approaches, specifically immunofluorescence flow cytometry as well as a newly developed qPCR assay for A. lagunensis presented here for the first time. An annual bloom index (ABI) was established for each taxon based on occurrence and abundance data. Blooms of A. lagunensis (>2 × 10 8 cells L –1 ) were observed in all 6 years sampled and across multiple seasons. In contrast, abundance of P. bahamense , largely driven by the annual temperature cycle that moderates life cycle transitions and growth, displayed a strong seasonal pattern with blooms (10 5 –10 7 cells L –1 ) generally developing in early summer and subsiding in autumn. However, P. bahamense bloom development was delayed and abundance was significantly lower in years and locations with sustained A. lagunensis blooms. Pseudo-nitzschia spp. were broadly distributed with sporadic bloom concentrations (reaching 10 7 cells L –1 ), but with minimal concentrations of the toxin domoic acid detected (<0.02 μg L –1 ). In summer 2020, multiple monitoring tools characterized a novel nano-cyanobacterium bloom (reaching 10 9 cells L –1 ) that coincided with a decline in A. lagunensis and persisted into autumn. Statistical and time-series analyses of this spatiotemporally intensive dataset highlight prominent patterns in variability for some taxa, but also identify challenges of characterizing mechanisms underlying more episodic yet persistent events. Nevertheless, the intersect of temperature and salinity as environmental proxies proved to be informative in delineating niche partitioning, not only in the case of taxa with long-standing data sets but also for seemingly unprecedented blooms of novel nanoplanktonic taxa.

The dangers of misrepresenting wildlife trade: response to Natusch et al. 2021 - David P. Edwards; Neil D'Cruze; Sandra Altherr; Alice Hughes; Jordi Janssen; Vincent Nijman; Stesha A. Pasachnik; Brett R. Scheffers; Chris R. Shepherd; Emerson Sy; Mark Auliya (Conservation Biology, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Coral reef resilience differs among islands within the Gulf of Mannar, southeast India, following successive coral bleaching events - K. Diraviya Raj; Greta S. Aeby; G. Mathews; Gareth J. Williams; Jamie M. Caldwell; R. L. Laju; M. Selva Bharath; P. Dinesh Kumar; A. Arasamuthu; N. Gladwin Gnana Asir; Lisa M. Wedding; Andrew J. Davies; et al. (Coral Reefs, 2021)

Are visual working memory and episodic memory distinct processes? Insight from stroke patients by lesion-symptom mapping - Selma Lugtmeijer; Linda Geerligs; Frank Erik de Leeuw; Edward H. F. de Haan; Roy P. C. Kessels; Anouk R. Smits; Ben A. Schmand; Edward H. F. de Haan; Frank Erik de Leeuw; Gert jan Luijckx; H. Steven Scholte; Joke M. Spikman; et al. (Brain Structure and Function, 2021)
Working memory and episodic memory are two different processes, although the nature of their interrelationship is debated. As these processes are predominantly studied in isolation, it is unclear whether they crucially rely on different neural substrates. To obtain more insight in this, 81 adults with sub-acute ischemic stroke and 29 elderly controls were assessed on a visual working memory task, followed by a surprise subsequent memory test for the same stimuli. Multivariate, atlas- and track-based lesion-symptom mapping (LSM) analyses were performed to identify anatomical correlates of visual memory. Behavioral results gave moderate evidence for independence between discriminability in working memory and subsequent memory, and strong evidence for a correlation in response bias on the two tasks in stroke patients. LSM analyses suggested there might be independent regions associated with working memory and episodic memory. Lesions in the right arcuate fasciculus were more strongly associated with discriminability in working memory than in subsequent memory, while lesions in the frontal operculum in the right hemisphere were more strongly associated with criterion setting in subsequent memory. These findings support the view that some processes involved in working memory and episodic memory rely on separate mechanisms, while acknowledging that there might also be shared processes.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Upland burning and grazing as strategies to offset climate-change effects on wetlands - Owen P. McKenna; David A. Renton; David M. Mushet; Edward S. DeKeyser (Wetlands Ecology and Management, 2021)
Wetland ecosystems perform a multitude of services valued by society and provide critical habitat for migratory birds and other wildlife. Despite their importance, wetlands have been lost to different local, regional, and global drivers. Remaining wetlands are extremely sensitive to changing temperature and precipitation regimes. Management of grassland areas in wetland catchments may be an effective strategy for counteracting potentially negative impacts of climate change on wetlands. Our objective was to estimate the effects of climate changes on wetland hydrology, and to explore strategies for increasing surface-water inputs to wetlands. We coupled a field study with process-based simulation modeling of wetland-water levels. We found that climate change could decrease the number of wetlands that hold ponded water during the waterfowl breeding season by 14% under a hot wet scenario or 29% under a hot dry scenario if no upland-management actions were taken. Upland burning reduced pond losses to 9% (hot wet) and 26% (hot dry). Upland grazing resulted in the smallest loss of ponded wetlands, 6% loss under the hot-and-wet scenario and 22% loss under the hot-and-dry scenario. Overall, water inputs could be increased by either burning or grazing of upland vegetation thereby reducing pond losses during the waterfowl breeding season. While field results suggest that both grazing and burning can reduce the vegetative structure that could lead to increases in runoff in grassland catchments, our model simulations indicated that additional actions may be needed for managers to minimize future meteorologically driven water losses.

Tropical land-use change alters trait-based community assembly rules for dung beetles and birds - Felicity A. Edwards; David P. Edwards; Keith C. Hamer; Tom M. Fayle (Oecologia, 2021)
Tropical rainforest disturbance and conversion are critical drivers of biodiversity loss. A key knowledge gap is understanding the impacts of habitat modification on mechanisms of community assembly, which are predicted to respond differently between taxa and across spatial scales. We use a null model approach to detect trait assembly of species at local- and landscape-scales, and then subdivide communities with different habitat associations and foraging guilds to investigate whether the detection of assembly mechanisms varies between groups. We focus on two indicator taxa, dung beetles and birds, across a disturbance gradient of primary rainforest, selectively logged rainforest, and oil palm plantations in Borneo, Southeast Asia. Random community assembly was predominant for dung beetles across habitats, whereas trait convergence, indicative of environmental filtering, occurred across the disturbance gradient for birds. Assembly patterns at the two spatial scales were similar. Subdividing for habitat association and foraging guild revealed patterns hidden when focusing on the overall community. Dung beetle forest specialists and habitat generalists showed opposing assembly mechanisms in primary forest, community assembly of habitat generalists for both taxa differed with disturbance intensity, and insectivorous birds strongly influenced overall community assembly relative to other guilds. Our study reveals the sensitivity of community assembly mechanisms to anthropogenic disturbance via a shift in the relative contribution of stochastic and deterministic processes. This highlights the need for greater understanding of how habitat modification alters species interactions and the importance of incorporating species’ traits within assessments.

Post-Stroke Working Memory Dysfunction: A Meta-Analysis and Systematic Review - Selma Lugtmeijer; Nikki A. Lammers; Edward H. F. de Haan; Frank-Erik de Leeuw; Roy P. C. Kessels (Neuropsychology Review, 2021)
This review investigates the severity and nature of post-stroke working memory deficits with reference to the multi-component model of working memory. We conducted a systematic search in PubMed up to March 2019 with search terms for stroke and memory. Studies on adult stroke patients, that included a control group, and assessed working memory function, were selected. Effect sizes (Hedges’ g ) were extracted from 50 studies (in total 3,084 stroke patients) based on the sample size, mean and standard deviation of patients and controls. Performance of stroke patients was compared to healthy controls on low-load (i.e. capacity) and high-load (executively demanding) working memory tasks, grouped by modality (verbal, non-verbal). A separate analysis compared patients in the sub-acute and the chronic stage. Longitudinal studies and effects of lesion location were systematically reviewed. Stroke patients demonstrated significant deficits in working memory with a moderate effect size for both low-load (Hedges’ g = -.58 [-.82 to -.43]) and high-load (Hedges’ g = -.59 [-.73 to -.45]) tasks. The effect sizes were comparable for verbal and non-verbal material. Systematically reviewing the literature showed that working memory deficits remain prominent in the chronic stage of stroke. Lesions in a widespread fronto-parietal network are associated with working memory deficits. Stroke patients show decrements of moderate magnitude in all subsystems of working memory. This review clearly demonstrates the global nature of the impairment in working memory post-stroke.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Ontogenetic scaling of the gastrointestinal tract of a marsupial foregut fermenter, the western grey kangaroo Macropus fuliginosus melanops - Adam J. Munn; Edward P. Snelling; David A. Taggart; Roger S. Seymour (Journal of Comparative Physiology B, 2021)

Perlecan Domain-V Enhances Neurogenic Brain Repair After Stroke in Mice - Amanda L. Trout; Michael P. Kahle; Jill M. Roberts; Aileen Marcelo; Leon de Hoog; Jeffery A. Boychuk; Stephen L. Grupke; Antonio Berretta; Emma K. Gowing; Carie R. Boychuk; Amanda A. Gorman; Danielle N. Edwards; et al. (Translational Stroke Research, 2021)
The extracellular matrix fragment perlecan domain V is neuroprotective and functionally restorative following experimental stroke. As neurogenesis is an important component of chronic post-stroke repair, and previous studies have implicated perlecan in developmental neurogenesis, we hypothesized that domain V could have a broad therapeutic window by enhancing neurogenesis after stroke. We demonstrated that domain V is chronically increased in the brains of human stroke patients, suggesting that it is present during post-stroke neurogenic periods. Furthermore, perlecan deficient mice had significantly less neuroblast precursor cells after experimental stroke. Seven-day delayed domain V administration enhanced neurogenesis and restored peri-infarct excitatory synaptic drive to neocortical layer 2/3 pyramidal neurons after experimental stroke. Domain V’s effects were inhibited by blockade of α2β1 integrin, suggesting the importance of α2β1 integrin to neurogenesis and domain V neurogenic effects. Our results demonstrate that perlecan plays a previously unrecognized role in post-stroke neurogenesis and that delayed DV administration after experimental stroke enhances neurogenesis and improves recovery in an α2β1 integrin-mediated fashion. We conclude that domain V is a clinically relevant neuroprotective and neuroreparative novel stroke therapy with a broad therapeutic window.

Scenarios for Global Aquaculture and Its Role in Human Nutrition - Jessica A. Gephart; Christopher D. Golden; Frank Asche; Ben Belton; Cecile Brugere; Halley E. Froehlich; Jillian P. Fry; Benjamin S. Halpern; Christina C. Hicks; Robert C. Jones; Dane H. Klinger; David C. Little; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Spatial analysis of urine zinc (Zn) concentration for women of reproductive age and school age children in Malawi - Felix P. Phiri; E. Louise Ander; R. Murray Lark; Edward J. M. Joy; Alexander A. Kalimbira; Parminder S. Suchdev; Jellita Gondwe; Elliott M. Hamilton; Michael J. Watts; Martin R. Broadley (Environmental Geochemistry and Health, 2021)
Zinc (Zn) is an essential micronutrient, and Zn deficiency remains a major global public health challenge. Recognised biomarkers of population Zn status include blood plasma or serum Zn concentration and proxy data such as dietary Zn intake and prevalence of stunting. Urine Zn concentration is rarely used to assess population Zn status. This study assessed the value of urine Zn concentration as a biomarker of population Zn status using a nationally representative sample of non-pregnant women of reproductive age (WRA) and school-aged children (SAC) in Malawi. Spot (casual) urine samples were collected from 741 WRA and 665 SAC. Urine Zn concentration was measured by inductively coupled plasma mass spectrometry with specific gravity adjustment for hydration status. Data were analysed using a linear mixed model with a spatially correlated random effect for between-cluster variation. The effect of time of sample collection (morning or afternoon), and gender (for SAC), on urine Zn concentration were examined. There was spatial dependence in urine Zn concentration between clusters among SAC but not WRA, which indicates that food system or environmental factors can influence urine Zn concentration. Mapping urine Zn concentration could potentially identify areas where the prevalence of Zn deficiency is greater and thus where further sampling or interventions might be targeted. There was no evidence for differences in urine Zn concentration between gender ( P = 0.69) or time of sample collection ( P = 0.85) in SAC. Urine Zn concentration was greater in afternoon samples for WRA ( P = 0.003). Relationships between urine Zn concentration, serum Zn concentration, dietary Zn intake, and potential food systems covariates warrant further study.

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Representation of Boundary-Layer Processes in Numerical Weather Prediction and Climate Models - John M. Edwards; Anton C. M. Beljaars; Albert A. M. Holtslag; Adrian P. Lock (Boundary-Layer Meteorology, 2020)

Trait‐based ecology at large scales: Assessing functional trait correlations, phylogenetic constraints and spatial variability using open data - Martin A. Wilkes; François Edwards; J. Iwan Jones; John F. Murphy; Judy England; Nikolai Friberg; Daniel Hering; N. LeRoy Poff; Philippe Usseglio‐Polatera; Wilco C. E. P. Verberk; Jon Webb; Lee E. Brown (Global Change Biology, 2020)
The growing use of functional traits in ecological research has brought new insights into biodiversity responses to global environmental change. However, further progress depends on overcoming three major challenges involving (a) statistical correlations between traits, (b) phylogenetic constraints on the combination of traits possessed by any single species, and (c) spatial effects on trait structure and trait–environment relationships. Here, we introduce a new framework for quantifying trait correlations, phylogenetic constraints and spatial variability at large scales by combining openly available species’ trait, occurrence and phylogenetic data with gridded, high‐resolution environmental layers and computational modelling. Our approach is suitable for use among a wide range of taxonomic groups inhabiting terrestrial, marine and freshwater habitats. We demonstrate its application using freshwater macroinvertebrate data from 35 countries in Europe. We identified a subset of available macroinvertebrate traits, corresponding to a life‐history model with axes of resistance, resilience and resource use, as relatively unaffected by correlations and phylogenetic constraints. Trait structure responded more consistently to environmental variation than taxonomic structure, regardless of location. A re‐analysis of existing data on macroinvertebrate communities of European alpine streams supported this conclusion, and demonstrated that occurrence‐based functional diversity indices are highly sensitive to the traits included in their calculation. Overall, our findings suggest that the search for quantitative trait–environment relationships using single traits or simple combinations of multiple traits is unlikely to be productive. Instead, there is a need to embrace the value of conceptual frameworks linking community responses to environmental change via traits which correspond to the axes of life‐history models. Through a novel integration of tools and databases, our flexible framework can address this need.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Treatment cost and access to care: experiences of young women diagnosed with breast cancer - Sujha Subramanian; Florence K. L. Tangka; Patrick Edwards; Madeleine Jones; Tim Flanigan; Jenya Kaganova; Kevin Smith; Cheryll C. Thomas; Nikki A. Hawkins; Juan L. Rodriguez; Gery P. Guy; Temeika Fairley (Cancer Causes & Control, 2020)

Historical biogeography of smoothhound sharks (genus Mustelus ) of Southern Africa reveals multiple dispersal events from the Northern Hemisphere - Simo N. Maduna; Kelvin L. Hull; Edward D. Farrell; Jessica J. Boomer; Ana Veríssimo; Ilaria A. M. Marino; Carlotta Mazzoldi; Lorenzo Zane; Sabine P. Wintner; Mikhail V. Chesalin; Charlene da Silva; Chrysoula Gubili; et al. (Systematics and Biodiversity, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Eroding islands of Gulf of Mannar, Southeast India: a consequence of long-term impact of coral mining and climate change - N. Gladwin Gnana Asir; P. Dinesh Kumar; A. Arasamuthu; G. Mathews; K. Diraviya Raj; T. K. Ashok Kumar; Deepak S. Bilgi; J. K. Patterson Edward (Natural Hazards, 2020)

Fitness, independent of physical activity is associated with cerebral blood flow in adults at risk for Alzheimer’s disease - Ryan J. Dougherty; Elizabeth A. Boots; Jacob B. Lindheimer; Aaron J. Stegner; Stephanie Van Riper; Dorothy F. Edwards; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; Sanjay Asthana; Bruce P. Hermann; et al. (Brain Imaging and Behavior, 2020)

Exploiting the genome of Thinopyrum elongatum to expand the gene pool of hexaploid wheat - Lauren Baker; Surbhi Grewal; Cai-yun Yang; Stella Hubbart-Edwards; Duncan Scholefield; Stephen Ashling; Amanda J. Burridge; Alexandra M. Przewieslik-Allen; Paul A. Wilkinson; Ian P. King; Julie King (Theoretical and Applied Genetics, 2020)
Key message One hundred and thirty four introgressions from Thinopyrum elongatum have been transferred into a wheat background and were characterised using 263 SNP markers. Abstract Species within the genus Thinopyrum have been shown to carry genetic variation for a very wide range of traits including biotic and abiotic stresses and quality. Research has shown that one of the species within this genus, Th. elongatum , has a close relationship with the genomes of wheat making it a highly suitable candidate to expand the gene pool of wheat. Homoeologous recombination, in the absence of the Ph1 gene, has been exploited to transfer an estimated 134 introgressions from Th. elongatum into a hexaploid wheat background. The introgressions were detected and characterised using 263 single nucleotide polymorphism markers from a 35 K Axiom ® Wheat-Relative Genotyping Array, spread across seven linkage groups and validated using genomic in situ hybridisation. The genetic map had a total length of 187.8 cM and the average chromosome length was 26.8 cM. Comparative analyses of the genetic map of Th. elongatum and the physical map of hexaploid wheat confirmed previous work that indicated good synteny at the macro-level, although Th. elongatum does not contain the 4A/5A/7B translocation found in wheat.

Nutritional factors modulating plant and fruit susceptibility to pathogens: BARD workshop, Haifa, Israel, February 25–26, 2018 - Dov Prusky; Leandro José de Assis; Riccardo Baroncelli; Ernesto P. Benito; Virginia Casado del Castillo; Timothy Chaya; Shay Covo; José María Díaz-Mínguez; Nicole M. Donofrio; Eduardo Espeso; Tânia Ribeiro Fernandes; Gustavo H. Goldman; et al. (Phytoparasitica, 2020)

Can One-Run-Fixed-Arrhenius Kerogen Analysis Provide Comparable Organofacies Results to Detailed Palynological Analysis? A Case Study from a Prospective Mississippian Source Rock Reservoir (Bowland Shale, UK) - Sarah M. Newport; Jan A. I. Hennissen; James P. Armstrong; Kevin G. Taylor; Leo P. Newport; Edward Hough (Natural Resources Research, 2020)

The Rapid Regenerative Response of a Model Sea Anemone Species Exaiptasia pallida Is Characterised by Tissue Plasticity and Highly Coordinated Cell Communication - Chloé A. van der Burg; Ana Pavasovic; Edward K. Gilding; Elise S. Pelzer; Joachim M. Surm; Hayden L. Smith; Terence P. Walsh; Peter J. Prentis (Marine Biotechnology, 2020)

The association of HFE gene H63D polymorphism with endurance athlete status and aerobic capacity: novel findings and a meta-analysis - Ekaterina A. Semenova; Eri Miyamoto-Mikami; Egor B. Akimov; Fatima Al-Khelaifi; Haruka Murakami; Hirofumi Zempo; Elena S. Kostryukova; Nikolay A. Kulemin; Andrey K. Larin; Oleg V. Borisov; Motohiko Miyachi; Daniil V. Popov; et al. (European Journal of Applied Physiology, 2020)
Purpose Iron is an important component of the oxygen-binding proteins and may be critical to optimal athletic performance. Previous studies have suggested that the G allele of C/G rare variant (rs1799945), which causes H63D amino acid replacement, in the HFE is associated with elevated iron indexes and may give some advantage in endurance-oriented sports. The aim of the present study was to investigate the association between the HFE H63D polymorphism and elite endurance athlete status in Japanese and Russian populations, aerobic capacity and to perform a meta-analysis using current findings and three previous studies. Methods The study involved 315 international-level endurance athletes (255 Russian and 60 Japanese) and 809 healthy controls (405 Russian and 404 Japanese). Genotyping was performed using micro-array analysis or by PCR. VO 2max in 46 male Russian endurance athletes was determined using gas analysis system. Results The frequency of the iron-increasing CG/GG genotypes was significantly higher in Russian (38.0 vs 24.9%; OR 1.85, P = 0.0003) and Japanese (13.3 vs 5.0%; OR 2.95, P = 0.011) endurance athletes compared to ethnically matched controls. The meta-analysis using five cohorts (two French, Japanese, Spanish, and Russian; 586 athletes and 1416 controls) showed significant prevalence of the CG/GG genotypes in endurance athletes compared to controls (OR 1.96, 95% CI 1.58–2.45; P = 1.7 × 10 –9 ). Furthermore, the HFE G allele was associated with high V̇O 2max in male athletes [CC: 61.8 (6.1), CG/GG: 66.3 (7.8) ml/min/kg; P = 0.036]. Conclusions We have shown that the HFE H63D polymorphism is strongly associated with elite endurance athlete status, regardless ethnicities and aerobic capacity in Russian athletes.

Acclimation to a thermoneutral environment abolishes age-associated alterations in heart rate and heart rate variability in conscious, unrestrained mice - Jessie E. Axsom; Alay P. Nanavati; Carolyn A. Rutishauser; Janet E. Bonin; Jack M. Moen; Edward G. Lakatta (GeroScience, 2020)
Mice are among the most widely used translational models of cardiovascular aging and offer a method to quickly assess lifespan changes in a controlled environment. The standard laboratory temperature (20–22 °C), however, imposes a cold stress on mice that causes an increase in sympathetic nervous system–mediated activation of brown adipose tissue (BAT) to maintain a core body temperature of 36–37 °C. Thus, while physiologic data obtained recapitulate human physiology to a certain degree, interpretations of previous research in mice may have been contaminated by a cold stress, due to housing mice below their thermoneutral zone (30 °C). The purpose of this investigation was to examine how chronic sympathetic stimulation evoked by acclimation to 20 °C might obscure interpretation of changes in autonomic modulation of heart rate (HR) and heart rate variability (HRV) that accompany advancing age. HR and HRV before and after administration of a dual-autonomic blockade were measured via in-vivo ECG in young (3 months) and aged (30 months) male C57BL/6 telemetry-implanted mice following temperature acclimation for 3 days at 30 °C or 20 °C. Mean basal and intrinsic HR of both young and aged mice became markedly reduced at 30 °C compared to 20 °C. In both age groups, HRV parameters in time, frequency, and non-linear domains displayed increased variability at 30 °C compared to 20 °C under basal conditions. Importantly, age-associated declines in HRV observed at 20 °C were ameliorated when mice were studied at their thermoneutral ambient temperature of 30 °C. Thus, an accurate understanding of autonomic modulation of cardiovascular functions in mice of advanced age requires that they are housed in a metabolically neutral environment.

Secondary forest fragments offer important carbon and biodiversity cobenefits - Fabio A. R. Matos; Luiz F. S. Magnago; Carlos Aquila Chan Miranda; Luis F. T. de Menezes; Markus Gastauer; Nathália V. H. Safar; Carlos E. G. R. Schaefer; Mônica P. da Silva; Marcelo Simonelli; Felicity A. Edwards; Sebastião V. Martins; João A. A. Meira‐Neto; et al. (Global Change Biology, 2020)
Tropical forests store large amounts of carbon and high biodiversity, but are being degraded at alarming rates. The emerging global Forest and Landscape Restoration (FLR) agenda seeks to limit global climate change by removing carbon dioxide from the atmosphere through the growth of trees. In doing so, it may also protect biodiversity as a free cobenefit, which is vital given the massive shortfall in funding for biodiversity conservation. We investigated whether natural forest regeneration on abandoned pastureland offers such cobenefits, focusing for the first time on the recovery of taxonomic diversity (TD), phylogenetic diversity (PD) and functional diversity (FD) of trees, including the recovery of threatened and endemic species richness, within isolated secondary forest (SF) fragments. We focused on the globally threatened Brazilian Atlantic Forest, where commitments have been made to restore 1 million hectares under FLR. Three decades after land abandonment, regenerating forests had recovered ~20% (72 Mg/ha) of the above‐ground carbon stocks of a primary forest (PF), with cattle pasture containing just 3% of stocks relative to PFs. Over this period, SF recovered ~76% of TD, 84% of PD and 96% of FD found within PFs. In addition, SFs had on average recovered 65% of threatened and ~30% of endemic species richness of primary Atlantic forest. Finally, we find positive relationships between carbon stock and tree diversity recovery. Our results emphasize that SF fragments offer cobenefits under FLR and other carbon‐based payments for ecosystem service schemes (e.g. carbon enhancements under REDD+). They also indicate that even isolated patches of SF could help to mitigate climate change and the biodiversity extinction crisis by recovering species of high conservation concern and improving landscape connectivity.

Quantitative trait loci and differential gene expression analyses reveal the genetic basis for negatively associated β-carotene and starch content in hexaploid sweetpotato [Ipomoea batatas (L.) Lam.] - Dorcus C. Gemenet; Guilherme da Silva Pereira; Bert De Boeck; Joshua C. Wood; Marcelo Mollinari; Bode A. Olukolu; Federico Diaz; Veronica Mosquera; Reuben T. Ssali; Maria David; Mercy N. Kitavi; Gabriela Burgos; et al. (Theoretical and Applied Genetics, 2020)
Key message β-Carotene content in sweetpotato is associated with the Orange and phytoene synthase genes; due to physical linkage of phytoene synthase with sucrose synthase , β-carotene and starch content are negatively correlated. Abstract In populations depending on sweetpotato for food security, starch is an important source of calories, while β-carotene is an important source of provitamin A. The negative association between the two traits contributes to the low nutritional quality of sweetpotato consumed, especially in sub-Saharan Africa. Using a biparental mapping population of 315 F 1 progeny generated from a cross between an orange-fleshed and a non-orange-fleshed sweetpotato variety, we identified two major quantitative trait loci (QTL) on linkage group (LG) three (LG3) and twelve (LG12) affecting starch, β-carotene, and their correlated traits, dry matter and flesh color. Analysis of parental haplotypes indicated that these two regions acted pleiotropically to reduce starch content and increase β-carotene in genotypes carrying the orange-fleshed parental haplotype at the LG3 locus. Phytoene synthase and sucrose synthase, the rate-limiting and linked genes located within the QTL on LG3 involved in the carotenoid and starch biosynthesis, respectively, were differentially expressed in Beauregard versus Tanzania storage roots. The Orange gene, the molecular switch for chromoplast biogenesis, located within the QTL on LG12 while not differentially expressed was expressed in developing roots of the parental genotypes. We conclude that these two QTL regions act together in a cis and trans manner to inhibit starch biosynthesis in amyloplasts and enhance chromoplast biogenesis, carotenoid biosynthesis, and accumulation in orange-fleshed sweetpotato. Understanding the genetic basis of this negative association between starch and β-carotene will inform future sweetpotato breeding strategies targeting sweetpotato for food and nutritional security.

Culturable microbial composition in the midgut of Aedes aegypti strains with different susceptibility to dengue-2 virus infection - Edward H. Molina-Henao; M. Yineth Graffe; Elsa P. De La Cadena; Idalba M. Serrato; Adriana Correa; Lizeth V. Romero; Paola A. Caicedo; Clara B. Ocampo (Symbiosis, 2020)

Frag SAD : A database of diversity and species abundance distributions from habitat fragments - Jonathan M. Chase; Mario Liebergesell; Alban Sagouis; Felix May; Shane A. Blowes; Åke Berg; Enrico Bernard; Berry J. Brosi; Marc W. Cadotte; Luis Cayuela; Adriano G. Chiarello; Jean‐Francois Cosson; et al. (Ecology, 2019)
Habitat destruction is the single greatest anthropogenic threat to biodiversity. Decades of research on this issue have led to the accumulation of hundreds of data sets comparing species assemblages in larger, intact, habitats to smaller, more fragmented, habitats. Despite this, little synthesis or consensus has been achieved, primarily because of non‐standardized sampling methodology and analyses of notoriously scale‐dependent response variables (i.e., species richness). To be able to compare and contrast the results of habitat fragmentation on species’ assemblages, it is necessary to have the underlying data on species abundances and sampling intensity, so that standardization can be achieved. To accomplish this, we systematically searched the literature for studies where abundances of species in assemblages (of any taxa) were sampled from many habitat patches that varied in size. From these, we extracted data from several studies, and contacted authors of studies where appropriate data were collected but not published, giving us 117 studies that compared species assemblages among habitat fragments that varied in area. Less than one‐half (41) of studies came from tropical forests of Central and South America, but there were many studies from temperate forests and grasslands from all continents except Antarctica. Fifty‐four of the studies were on invertebrates (mostly insects), but there were several studies on plants (15), birds (16), mammals (19), and reptiles and amphibians (13). We also collected qualitative information on the length of time since fragmentation. With data on total and relative abundances (and identities) of species, sampling effort, and affiliated meta‐data about the study sites, these data can be used to more definitively test hypotheses about the role of habitat fragmentation in altering patterns of biodiversity. There are no copyright restrictions. Please cite this data paper and the associated Dryad data set if the data are used in publications.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

The impact of secondary forest regeneration on ground-dwelling ant communities in the Tropical Andes - Matthew G. Hethcoat; Bethany J. King; Fernando Fernandez Castiblanco; Claudia M. Ortiz-Sepúlveda; Fabian Camilo Prada Achiardi; Felicity A. Edwards; Claudia Medina; James J. Gilroy; Torbjørn Haugaasen; David P. Edwards (Oecologia, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Effect of rhizomania on red table-beet biomass production and molecular characterization of an isolate of Beet necrotic yellow vein virus from Brazil - Viviana M. Camelo-García; Juan P. Edwards Molina; Tatsuya Nagata; Jorge A. M. Rezende; João M. F. Silva (European Journal of Plant Pathology, 2019)

Addressing limitations in existing ‘simplified’ liquefaction triggering evaluation procedures: application to induced seismicity in the Groningen gas field - R. A. Green; J. J. Bommer; A. Rodriguez-Marek; B. W. Maurer; P. J. Stafford; B. Edwards; P. P. Kruiver; G. de Lange; J. van Elk (Bulletin of Earthquake Engineering, 2019)

Late Holocene environmental changes and anthropogenic impact in Dee Why Lagoon, New South Wales - C. Chagué; D. Edwards; J. Ruszczyk; P. Gadd; A. Zawadzki; G. Jacobsen; D. Fierro; J. Goralewski; L. Clement; A. Albani (Australian Journal of Earth Sciences, 2019)

Seagrass restoration in Gulf of Mannar, Tamil Nadu, Southeast India: a viable management tool - J. K. Patterson Edward; K. Diraviya Raj; G. Mathews; P. Dinesh Kumar; A. Arasamuthu; Nisha D’ Souza; Deepak S. Bilgi (Environmental Monitoring and Assessment, 2019)

Seasonal variations in household food insecurity and dietary diversity and their association with maternal and child nutritional status in rural Ethiopia - Kedir T. Roba; Thomas P. O’Connor; Nora M. O’Brien; Chanyalew S. Aweke; Zenebe A. Kahsay; Nick Chisholm; Edward Lahiff (Food Security, 2019)

Dispersal limitations and historical factors determine the biogeography of specialized terrestrial protists - David Singer; Edward A. D. Mitchell; Richard J. Payne; Quentin Blandenier; Clément Duckert; Leonardo D. Fernández; Bertrand Fournier; Cristián E. Hernández; Gustaf Granath; Håkan Rydin; Luca Bragazza; Natalia G. Koronatova; et al. (Molecular Ecology, 2019)
Recent studies show that soil eukaryotic diversity is immense and dominated by micro‐organisms. However, it is unclear to what extent the processes that shape the distribution of diversity in plants and animals also apply to micro‐organisms. Major diversification events in multicellular organisms have often been attributed to long‐term climatic and geological processes, but the impact of such processes on protist diversity has received much less attention as their distribution has often been believed to be largely cosmopolitan. Here, we quantified phylogeographical patterns in Hyalosphenia papilio , a large testate amoeba restricted to Holarctic Sphagnum ‐dominated peatlands, to test if the current distribution of its genetic diversity can be explained by historical factors or by the current distribution of suitable habitats. Phylogenetic diversity was higher in Western North America, corresponding to the inferred geographical origin of the H. papilio complex, and was lower in Eurasia despite extensive suitable habitats. These results suggest that patterns of phylogenetic diversity and distribution can be explained by the history of Holarctic Sphagnum peatland range expansions and contractions in response to Quaternary glaciations that promoted cladogenetic range evolution, rather than the contemporary distribution of suitable habitats. Species distributions were positively correlated with climatic niche breadth, suggesting that climatic tolerance is key to dispersal ability in H. papilio . This implies that, at least for large and specialized terrestrial micro‐organisms, propagule dispersal is slow enough that historical processes may contribute to their diversification and phylogeographical patterns and may partly explain their very high overall diversity.

Simultaneous‐count models to estimate abundance from counts of unmarked individuals with imperfect detection - Gerard Edward Ryan; Emily Nicholson; Jonathan C. Eames; Thomas N. E. Gray; Robin Loveridge; Simon P. Mahood; Phearun Sum; Michael A. McCarthy (Conservation Biology, 2019)
We developed a method to estimate population abundance from simultaneous counts of unmarked individuals over multiple sites. We considered that at each sampling occasion, individuals in a population could be detected at 1 of the survey sites or remain undetected and used either multinomial or binomial simultaneous‐count models to estimate abundance, the latter being equivalent to an N‐mixture model with one site. We tested model performance with simulations over a range of detection probabilities, population sizes, growth rates, number of years, sampling occasions, and sites. We then applied our method to 3 critically endangered vulture species in Cambodia to demonstrate the real‐world applicability of the model and to provide the first abundance estimates for these species in Cambodia. Our new approach works best when existing methods are expected to perform poorly (i.e., few sites and large variation in abundance among sites) and if individuals may move among sites between sampling occasions. The approach performed better when there were >8 sampling occasions and net probability of detection was high (>0.5). We believe our approach will be useful in particular for simultaneous surveys at aggregation sites, such as roosts. The method complements existing approaches for estimating abundance of unmarked individuals and is the first method designed specifically for simultaneous counts.

Development and validation of an exome-based SNP marker set for identification of the St, Jr and Jvs genomes of Thinopyrym intermedium in a wheat background - Andras Cseh; Caiyun Yang; Stella Hubbart-Edwards; Duncan Scholefield; Stephen S. Ashling; Amanda J. Burridge; Paul A. Wilkinson; Ian P. King; Julie King; Surbhi Grewal (Theoretical and Applied Genetics, 2019)

Magmatic platinum nanoparticles in metasomatic silicate glasses and sulfides from Patagonian mantle xenoliths - José María González-Jiménez; Josep Roqué-Rosell; Abigail Jiménez-Franco; Santiago Tassara; Fernando Nieto; Fernando Gervilla; Sandra Baurier; Joaquín A. Proenza; Edward Saunders; Artur P. Deditius; Manuel Schilling; Alexandre Corgne (Contributions to Mineralogy and Petrology, 2019)

Land‐sparing agriculture sustains higher levels of avian functional diversity than land sharing - Patrick G. Cannon; James J. Gilroy; Joseph A. Tobias; Alex Anderson; Torbjørn Haugaasen; David P. Edwards (Global Change Biology, 2019)
The ecological impacts of meeting rising demands for food production can potentially be mitigated by two competing land‐use strategies: off‐setting natural habitats through intensification of existing farmland (land sparing), or elevating biodiversity within the agricultural matrix via the integration of “wildlife‐friendly” habitat features (land sharing). However, a key unanswered question is whether sparing or sharing farming would best conserve functional diversity, which can promote ecosystem stability and resilience to future land‐use change. Focusing on bird communities in tropical cloud forests of the Colombian Andes, we test the performance of each strategy in conserving functional diversity. We show that multiple components of avian functional diversity in farmland are positively related to the proximity and extent of natural forest. Using landscape and community simulations, we also show that land‐sparing agriculture conserves greater functional diversity and predicts higher abundance of species supplying key ecological functions than land sharing, with sharing becoming progressively inferior with increasing isolation from remnant forest. These results suggest low‐intensity agriculture is likely to conserve little functional diversity unless large blocks of adjacent natural habitat are protected, consistent with land sparing. To ensure the retention of functionally diverse ecosystems, we urgently need to implement mechanisms for increasing farmland productivity whilst protecting spared land.

Better Regional Ocean Observing Through Cross-National Cooperation: A Case Study From the Northeast Pacific - John A. Barth; Susan E. Allen; Edward P. Dever; Richard K. Dewey; Wiley Evans; Richard A. Feely; Jennifer L. Fisher; Jonathan P. Fram; Burke Hales; Debby Ianson; Jennifer Jackson; Kim Juniper; et al. (Frontiers in Marine Science, 2019)

Future Directions in Conservation Research on Petrels and Shearwaters - Airam Rodríguez; José M. Arcos; Vincent Bretagnolle; Maria P. Dias; Nick D. Holmes; Maite Louzao; Jennifer Provencher; André F. Raine; Francisco Ramírez; Beneharo Rodríguez; Robert A. Ronconi; Rebecca S. Taylor; et al. (Frontiers in Marine Science, 2019)

Pharmacokinetics and safety of glecaprevir and pibrentasvir in HCV-negative subjects with hepatic impairment - Matthew P. Kosloski; Haoyu Wang; David Pugatch; Federico J. Mensa; Edward Gane; Eric Lawitz; Thomas C. Marbury; Richard A. Preston; Jens Kort; Wei Liu (European Journal of Clinical Pharmacology, 2019)

Understanding the evolving phenotype of vascular complications in telomere biology disorders - Cecilia Higgs; Yanick J. Crow; Denise M. Adams; Emmanuel Chang; Don Hayes; Utz Herbig; James N. Huang; Ryan Himes; Kunal Jajoo; F. Brad Johnson; Susan D. Reynolds; Yoshihiro Yonekawa; et al. (Angiogenesis, 2019)

Bioassays on the role of tomato, potato and sweet pepper as sources of Tomato chlorosis virus transmitted by Bemisia tabaci MEAM1 - T. Mituti; J. P. Edwards Molina; J. A. M. Rezende (European Journal of Plant Pathology, 2018)

Factors Affecting Disaster Preparedness, Response, and Recovery Using the Community Capitals Framework - Amber Himes-Cornell; Carlos Ormond; Kristin Hoelting; Natalie C. Ban; J. Zachary Koehn; Edward H. Allison; Eric C. Larson; Daniel H. Monson; Henry P. Huntington; Thomas A. Okey (Coastal Management, 2018)

A lateral-to-mesial organization of human ventral visual cortex at birth - P. Barttfeld; S. Abboud; H. Lagercrantz; U. Adén; N. Padilla; A. D. Edwards; L. Cohen; M. Sigman; S. Dehaene; G. Dehaene-Lambertz (Brain Structure and Function, 2018)

Spatiotemporal heterogeneity and patterning of developing renal blood vessels - Edward Daniel; D. Berfin Azizoglu; Anne R. Ryan; Tezin A. Walji; Christopher P. Chaney; Gabrielle I. Sutton; Thomas J. Carroll; Denise K. Marciano; Ondine Cleaver (Angiogenesis, 2018)

“Periderm Disorder Syndrome”: a New Name for the Syndrome Formerly Referred to as Pink Eye - Edward C. Lulai; Robert P. Sabba; Philip Nolte; Neil C. Gudmestad; Gary A. Secor (American Journal of Potato Research, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Neural correlates of verbal memory in youth with heavy prenatal alcohol exposure - Lauren A. Gross; Eileen M. Moore; Jeffrey R. Wozniak; Claire D. Coles; Julie A. Kable; Elizabeth R. Sowell; Kenneth L. Jones; Edward P. Riley; Sarah N. Mattson (Brain Imaging and Behavior, 2018)

Characteristics and consequences of lava dome collapse at Ruawahia, Taupo Volcanic Zone, New Zealand - P. A. Ashwell; B. M. Kennedy; M. Edwards; J. W. Cole (Bulletin of Volcanology, 2018)

TOX3 Variants Are Involved in Restless Legs Syndrome and Parkinson’s Disease with Opposite Effects - Sadaf Mohtashami; Qin He; Jennifer A. Ruskey; Sirui Zhou; Patrick A. Dion; Richard P. Allen; Christopher J. Earley; Edward A. Fon; Lan Xiong; Nicolas Dupre; Yves Dauvilliers; Guy A. Rouleau; et al. (Journal of Molecular Neuroscience, 2018)

Tropical forests are thermally buffered despite intensive selective logging - Rebecca A. Senior; Jane K. Hill; Suzan Benedick; David P. Edwards (Global Change Biology, 2018)
Tropical rainforests are subject to extensive degradation by commercial selective logging. Despite pervasive changes to forest structure, selectively logged forests represent vital refugia for global biodiversity. The ability of these forests to buffer temperature‐sensitive species from climate warming will be an important determinant of their future conservation value, although this topic remains largely unexplored. Thermal buffering potential is broadly determined by: (i) the difference between the “macroclimate” (climate at a local scale, m to ha) and the “microclimate” (climate at a fine‐scale, mm to m, that is distinct from the macroclimate); (ii) thermal stability of microclimates (e.g. variation in daily temperatures); and (iii) the availability of microclimates to organisms. We compared these metrics in undisturbed primary forest and intensively logged forest on Borneo, using thermal images to capture cool microclimates on the surface of the forest floor, and information from dataloggers placed inside deadwood, tree holes and leaf litter. Although major differences in forest structure remained 9–12 years after repeated selective logging, we found that logging activity had very little effect on thermal buffering, in terms of macroclimate and microclimate temperatures, and the overall availability of microclimates. For 1°C warming in the macroclimate, temperature inside deadwood, tree holes and leaf litter warmed slightly more in primary forest than in logged forest, but the effect amounted to

Anthropometric characteristics and ovarian cancer risk and survival - Albina N. Minlikeeva; Kirsten B. Moysich; Paul C. Mayor; John L. Etter; Rikki A. Cannioto; Roberta B. Ness; Kristen Starbuck; Robert P. Edwards; Brahm H. Segal; Sashikant Lele; Kunle Odunsi; Brenda Diergaarde; et al. (Cancer Causes & Control, 2018)

Evaluation of Nitrogen Concentration in Final Effluent of Advanced Nitrogen-Removal Onsite Wastewater Treatment Systems (OWTS) - Brittany V. Lancellotti; George W. Loomis; Kevin P. Hoyt; Edward Avizinis; Jose A. Amador (Water, Air, & Soil Pollution, 2017)

Facultative CAM photosynthesis (crassulacean acid metabolism) in four species of Calandrinia, ephemeral succulents of arid Australia - Joseph A. M. Holtum; Lillian P. Hancock; Erika J. Edwards; Klaus Winter (Photosynthesis Research, 2017)

Functional connectivity abnormalities and associated cognitive deficits in fetal alcohol Spectrum disorders (FASD) - Jeffrey R. Wozniak; Bryon A. Mueller; Sarah N. Mattson; Claire D. Coles; Julie A. Kable; Kenneth L. Jones; Christopher J. Boys; Kelvin O. Lim; Edward P. Riley; Elizabeth R. Sowell (Brain Imaging and Behavior, 2017)

The tooth, the whole tooth and nothing but the tooth: tooth shape and ontogenetic shift dynamics in the white shark Carcharodon carcharias - G. C. A. French; M. Stürup; S. Rizzuto; J. H. van Wyk; D. Edwards; R. W. Dolan; S. P. Wintner; A. V. Towner; W. O. H. Hughes (Journal of Fish Biology, 2017)
Results from this study of the white shark Carcharodon carcharias include measurements obtained using a novel photographic method that reveal significant differences between the sexes in the relationship between tooth cuspidity and shark total length, and a novel ontogenetic change in male tooth shape. Males exhibit broader upper first teeth and increased distal inclination of upper third teeth with increasing length, while females do not present a consistent morphological change. Substantial individual variation, with implications for pace of life syndrome, was present in males and tooth polymorphism was suggested in females. Sexual differences and individual variation may play major roles in ontogenetic changes in tooth morphology in C. carcharias , with potential implications for their foraging biology. Such individual and sexual differences should be included in studies of ontogenetic shift dynamics in other species and systems.

Asymmetric responses of primary productivity to precipitation extremes: A synthesis of grassland precipitation manipulation experiments - Kevin R. Wilcox; Zheng Shi; Laureano A. Gherardi; Nathan P. Lemoine; Sally E. Koerner; David L. Hoover; Edward Bork; Kerry M. Byrne; James Cahill; Scott L. Collins; Sarah Evans; Anna K. Gilgen; et al. (Global Change Biology, 2017)
Climatic changes are altering Earth's hydrological cycle, resulting in altered precipitation amounts, increased interannual variability of precipitation, and more frequent extreme precipitation events. These trends will likely continue into the future, having substantial impacts on net primary productivity ( NPP ) and associated ecosystem services such as food production and carbon sequestration. Frequently, experimental manipulations of precipitation have linked altered precipitation regimes to changes in NPP . Yet, findings have been diverse and substantial uncertainty still surrounds generalities describing patterns of ecosystem sensitivity to altered precipitation. Additionally, we do not know whether previously observed correlations between NPP and precipitation remain accurate when precipitation changes become extreme. We synthesized results from 83 case studies of experimental precipitation manipulations in grasslands worldwide. We used meta‐analytical techniques to search for generalities and asymmetries of aboveground NPP ( ANPP ) and belowground NPP ( BNPP ) responses to both the direction and magnitude of precipitation change. Sensitivity (i.e., productivity response standardized by the amount of precipitation change) of BNPP was similar under precipitation additions and reductions, but ANPP was more sensitive to precipitation additions than reductions; this was especially evident in drier ecosystems. Additionally, overall relationships between the magnitude of productivity responses and the magnitude of precipitation change were saturating in form. The saturating form of this relationship was likely driven by ANPP responses to very extreme precipitation increases, although there were limited studies imposing extreme precipitation change, and there was considerable variation among experiments. This highlights the importance of incorporating gradients of manipulations, ranging from extreme drought to extreme precipitation increases into future climate change experiments. Additionally, policy and land management decisions related to global change scenarios should consider how ANPP and BNPP responses may differ, and that ecosystem responses to extreme events might not be predicted from relationships found under moderate environmental changes.

Qualitative and quantitative factors affecting the relationship between Canola leaf spot epidemic and stem base canker (Leptosphaeria maculans) in Argentina - J. P. Edwards Molina; A. Escande; G. Cendoya; F. Quiroz (Australasian Plant Pathology, 2017)

Optimisation of kelp (Laminaria digitata) gametophyte growth and gametogenesis: effects of photoperiod and culture media - J. J. Ratcliff; A. Soler-Vila; D. Hanniffy; M. P. Johnson; M. D. Edwards (Journal of Applied Phycology, 2017)

Genomic analysis of chimeric human cytomegalovirus vaccine candidates derived from strains Towne and Toledo - Nicolás M. Suárez; Betty Lau; George M. Kemble; Ronzo Lee; Edward S. Mocarski; Gavin W. G. Wilkinson; Stuart P. Adler; Michael A. McVoy; Andrew J. Davison (Virus Genes, 2017)

Continued feeding on Diporeia by deepwater sculpin in Lake Huron - Patricia A. Thompson; Edward F. Roseman; Kevin M. Keeler; Timothy P. O’Brien; Dustin A. Bowser (Environmental Biology of Fishes, 2017)

Litter decay controlled by temperature, not soil properties, affecting future soil carbon - Edward G. Gregorich; Henry Janzen; Benjamin H. Ellert; Bobbi L. Helgason; Budong Qian; Bernie J. Zebarth; Denis A. Angers; Ronald P. Beyaert; Craig F. Drury; Scott D. Duguid; William E. May; Brian G. McConkey; et al. (Global Change Biology, 2017)
Widespread global changes, including rising atmospheric CO 2 concentrations, climate warming and loss of biodiversity, are predicted for this century; all of these will affect terrestrial ecosystem processes like plant litter decomposition. Conversely, increased plant litter decomposition can have potential carbon‐cycle feedbacks on atmospheric CO 2 levels, climate warming and biodiversity. But predicting litter decomposition is difficult because of many interacting factors related to the chemical, physical and biological properties of soil, as well as to climate and agricultural management practices. We applied 13 C‐labelled plant litter to soil at ten sites spanning a 3500‐km transect across the agricultural regions of Canada and measured its decomposition over five years. Despite large differences in soil type and climatic conditions, we found that the kinetics of litter decomposition were similar once the effect of temperature had been removed, indicating no measurable effect of soil properties. A two‐pool exponential decay model expressing undecomposed carbon simply as a function of thermal time accurately described kinetics of decomposition. ( R 2 = 0.94; RMSE = 0.0508). Soil properties such as texture, cation exchange capacity, pH and moisture, although very different among sites, had minimal discernible influence on decomposition kinetics. Using this kinetic model under different climate change scenarios, we projected that the time required to decompose 50% of the litter (i.e. the labile fractions) would be reduced by 1–4 months, whereas time required to decompose 90% of the litter (including recalcitrant fractions) would be reduced by 1 year in cooler sites to as much as 2 years in warmer sites. These findings confirm quantitatively the sensitivity of litter decomposition to temperature increases and demonstrate how climate change may constrain future soil carbon storage, an effect apparently not influenced by soil properties.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Evolution of a small hydrothermal eruption episode through a mud pool of varying depth and rheology, White Island, NZ - M. J. Edwards; B. M. Kennedy; A. D. Jolly; B. Scheu; P. Jousset (Bulletin of Volcanology, 2017)

Role of polysaccharides in food, digestion, and health - A. Lovegrove; C. H. Edwards; I. De Noni; H. Patel; S. N. El; T. Grassby; C. Zielke; M. Ulmius; L. Nilsson; P. J. Butterworth; P. R Ellis; P. R. Shewry (Critical Reviews in Food Science and Nutrition, 2017)

A high-density SNP genotyping array for Brassica napus and its ancestral diploid species based on optimised selection of single-locus markers in the allotetraploid genome - Wayne E. Clarke; Erin E. Higgins; Joerg Plieske; Ralf Wieseke; Christine Sidebottom; Yogendra Khedikar; Jacqueline Batley; Dave Edwards; Jinling Meng; Ruiyuan Li; Cynthia Taylor Lawley; Jérôme Pauquet; et al. (Theoretical and Applied Genetics, 2016)

Prevalence of enteric bacterial parasites with respect to anthropogenic factors among commensal rhesus macaques in Dehradun, India - Brianne A. Beisner; Krishna N. Balasubramaniam; Kristine Fernandez; Allison Heagerty; Shannon K. Seil; Edward R. Atwill; Brij K. Gupta; P. C. Tyagi; Netrapal. P. S. Chauhan; Bishan S. Bonal; Priya. R. Sinha; Brenda McCowan (Primates, 2016)

Dissolved Copper, Nickel and Lead in Tampamachoco Lagoon and Tuxpan River Estuary in the SW Gulf of Mexico - E. P. Garduño Ruiz; L. Rosales Hoz; A. Carranza Edwards (Bulletin of Environmental Contamination and Toxicology, 2016)

Accuracy of Rapid Tests Used for Analysis of Advanced Onsite Wastewater Treatment System Effluent - Brittany V. Lancellotti; Robert J. Bercaw; George W. Loomis; Kevin P. Hoyt; Edward J. Avizinis; Jose A. Amador (Water, Air, & Soil Pollution, 2016)

Use of a coupled soil-root-leaf model to optimise phosphate fertiliser use efficiency in barley - J. Heppell; S. Payvandi; P. Talboys; K. C. Zygalakis; D. Langton; R. Sylvester-Bradley; A. C. Edwards; R. Walker; P. Withers; D. L. Jones; T. Roose (Plant and Soil, 2016)

Fine-scale spatial variation in ice cover and surface temperature trends across the surface of the Laurentian Great Lakes - Lacey A. Mason; Catherine M. Riseng; Andrew D. Gronewold; Edward S. Rutherford; Jia Wang; Anne Clites; Sigrid D. P. Smith; Peter B. McIntyre (Climatic Change, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Mapping adipose and muscle tissue expression quantitative trait loci in African Americans to identify genes for type 2 diabetes and obesity - Satria P. Sajuthi; Neeraj K. Sharma; Jeff W. Chou; Nicholette D. Palmer; David R. McWilliams; John Beal; Mary E. Comeau; Lijun Ma; Jorge Calles-Escandon; Jamehl Demons; Samantha Rogers; Kristina Cherry; et al. (Human Genetics, 2016)

Taxon interactions control the distributions of cryoconite bacteria colonizing a High Arctic ice cap - Jarishma K. Gokul; Andrew J. Hodson; Eli R. Saetnan; Tristram D. L. Irvine‐Fynn; Philippa J. Westall; Andrew P. Detheridge; Nozomu Takeuchi; Jennifer Bussell; Luis A. J. Mur; Arwyn Edwards (Molecular Ecology, 2016)
Microbial colonization of glacial ice surfaces incurs feedbacks which affect the melting rate of the ice surface. Ecosystems formed as microbe–mineral aggregates termed cryoconite locally reduce ice surface albedo and represent foci of biodiversity and biogeochemical cycling. Consequently, greater understanding the ecological processes in the formation of functional cryoconite ecosystems upon glacier surfaces is sought. Here, we present the first bacterial biogeography of an ice cap, evaluating the respective roles of dispersal, environmental and biotic filtration occurring at local scales in the assembly of cryoconite microbiota. 16S rRNA gene amplicon semiconductor sequencing of cryoconite colonizing a Svalbard ice cap coupled with digital elevation modelling of physical parameters reveals the bacterial community is dominated by a ubiquitous core of generalist taxa, with evidence for a moderate pairwise distance–decay relationship. While geographic position and melt season duration are prominent among environmental predictors of community structure, the core population of taxa appears highly influential in structuring the bacterial community. Taxon co‐occurrence network analysis reveals a highly modular community structured by positive interactions with bottleneck taxa, predominantly Actinobacteria affiliated to isolates from soil humus. In contrast, the filamentous cyanobacterial taxon (assigned to Leptolyngbya/Phormidesmis pristleyi ) which dominates the community and binds together granular cryoconite are poorly connected to other taxa. While our study targeted one ice cap, the prominent role of generalist core taxa with close environmental relatives across the global cryosphere indicate discrete roles for cosmopolitan Actinobacteria and Cyanobacteria as respective keystone taxa and ecosystem engineers of cryoconite ecosystems colonizing ice caps.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Tree‐mycorrhizal associations detected remotely from canopy spectral properties - Joshua B. Fisher; Sean Sweeney; Edward R. Brzostek; Tom P. Evans; Daniel J. Johnson; Jonathan A. Myers; Norman A. Bourg; Amy T. Wolf; Robert W. Howe; Richard P. Phillips (Global Change Biology, 2016)
A central challenge in global ecology is the identification of key functional processes in ecosystems that scale, but do not require, data for individual species across landscapes. Given that nearly all tree species form symbiotic relationships with one of two types of mycorrhizal fungi – arbuscular mycorrhizal ( AM ) and ectomycorrhizal ( ECM ) fungi – and that AM ‐ and ECM ‐dominated forests often have distinct nutrient economies, the detection and mapping of mycorrhizae over large areas could provide valuable insights about fundamental ecosystem processes such as nutrient cycling, species interactions, and overall forest productivity. We explored remotely sensed tree canopy spectral properties to detect underlying mycorrhizal association across a gradient of AM ‐ and ECM ‐dominated forest plots. Statistical mining of reflectance and reflectance derivatives across moderate/high‐resolution Landsat data revealed distinctly unique phenological signals that differentiated AM and ECM associations. This approach was trained and validated against measurements of tree species and mycorrhizal association across ~130 000 trees throughout the temperate United States. We were able to predict 77% of the variation in mycorrhizal association distribution within the forest plots ( P

Genomic insights into the carbohydrate catabolism of Cairneyella variabilis gen. nov. sp. nov., the first reports from a genome of an ericoid mycorrhizal fungus from the southern hemisphere - David J. Midgley; Carly P. Rosewarne; Paul Greenfield; Dongmei Li; Cassandra J. Vockler; Catherine J. Hitchcock; Nicole A. Sawyer; Robyn Brett; Jacqueline Edwards; John I. Pitt; Nai Tran-Dinh (Mycorrhiza, 2016)

Combined evidence indicates that Perna indica Kuriakose and Nair 1976 is Perna perna (Linnaeus, 1758) from the Oman region introduced into southern India more than 100 years ago - Jonathan P. A. Gardner; Jamila Patterson; Sanil George; J. K. Patterson Edward (Biological Invasions, 2016)

An integrated pan‐tropical biomass map using multiple reference datasets - Valerio Avitabile; Martin Herold; Gerard B. M. Heuvelink; Simon L. Lewis; Oliver L. Phillips; Gregory P. Asner; John Armston; Peter S. Ashton; Lindsay Banin; Nicolas Bayol; Nicholas J. Berry; Pascal Boeckx; et al. (Global Change Biology, 2016)
We combined two existing datasets of vegetation aboveground biomass ( AGB ) ( Proceedings of the National Academy of Sciences of the United States of America , 108 , 2011, 9899; Nature Climate Change , 2 , 2012, 182) into a pan‐tropical AGB map at 1‐km resolution using an independent reference dataset of field observations and locally calibrated high‐resolution biomass maps, harmonized and upscaled to 14 477 1‐km AGB estimates. Our data fusion approach uses bias removal and weighted linear averaging that incorporates and spatializes the biomass patterns indicated by the reference data. The method was applied independently in areas (strata) with homogeneous error patterns of the input (Saatchi and Baccini) maps, which were estimated from the reference data and additional covariates. Based on the fused map, we estimated AGB stock for the tropics (23.4 N–23.4 S) of 375 Pg dry mass, 9–18% lower than the Saatchi and Baccini estimates. The fused map also showed differing spatial patterns of AGB over large areas, with higher AGB density in the dense forest areas in the Congo basin, Eastern Amazon and South‐East Asia, and lower values in Central America and in most dry vegetation areas of Africa than either of the input maps. The validation exercise, based on 2118 estimates from the reference dataset not used in the fusion process, showed that the fused map had a RMSE 15–21% lower than that of the input maps and, most importantly, nearly unbiased estimates (mean bias 5 Mg dry mass ha −1 vs. 21 and 28 Mg ha −1 for the input maps). The fusion method can be applied at any scale including the policy‐relevant national level, where it can provide improved biomass estimates by integrating existing regional biomass maps as input maps and additional, country‐specific reference datasets.

The invertebrate ecology of the Chalk aquifer in England (UK) - L. Maurice; A. R. Robertson; D. White; L. Knight; T. Johns; F. Edwards; M. Arietti; J. P. R. Sorensen; D. Weitowitz; B. P. Marchant; J. P. Bloomfield (Hydrogeology Journal, 2016)

Alcohol exposure in utero is associated with decreased gray matter volume in neonates - Kirsten A. Donald; J. P. Fouche; Annerine Roos; Nastassja Koen; Fleur M. Howells; Edward P. Riley; Roger P. Woods; Heather J. Zar; Katherine L. Narr; Dan J. Stein (Metabolic Brain Disease, 2016)

The impact of the introduction of fidaxomicin on the management of Clostridium difficile infection in seven NHS secondary care hospitals in England: a series of local service evaluations - S. D. Goldenberg; S. Brown; L. Edwards; D. Gnanarajah; P. Howard; D. Jenkins; D. Nayar; M. Pasztor; S. Oliver; T. Planche; J. A. T. Sandoe; P. Wade; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Negative impacts of high temperatures on growth of black spruce forests intensify with the anticipated climate warming - Martin P. Girardin; Edward H. Hogg; Pierre Y. Bernier; Werner A. Kurz; Xiao Jing Guo; Guillaume Cyr (Global Change Biology, 2016)
An increasing number of studies conclude that water limitations and heat stress may hinder the capacity of black spruce ( Picea mariana (Mill.) B.S.P.) trees, a dominant species of Canada's boreal forests, to grow and assimilate atmospheric carbon. However, there is currently no scientific consensus on the future of these forests over the next century in the context of widespread climate warming. The large spatial extent of black spruce forests across the Canadian boreal forest and associated variability in climate, demography, and site conditions pose challenges for projecting future climate change responses. Here we provide an evaluation of the impacts of climate warming and drying, as well as increasing [CO 2 ], on the aboveground productivity of black spruce forests across Canada south of 60°N for the period 1971 to 2100. We use a new extensive network of tree‐ring data obtained from Canada's National Forest Inventory, spatially explicit simulations of net primary productivity (NPP) and its drivers, and multivariate statistical modeling. We found that soil water availability is a significant driver of black spruce interannual variability in productivity across broad areas of the western to eastern Canadian boreal forest. Interannual variability in productivity was also found to be driven by autotrophic respiration in the warmest regions. In most regions, the impacts of soil water availability and respiration on interannual variability in productivity occurred during the phase of carbohydrate accumulation the year preceding tree‐ring formation. Results from projections suggest an increase in the importance of soil water availability and respiration as limiting factors on NPP over the next century due to warming, but this response may vary to the extent that other factors such as carbon dioxide fertilization, and respiration acclimation to high temperature, contribute to dampening these limitations.

Comments on manuscript—Zheng, J., Huynh, T., Gasparon, M., Ng, J. and Noller, B., 2013. Human health risk assessment of lead from mining activities at semi-arid locations in the context of total lead exposure. Environmental Science and Pollution Research, 20, 8404–8416 - M. P. Taylor; A. K. Mackay; N. C. Munksgaard; K. A. Hudson-Edwards (Environmental Science and Pollution Research, 2015)

Decadal warming causes a consistent and persistent shift from heterotrophic to autotrophic respiration in contrasting permafrost ecosystems - Caitlin E. Hicks Pries; Richard S. P. van Logtestijn; Edward A. G. Schuur; Susan M. Natali; Johannes H. C. Cornelissen; Rien Aerts; Ellen Dorrepaal (Global Change Biology, 2015)
Soil carbon in permafrost ecosystems has the potential to become a major positive feedback to climate change if permafrost thaw increases heterotrophic decomposition. However, warming can also stimulate autotrophic production leading to increased ecosystem carbon storage—a negative climate change feedback. Few studies partitioning ecosystem respiration examine decadal warming effects or compare responses among ecosystems. Here, we first examined how 11 years of warming during different seasons affected autotrophic and heterotrophic respiration in a bryophyte‐dominated peatland in Abisko, Sweden. We used natural abundance radiocarbon to partition ecosystem respiration into autotrophic respiration, associated with production, and heterotrophic decomposition. Summertime warming decreased the age of carbon respired by the ecosystem due to increased proportional contributions from autotrophic and young soil respiration and decreased proportional contributions from old soil. Summertime warming's large effect was due to not only warmer air temperatures during the growing season, but also to warmer deep soils year‐round. Second, we compared ecosystem respiration responses between two contrasting ecosystems, the Abisko peatland and a tussock‐dominated tundra in Healy, Alaska. Each ecosystem had two different timescales of warming (

Defining adult bonefish (Albula vulpes) movement corridors around Grand Bahama in the Bahamian Archipelago - Karen J. Murchie; Aaron D. Shultz; Jeffrey A. Stein; Steven J. Cooke; Justin Lewis; Jason Franklin; Greg Vincent; Edward J. Brooks; Julie E. Claussen; David P. Philipp (Environmental Biology of Fishes, 2015)

Cardiorespiratory fitness is associated with brain structure, cognition, and mood in a middle-aged cohort at risk for Alzheimer’s disease - Elizabeth A. Boots; Stephanie A. Schultz; Jennifer M. Oh; Jordan Larson; Dorothy Edwards; Dane Cook; Rebecca L. Koscik; Maritza N. Dowling; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; et al. (Brain Imaging and Behavior, 2015)

Inter-comparison of the potentially active prokaryotic communities in the halocline sediments of Mediterranean deep-sea hypersaline basins - Konstantinos A. Kormas; Maria G. Pachiadaki; Hera Karayanni; Edward R. Leadbetter; Joan M. Bernhard; Virginia P. Edgcomb (Extremophiles, 2015)

Would protecting tropical forest fragments provide carbon and biodiversity cobenefits under REDD +? - Luiz Fernando S. Magnago; Ainhoa Magrach; William F. Laurance; Sebastião V. Martins; João Augusto A. Meira‐Neto; Marcelo Simonelli; David P. Edwards (Global Change Biology, 2015)
Tropical forests store vast amounts of carbon and are the most biodiverse terrestrial habitats, yet they are being converted and degraded at alarming rates. Given global shortfalls in the budgets required to prevent carbon and biodiversity loss, we need to seek solutions that simultaneously address both issues. Of particular interest are carbon‐based payments under the Reducing Emissions from Deforestation and Forest Degradation ( REDD +) mechanism to also conserve biodiversity at no additional cost. One potential is for REDD + to protect forest fragments, especially within biomes where contiguous forest cover has diminished dramatically, but we require empirical tests of the strength of any carbon and biodiversity cobenefits in such fragmented systems. Using the globally threatened Atlantic Forest landscape, we measured above‐ground carbon stocks within forest fragments spanning 13 to 23 442 ha in area and with different degrees of isolation. We related these stocks to tree community structure and to the richness and abundance of endemic and IUCN Red‐listed species. We found that increasing fragment size has a positive relationship with above‐ground carbon stock and with abundance of IUCN Red‐listed species and tree community structure. We also found negative relationships between distance from large forest block and tree community structure, endemic species richness and abundance, and IUCN Red‐listed species abundance. These resulted in positive congruence between carbon stocks and Red‐listed species, and the abundance and richness of endemic species, demonstrating vital cobenefits. As such, protecting forest fragments in hotspots of biodiversity, particularly larger fragments and those closest to sources, offers important carbon and biodiversity cobenefits. More generally, our results suggest that macroscale models of cobenefits under REDD + have likely overlooked key benefits at small scales, indicating the necessity to apply models that include finer‐grained assessments in fragmented landscapes rather than using averaged coarse‐grained cells.

Hydrology under change: an evaluation protocol to investigate how hydrological models deal with changing catchments - G. Thirel; V. Andréassian; C. Perrin; J.-N. Audouy; L. Berthet; P. Edwards; N. Folton; C. Furusho; A. Kuentz; J. Lerat; G. Lindström; E. Martin; et al. (Hydrological Sciences Journal, 2015)

Monthly Water Balance of an Iconic Coastal Desert Wetland Under Reduced Flows and Increased Salinities; Implications for Management - Marcelo A. Lomeli; Jorge Ramírez-Hernández; Edward P. Glenn; Francisco Zamora-Arroyo; Karl W. Flessa (Wetlands, 2015)

A pan‐Arctic synthesis of CH 4 and CO 2 production from anoxic soil incubations - Claire C. Treat; Susan M. Natali; Jessica Ernakovich; Colleen M. Iversen; Massimo Lupascu; Anthony David McGuire; Richard J. Norby; Taniya Roy Chowdhury; Andreas Richter; Hana Šantrůčková; Christina Schädel; Edward A. G. Schuur; et al. (Global Change Biology, 2015)
Permafrost thaw can alter the soil environment through changes in soil moisture, frequently resulting in soil saturation, a shift to anaerobic decomposition, and changes in the plant community. These changes, along with thawing of previously frozen organic material, can alter the form and magnitude of greenhouse gas production from permafrost ecosystems. We synthesized existing methane (CH 4 ) and carbon dioxide (CO 2 ) production measurements from anaerobic incubations of boreal and tundra soils from the geographic permafrost region to evaluate large‐scale controls of anaerobic CO 2 and CH 4 production and compare the relative importance of landscape‐level factors (e.g., vegetation type and landscape position), soil properties (e.g., pH, depth, and soil type), and soil environmental conditions (e.g., temperature and relative water table position). We found fivefold higher maximum CH 4 production per gram soil carbon from organic soils than mineral soils. Maximum CH 4 production from soils in the active layer (ground that thaws and refreezes annually) was nearly four times that of permafrost per gram soil carbon, and CH 4 production per gram soil carbon was two times greater from sites without permafrost than sites with permafrost. Maximum CH 4 and median anaerobic CO 2 production decreased with depth, while CO 2 :CH 4 production increased with depth. Maximum CH 4 production was highest in soils with herbaceous vegetation and soils that were either consistently or periodically inundated. This synthesis identifies the need to consider biome, landscape position, and vascular/moss vegetation types when modeling CH 4 production in permafrost ecosystems and suggests the need for longer‐term anaerobic incubations to fully capture CH 4 dynamics. Our results demonstrate that as climate warms in arctic and boreal regions, rates of anaerobic CO 2 and CH 4 production will increase, not only as a result of increased temperature, but also from shifts in vegetation and increased ground saturation that will accompany permafrost thaw.

An ant–plant by-product mutualism is robust to selective logging of rain forest and conversion to oil palm plantation - Tom M. Fayle; David P. Edwards; William A. Foster; Kalsum M. Yusah; Edgar C. Turner (Oecologia, 2015)

Females Exceed Males in Mercury Concentrations of Burbot Lota lota - Charles P. Madenjian; Martin A. Stapanian; Peter A. Cott; David P. Krabbenhoft; William H. Edwards; Lynn M. Ogilvie; Justin G. Mychek-Londer; John F. DeWild (Archives of Environmental Contamination and Toxicology, 2015)

Rhizosphere processes are quantitatively important components of terrestrial carbon and nutrient cycles - Adrien C. Finzi; Rose Z. Abramoff; Kimberly S. Spiller; Edward R. Brzostek; Bridget A. Darby; Mark A. Kramer; Richard P. Phillips (Global Change Biology, 2015)
While there is an emerging view that roots and their associated microbes actively alter resource availability and soil organic matter ( SOM ) decomposition, the ecosystem consequences of such rhizosphere effects have rarely been quantified. Using a meta‐analysis, we show that multiple indices of microbially mediated C and nitrogen (N) cycling, including SOM decomposition, are significantly enhanced in the rhizospheres of diverse vegetation types. Then, using a numerical model that combines rhizosphere effect sizes with fine root morphology and depth distributions, we show that root‐accelerated mineralization and priming can account for up to one‐third of the total C and N mineralized in temperate forest soils. Finally, using a stoichiometrically constrained microbial decomposition model, we show that these effects can be induced by relatively modest fluxes of root‐derived C, on the order of 4% and 6% of gross and net primary production, respectively. Collectively, our results indicate that rhizosphere processes are a widespread, quantitatively important driver of SOM decomposition and nutrient release at the ecosystem scale, with potential consequences for global C stocks and vegetation feedbacks to climate.

Small Amounts of Sub-Visible Aggregates Enhance the Immunogenic Potential of Monoclonal Antibody Therapeutics - Maryam Ahmadi; Christine J. Bryson; Edward A. Cloake; Katie Welch; Vasco Filipe; Stefan Romeijn; Andrea Hawe; Wim Jiskoot; Matthew P. Baker; Mark H. Fogg (Pharmaceutical Research, 2015)

Comparative analysis of the complete genome sequences of Kenyan African swine fever virus isolates within p72 genotypes IX and X - Richard P. Bishop; Clare Fleischauer; Etienne P. de Villiers; Edward A. Okoth; Marisa Arias; Carmina Gallardo; Chris Upton (Virus Genes, 2015)

Minimizing the biodiversity impact of Neotropical oil palm development - James J. Gilroy; Graham W. Prescott; Johann S. Cardenas; Pamela González del Pliego Castañeda; Andrés Sánchez; Luis E. Rojas‐Murcia; Claudia A. Medina Uribe; Torbjørn Haugaasen; David P. Edwards (Global Change Biology, 2015)
Oil palm agriculture is rapidly expanding in the Neotropics, at the expense of a range of natural and seminatural habitats. A key question is how this expansion should be managed to reduce negative impacts on biodiversity. Focusing on the Llanos of Colombia, a mixed grassland–forest system identified as a priority zone for future oil palm development, we survey communities of ants, dung beetles, birds and herpetofauna occurring in oil palm plantations and the other principal form of agriculture in the region – improved cattle pasture – together with those of surrounding natural forests. We show that oil palm plantations have similar or higher species richness across all four taxonomic groups than improved pasture. For dung beetles, species richness in oil palm was equal to that of forest, whereas the other three taxa had highest species richness in forests. Hierarchical modelling of species occupancy probabilities indicated that oil palm plantations supported a higher proportion of species characteristic of forests than did cattle pastures. Across the bird community, occupancy probabilities within oil palm were positively influenced by increasing forest cover in a surrounding 250 m radius, whereas surrounding forest cover did not strongly influence the occurrence of other taxonomic groups in oil palm. Overall, our results suggest that the conversion of existing improved pastures to oil palm has limited negative impacts on biodiversity. As such, existing cattle pastures of the Colombian Llanos could offer a key opportunity to meet governmental targets for oil palm development without incurring significant biodiversity costs. Our results also highlight the value of preserving remnant forests within these agricultural landscapes, protecting high biodiversity and exporting avian ‘spill‐over’ effects into oil palm plantations.

Effect of scale on trait predictors of species responses to agriculture - James J. Gilroy; Claudia A. Medina Uribe; Torbjørn Haugaasen; David P. Edwards (Conservation Biology, 2015)
Species persistence in human‐altered landscapes can depend on factors operating at multiple spatial scales. To understand anthropogenic impacts on biodiversity, it is useful to examine relationships between species traits and their responses to land‐use change. A key knowledge gap concerns whether these relationships vary depending on the scale of response under consideration. We examined how local‐ and large‐scale habitat variables influence the occupancy dynamics of a bird community in cloud forest zones in the Colombian Chocó‐Andes. Using data collected across a continuum of forest and agriculture, we examined which traits best predict species responses to local variation in farmland and which traits best predict species responses to isolation from contiguous forest. Global range size was a strong predictor of species responses to agriculture at both scales; widespread species were less likely to decline as local habitat cover decreased and as distance from forest increased. Habitat specialization was a strong predictor of species responses only at the local scale. Open‐habitat species were particularly likely to increase as pasture increased, but they were relatively insensitive to variation in distance to forest. Foraging plasticity and flocking behavior were strong predictors of species responses to distance from forest, but not their responses to local habitat. Species with lower plasticity in foraging behaviors and obligate flock‐following species were more likely to decline as distance from contiguous forest increased. For species exhibiting these latter traits, persistence in tropical landscapes may depend on the protection of larger contiguous blocks of forest, rather than the integration of smaller‐scale woodland areas within farmland. Species listed as threatened or near threatened on the International Union for Conservation of Nature Red List were also more likely to decline in response to both local habitat quality and isolation from forest relative to least‐concern species, underlining the importance of contiguous forests for threatened taxa.

Bacteria or melanosomes? A geochemical analysis of micro-bodies on a tadpole from the Oligocene Enspel Formation of Germany - Holly E. Barden; Uwe Bergmann; Nicholas P. Edwards; Victoria M. Egerton; Phillip L. Manning; Sarah Perry; Arjen van Veelen; Roy A. Wogelius; Bart E. van Dongen (Palaeobiodiversity and Palaeoenvironments, 2015)

Gene loss in the fungal canola pathogen Leptosphaeria maculans - Agnieszka A. Golicz; Paula A. Martinez; Manuel Zander; Dhwani A. Patel; Angela P. Van De Wouw; Paul Visendi; Timothy L. Fitzgerald; David Edwards; Jacqueline Batley (Functional & Integrative Genomics, 2015)

Worldwide phylogeography of the invasive ctenophore Mnemiopsis leidyi (Ctenophora) based on nuclear and mitochondrial DNA data - K. M. Bayha; M. H. Chang; C. L. Mariani; J. L. Richardson; D. L. Edwards; T. S. DeBoer; C. Moseley; E. Aksoy; M. B. Decker; P. M. Gaffney; G. R. Harbison; J. H. McDonald; et al. (Biological Invasions, 2015)

Decadal environmental ‘memory’ in a reef coral? - B. E. Brown; R. P. Dunne; A. J. Edwards; M. J. Sweet; N. Phongsuwan (Marine Biology, 2015)

Risks of large-scale use of systemic insecticides to ecosystem functioning and services - Madeleine Chagnon; David Kreutzweiser; Edward A.D. Mitchell; Christy A. Morrissey; Dominique A. Noome; Jeroen P. Van der Sluijs (Environmental Science and Pollution Research, 2015)

Operationalizing resilience for adaptive coral reef management under global environmental change - Kenneth R.N. Anthony; Paul A. Marshall; Ameer Abdulla; Roger Beeden; Chris Bergh; Ryan Black; C. Mark Eakin; Edward T. Game; Margaret Gooch; Nicholas A.J. Graham; Alison Green; Scott F. Heron; et al. (Global Change Biology, 2015)
Cumulative pressures from global climate and ocean change combined with multiple regional and local‐scale stressors pose fundamental challenges to coral reef managers worldwide. Understanding how cumulative stressors affect coral reef vulnerability is critical for successful reef conservation now and in the future. In this review, we present the case that strategically managing for increased ecological resilience (capacity for stress resistance and recovery) can reduce coral reef vulnerability (risk of net decline) up to a point. Specifically, we propose an operational framework for identifying effective management levers to enhance resilience and support management decisions that reduce reef vulnerability. Building on a system understanding of biological and ecological processes that drive resilience of coral reefs in different environmental and socio‐economic settings, we present an Adaptive Resilience‐Based management ( ARBM ) framework and suggest a set of guidelines for how and where resilience can be enhanced via management interventions. We argue that press‐type stressors (pollution, sedimentation, overfishing, ocean warming and acidification) are key threats to coral reef resilience by affecting processes underpinning resistance and recovery, while pulse‐type (acute) stressors (e.g. storms, bleaching events, crown‐of‐thorns starfish outbreaks) increase the demand for resilience. We apply the framework to a set of example problems for Caribbean and Indo‐Pacific reefs. A combined strategy of active risk reduction and resilience support is needed, informed by key management objectives, knowledge of reef ecosystem processes and consideration of environmental and social drivers. As climate change and ocean acidification erode the resilience and increase the vulnerability of coral reefs globally, successful adaptive management of coral reefs will become increasingly difficult. Given limited resources, on‐the‐ground solutions are likely to focus increasingly on actions that support resilience at finer spatial scales, and that are tightly linked to ecosystem goods and services.

Fire in Australian savannas: from leaf to landscape - Jason Beringer; Lindsay B. Hutley; David Abramson; Stefan K. Arndt; Peter Briggs; Mila Bristow; Josep G. Canadell; Lucas A. Cernusak; Derek Eamus; Andrew C. Edwards; Bradley J. Evans; Benedikt Fest; et al. (Global Change Biology, 2015)
Savanna ecosystems comprise 22% of the global terrestrial surface and 25% of Australia (almost 1.9 million km 2 ) and provide significant ecosystem services through carbon and water cycles and the maintenance of biodiversity. The current structure, composition and distribution of Australian savannas have coevolved with fire, yet remain driven by the dynamic constraints of their bioclimatic niche. Fire in Australian savannas influences both the biophysical and biogeochemical processes at multiple scales from leaf to landscape. Here, we present the latest emission estimates from Australian savanna biomass burning and their contribution to global greenhouse gas budgets. We then review our understanding of the impacts of fire on ecosystem function and local surface water and heat balances, which in turn influence regional climate. We show how savanna fires are coupled to the global climate through the carbon cycle and fire regimes. We present new research that climate change is likely to alter the structure and function of savannas through shifts in moisture availability and increases in atmospheric carbon dioxide, in turn altering fire regimes with further feedbacks to climate. We explore opportunities to reduce net greenhouse gas emissions from savanna ecosystems through changes in savanna fire management.

Lineage fusion in G alápagos giant tortoises - Ryan C. Garrick; Edgar Benavides; Michael A. Russello; Chaz Hyseni; Danielle L. Edwards; James P. Gibbs; Washington Tapia; Claudio Ciofi; Adalgisa Caccone (Molecular Ecology, 2014)
Although many classic radiations on islands are thought to be the result of repeated lineage splitting, the role of past fusion is rarely known because during these events, purebreds are rapidly replaced by a swarm of admixed individuals. Here, we capture lineage fusion in action in a Galápagos giant tortoise species, Chelonoidis becki , from Wolf Volcano (Isabela Island). The long generation time of Galápagos tortoises and dense sampling (841 individuals) of genetic and demographic data were integral in detecting and characterizing this phenomenon. In C. becki, we identified two genetically distinct, morphologically cryptic lineages. Historical reconstructions show that they colonized Wolf Volcano from Santiago Island in two temporally separated events, the first estimated to have occurred ~199 000 years ago. Following arrival of the second wave of colonists, both lineages coexisted for approximately ~53 000 years. Within that time, they began fusing back together, as microsatellite data reveal widespread introgressive hybridization. Interestingly, greater mate selectivity seems to be exhibited by purebred females of one of the lineages. Forward‐in‐time simulations predict rapid extinction of the early arriving lineage. This study provides a rare example of reticulate evolution in action and underscores the power of population genetics for understanding the past, present and future consequences of evolutionary phenomena associated with lineage fusion.

Normal Motor Adaptation in Cervical Dystonia: A Fundamental Cerebellar Computation is Intact - Anna Sadnicka; Bansi Patani; Tabish A. Saifee; Panagiotis Kassavetis; Isabel Pareés; Prasad Korlipara; Kailash P. Bhatia; John C. Rothwell; Joseph M. Galea; Mark J. Edwards (The Cerebellum, 2014)

A reconstruction of extratropical Indo-Pacific sea-level pressure patterns during the Medieval Climate Anomaly - Ian D. Goodwin; Stuart Browning; Andrew M. Lorrey; Paul A. Mayewski; Steven J. Phipps; Nancy A. N. Bertler; Ross P. Edwards; Tim J. Cohen; Tas van Ommen; Mark Curran; Cameron Barr; J. Curt Stager (Climate Dynamics, 2014)

An improved approach for remotely sensing water stress impacts on forest C uptake - Daniel A. Sims; Edward R. Brzostek; Abdullah F. Rahman; Danilo Dragoni; Richard P. Phillips (Global Change Biology, 2014)
Given that forests represent the primary terrestrial sink for atmospheric CO 2 , projections of future carbon (C) storage hinge on forest responses to climate variation. Models of gross primary production ( GPP ) responses to water stress are commonly based on remotely sensed changes in canopy ‘greenness’ (e.g., normalized difference vegetation index; NDVI ). However, many forests have low spectral sensitivity to water stress ( SSWS ) – defined here as drought‐induced decline in GPP without a change in greenness. Current satellite‐derived estimates of GPP use a vapor pressure deficit ( VPD ) scalar to account for the low SWSS of forests, but fail to capture their responses to water stress. Our objectives were to characterize differences in SSWS among forested and nonforested ecosystems, and to develop an improved framework for predicting the impacts of water stress on GPP in forests with low SSWS . First, we paired two independent drought indices with NDVI data for the conterminous US from 2000 to 2011, and examined the relationship between water stress and NDVI . We found that forests had lower SSWS than nonforests regardless of drought index or duration. We then compared satellite‐derived estimates of GPP with eddy‐covariance observations of GPP in two deciduous broadleaf forests with low SSWS : the Missouri Ozark ( MO ) and Morgan Monroe State Forest ( MMSF ) AmeriFlux sites. Model estimates of GPP that used VPD scalars were poorly correlated with observations of GPP at MO ( r 2 = 0.09) and MMSF ( r 2 = 0.38). When we included the NDVI responses to water stress of adjacent ecosystems with high SSWS into a model based solely on temperature and greenness, we substantially improved predictions of GPP at MO ( r 2 = 0.83) and for a severe drought year at the MMSF ( r 2 = 0.82). Collectively, our results suggest that large‐scale estimates of GPP that capture variation in SSWS among ecosystems could improve predictions of C uptake by forests under drought.

Ecosystem-Scale Rates of Primary Production Within Wetland Habitats of the Northern San Francisco Estuary - Risa A. Cohen; Frances P. Wilkerson; Alexander E. Parker; Edward J. Carpenter (Wetlands, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Chronic water stress reduces tree growth and the carbon sink of deciduous hardwood forests - Edward R. Brzostek; Danilo Dragoni; Hans Peter Schmid; Abdullah F. Rahman; Daniel Sims; Craig A. Wayson; Daniel J. Johnson; Richard P. Phillips (Global Change Biology, 2014)
Predicted decreases in water availability across the temperate forest biome have the potential to offset gains in carbon (C) uptake from phenology trends, rising atmospheric CO 2 , and nitrogen deposition. While it is well established that severe droughts reduce the C sink of forests by inducing tree mortality, the impacts of mild but chronic water stress on forest phenology and physiology are largely unknown. We quantified the C consequences of chronic water stress using a 13‐year record of tree growth ( n = 200 trees), soil moisture, and ecosystem C balance at the Morgan–Monroe State Forest ( MMSF ) in Indiana, and a regional 11‐year record of tree growth ( n > 300 000 trees) and water availability for the 20 most dominant deciduous broadleaf tree species across the eastern and midwestern USA . We show that despite ~26 more days of C assimilation by trees at the MMSF , increasing water stress decreased the number of days of wood production by ~42 days over the same period, reducing the annual accrual of C in woody biomass by 41%. Across the deciduous forest region, water stress induced similar declines in tree growth, particularly for water‐demanding ‘mesophytic’ tree species. Given the current replacement of water‐stress adapted ‘xerophytic’ tree species by mesophytic tree species, we estimate that chronic water stress has the potential to decrease the C sink of deciduous forests by up to 17% (0.04 Pg C yr −1 ) in the coming decades. This reduction in the C sink due to mesophication and chronic water stress is equivalent to an additional 1–3 days of global C emissions from fossil fuel burning each year. Collectively, our results indicate that regional declines in water availability may offset the growth‐enhancing effects of other global changes and reduce the extent to which forests ameliorate climate warming.

Optimizing carbon storage and biodiversity protection in tropical agricultural landscapes - James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Charlotte Wheeler; Claudia A. Medina Uribe; Torbjørn Haugaasen; David P. Edwards (Global Change Biology, 2014)
With the rapidly expanding ecological footprint of agriculture, the design of farmed landscapes will play an increasingly important role for both carbon storage and biodiversity protection. Carbon and biodiversity can be enhanced by integrating natural habitats into agricultural lands, but a key question is whether benefits are maximized by including many small features throughout the landscape (‘land‐sharing’ agriculture) or a few large contiguous blocks alongside intensive farmland (‘land‐sparing’ agriculture). In this study, we are the first to integrate carbon storage alongside multi‐taxa biodiversity assessments to compare land‐sparing and land‐sharing frameworks. We do so by sampling carbon stocks and biodiversity (birds and dung beetles) in landscapes containing agriculture and forest within the Colombian Chocó‐Andes, a zone of high global conservation priority. We show that woodland fragments embedded within a matrix of cattle pasture hold less carbon per unit area than contiguous primary or advanced secondary forests (>15 years). Farmland sites also support less diverse bird and dung beetle communities than contiguous forests, even when farmland retains high levels of woodland habitat cover. Landscape simulations based on these data suggest that land‐sparing strategies would be more beneficial for both carbon storage and biodiversity than land‐sharing strategies across a range of production levels. Biodiversity benefits of land‐sparing are predicted to be similar whether spared lands protect primary or advanced secondary forests, owing to the close similarity of bird and dung beetle communities between the two forest classes. Land‐sparing schemes that encourage the protection and regeneration of natural forest blocks thus provide a synergy between carbon and biodiversity conservation, and represent a promising strategy for reducing the negative impacts of agriculture on tropical ecosystems. However, further studies examining a wider range of ecosystem services will be necessary to fully understand the links between land‐allocation strategies and long‐term ecosystem service provision.

Erratum to: A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Non-invasive Cerebellar Stimulation—a Consensus Paper - G. Grimaldi; G. P. Argyropoulos; A. Boehringer; P. Celnik; M. J. Edwards; R. Ferrucci; J. M. Galea; S. J. Groiss; K. Hiraoka; P. Kassavetis; E. Lesage; M. Manto; et al. (The Cerebellum, 2014)

Improving the science-policy dialogue to meet the challenges of biodiversity conservation: having conversations rather than talking at one-another - Juliette C. Young; Kerry A. Waylen; Simo Sarkki; Steve Albon; Ian Bainbridge; Estelle Balian; James Davidson; David Edwards; Roddy Fairley; Ceri Margerison; Davy McCracken; Roger Owen; et al. (Biodiversity and Conservation, 2014)

Microhabitats reduce animal's exposure to climate extremes - Brett R. Scheffers; David P. Edwards; Arvin Diesmos; Stephen E. Williams; Theodore A. Evans (Global Change Biology, 2014)
Extreme weather events, such as unusually hot or dry conditions, can cause death by exceeding physiological limits, and so cause loss of population. Survival will depend on whether or not susceptible organisms can find refuges that buffer extreme conditions. Microhabitats offer different microclimates to those found within the wider ecosystem, but do these microhabitats effectively buffer extreme climate events relative to the physiological requirements of the animals that frequent them? We collected temperature data from four common microhabitats (soil, tree holes, epiphytes, and vegetation) located from the ground to canopy in primary rainforests in the Philippines. Ambient temperatures were monitored from outside of each microhabitat and from the upper forest canopy, which represent our macrohabitat controls. We measured the critical thermal maxima ( CT max ) of frog and lizard species, which are thermally sensitive and inhabit our microhabitats. Microhabitats reduced mean temperature by 1–2 °C and reduced the duration of extreme temperature exposure by 14–31 times. Microhabitat temperatures were below the CT max of inhabitant frogs and lizards, whereas macrohabitats consistently contained lethal temperatures. Microhabitat temperatures increased by 0.11–0.66 °C for every 1 °C increase in macrohabitat temperature, and this nonuniformity in temperature change influenced our forecasts of vulnerability for animal communities under climate change. Assuming uniform increases of 6 °C, microhabitats decreased the vulnerability of communities by up to 32‐fold, whereas under nonuniform increases of 0.66 to 3.96 °C, microhabitats decreased the vulnerability of communities by up to 108‐fold. Microhabitats have extraordinary potential to buffer climate and likely reduce mortality during extreme climate events. These results suggest that predicted changes in distribution due to mortality and habitat shifts that are derived from macroclimatic samples and that assume uniform changes in microclimates relative to macroclimates may be overly pessimistic. Nevertheless, even nonuniform temperature increases within buffered microhabitats would still threaten frogs and lizards.

Land‐sharing versus land‐sparing logging: reconciling timber extraction with biodiversity conservation - David P. Edwards; James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; David J. R. Andrews; Mia A. Derhé; Teegan D. S. Docherty; Wayne W. Hsu; Simon L. Mitchell; Takahiro Ota; Leah J. Williams; et al. (Global Change Biology, 2014)
Selective logging is a major driver of rainforest degradation across the tropics. Two competing logging strategies are proposed to meet timber demands with the least impact on biodiversity: land sharing, which combines timber extraction with biodiversity protection across the concession; and land sparing, in which higher intensity logging is combined with the protection of intact primary forest reserves. We evaluate these strategies by comparing the abundances and species richness of birds, dung beetles and ants in Borneo, using a protocol that allows us to control for both timber yield and net profit across strategies. Within each taxonomic group, more species had higher abundances with land‐sparing than land‐sharing logging, and this translated into significantly higher species richness within land‐sparing concessions. Our results are similar when focusing only on species found in primary forest and restricted in range to Sundaland, and they are independent of the scale of sampling. For each taxonomic group, land‐sparing logging was the most promising strategy for maximizing the biological value of logging operations.

Modeled diversity effects on microbial ecosystem functions of primary production, nutrient uptake, and remineralization - Nicole L. Goebel; Christopher A. Edwards; Michael J. Follows; Jonathan P. Zehr (Ecology, 2014)
Ecosystem‐wide primary productivity generally increases with primary producer diversity, emphasizing the importance of diversity for ecosystem function. However, most studies that demonstrate this positive relationship have focused on terrestrial and aquatic benthic systems, with little attention to the diverse marine pelagic primary producers that play an important role in regulating global climate. Here we show how phytoplankton biodiversity enhances overall marine ecosystem primary productivity and other ecosystem functions using a self‐organizing ecosystem model. Diversity manipulation numerical experiments reveal positive, asymptotically saturating relationships between ecosystem‐wide phytoplankton diversity and functions of productivity, nutrient uptake, remineralization, and diversity metrics used to identify mechanisms shaping these relationships. Increase in productivity with increasing diversity improves modeled ecosystem stability and model robustness and leads to productivity rates that exceed expected yields primarily through niche complementarity and facilitative interactions between coexisting phytoplankton types; the composition of traits in assemblages determines the magnitude of complementarity and selection effects. While findings based on these aggregate measures of diversity effects parallel those from the majority of experimental outcomes of terrestrial and benthic biodiversity–ecosystem function studies, we combine analyses of community diversity effects and investigations of the underlying interactions among phytoplankton types to demonstrate how an increase in recycled production of non‐diatoms through an increase in new production of diatoms drives this diversity–ecosystem function response. We demonstrate the important role that facilitation plays in the modeled marine plankton and how this facilitative interaction could amplify future climate‐driven changes in ocean ecosystem productivity.

Developing logistic models to relate the accumulation of DON associated with Fusarium head blight to climatic conditions in Europe - Xiangming Xu; Laurence V. Madden; Simon G. Edwards; Fiona M. Doohan; Antonio Moretti; L. Hornok; P. Nicholson; A. Ritieni (European Journal of Plant Pathology, 2013)

Nuclear double-fluorescent reporter for in vivo and ex vivo analyses of biological transitions in mouse nuclei - Justin R. Prigge; James A. Wiley; Emily A. Talago; Elise M. Young; Laura L. Johns; Jean A. Kundert; Katherine M. Sonsteng; William P. Halford; Mario R. Capecchi; Edward E. Schmidt (Mammalian Genome, 2013)

Reliable, verifiable and efficient monitoring of biodiversity via metabarcoding - Yinqiu Ji; Louise Ashton; Scott M. Pedley; David P. Edwards; Yong Tang; Akihiro Nakamura; Roger Kitching; Paul M. Dolman; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; Wayne W. Hsu; et al. (Ecology Letters, 2013)
To manage and conserve biodiversity, one must know what is being lost, where, and why, as well as which remedies are likely to be most effective. Metabarcoding technology can characterise the species compositions of mass samples of eukaryotes or of environmental DNA . Here, we validate metabarcoding by testing it against three high‐quality standard data sets that were collected in Malaysia (tropical), China (subtropical) and the United Kingdom (temperate) and that comprised 55,813 arthropod and bird specimens identified to species level with the expenditure of 2,505 person‐hours of taxonomic expertise. The metabarcode and standard data sets exhibit statistically correlated alpha‐ and beta‐diversities, and the two data sets produce similar policy conclusions for two conservation applications: restoration ecology and systematic conservation planning. Compared with standard biodiversity data sets, metabarcoded samples are taxonomically more comprehensive, many times quicker to produce, less reliant on taxonomic expertise and auditable by third parties, which is essential for dispute resolution.

Trophic Flexibility and the Persistence of Understory Birds in Intensively Logged Rainforest - DAVID P. EDWARDS; PAUL WOODCOCK; ROB J. NEWTON; FELICITY A. EDWARDS; DAVID J. R. ANDREWS; TEEGAN D. S. DOCHERTY; SIMON L. MITCHELL; TAKAHIRO OTA; SUZAN BENEDICK; SIMON H. BOTTRELL; KEITH C. HAMER (Conservation Biology, 2013)
Effects of logging on species composition in tropical rainforests are well known but may fail to reveal key changes in species interactions. We used nitrogen stable‐isotope analysis of 73 species of understory birds to quantify trophic responses to repeated intensive logging of rainforest in northern Borneo and to test 4 hypotheses: logging has significant effects on trophic positions and trophic‐niche widths of species, and the persistence of species in degraded forest is related to their trophic positions and trophic‐niche widths in primary forest. Species fed from higher up the food chain and had narrower trophic‐niche widths in degraded forest. Species with narrow trophic‐niche widths in primary forest were less likely to persist after logging, a result that indicates a higher vulnerability of dietary specialists to local extinction following habitat disturbance. Persistence of species in degraded forest was not related to a species’ trophic position. These results indicate changes in trophic organization that were not apparent from changes in species composition and highlight the importance of focusing on trophic flexibility over the prevailing emphasis on membership of static feeding guilds. Our results thus support the notion that alterations to trophic organization and interactions within tropical forests may be a pervasive and functionally important hidden effect of forest degradation. Flexibilidad Trófica y la Persistencia de Aves de Sotobosque en un Bosque Lluvioso Talado Intensivamente

A de novo FLCN mutation in a patient with spontaneous pneumothorax and renal cancer; a clinical and molecular evaluation - Fred H. Menko; Paul C. Johannesma; R. Jeroen A. van Moorselaar; Rinze Reinhard; Jan Hein van Waesberghe; Erik Thunnissen; Arjan C. Houweling; Edward M. Leter; Quinten Waisfisz; Martijn B. van Doorn; Theo M. Starink; Pieter E. Postmus; et al. (Familial Cancer, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Neuron-Specific Expression of Tomosyn1 in the Mouse Hippocampal Dentate Gyrus Impairs Spatial Learning and Memory - Boaz Barak; Eitan Okun; Yoav Ben-Simon; Ayal Lavi; Ronit Shapira; Ravit Madar; Yue Wang; Eric Norman; Anton Sheinin; Mario A. Pita; Ofer Yizhar; Mohamed R. Mughal; et al. (NeuroMolecular Medicine, 2013)

Genetic characterization and mapping of the Rht-1 homoeologs and flanking sequences in wheat - Edward P. Wilhelm; Rhian M. Howells; Nadia Al-Kaff; Jizeng Jia; Catherine Baker; Michelle A. Leverington-Waite; Simon Griffiths; Andy J. Greenland; Margaret I. Boulton; Wayne Powell (Theoretical and Applied Genetics, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Microevolution in time and space: SNP analysis of historical DNA reveals dynamic signatures of selection in A tlantic cod - Nina O. Therkildsen; Jakob Hemmer‐Hansen; Thomas D. Als; Douglas P. Swain; M. Joanne Morgan; Edward A. Trippel; Stephen R. Palumbi; Dorte Meldrup; Einar E. Nielsen (Molecular Ecology, 2013)
Little is known about how quickly natural populations adapt to changes in their environment and how temporal and spatial variation in selection pressures interact to shape patterns of genetic diversity. We here address these issues with a series of genome scans in four overfished populations of Atlantic cod ( G adus morhua ) studied over an 80‐year period. Screening of >1000 gene‐associated single‐nucleotide polymorphisms ( SNP s) identified 77 loci that showed highly elevated levels of differentiation, likely as an effect of directional selection, in either time, space or both. Exploratory analysis suggested that temporal allele frequency shifts at certain loci may correlate with local temperature variation and with life history changes suggested to be fisheries induced. Interestingly, however, largely nonoverlapping sets of loci were temporal outliers in the different populations and outliers from the 1928 to 1960 period showed almost complete stability during later decades. The contrasting microevolutionary trajectories among populations resulted in sequential shifts in spatial outliers, with no locus maintaining elevated spatial differentiation throughout the study period. Simulations of migration coupled with observations of temporally stable spatial structure at neutral loci suggest that population replacement or gene flow alone could not explain all the observed allele frequency variation. Thus, the genetic changes are likely to at least partly be driven by highly dynamic temporally and spatially varying selection. These findings have important implications for our understanding of local adaptation and evolutionary potential in high gene flow organisms and underscore the need to carefully consider all dimensions of biocomplexity for evolutionarily sustainable management.

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Building the niche through time: using 13,000 years of data to predict the effects of climate change on three tree species in Europe - L. Maiorano; R. Cheddadi; N. E. Zimmermann; L. Pellissier; B. Petitpierre; J. Pottier; H. Laborde; B. I. Hurdu; P. B. Pearman; A. Psomas; J. S. Singarayer; O. Broennimann; et al. (Global Ecology and Biogeography, 2013)
Aim Species distribution models (SDMs) based on current species ranges underestimate the potential distribution when projected in time and/or space. A multi‐temporal model calibration approach has been suggested as an alternative, and we evaluate this using 13,000 years of data. Location Europe. Methods We used fossil‐based records of presence for Picea abies , Abies alba and Fagus sylvatica and six climatic variables for the period 13,000 to 1000 yr bp . To measure the contribution of each 1000‐year time step to the total niche of each species (the niche measured by pooling all the data), we employed a principal components analysis (PCA) calibrated with data over the entire range of possible climates. Then we projected both the total niche and the partial niches from single time frames into the PCA space, and tested if the partial niches were more similar to the total niche than random. Using an ensemble forecasting approach, we calibrated SDMs for each time frame and for the pooled database. We projected each model to current climate and evaluated the results against current pollen data. We also projected all models into the future. Results Niche similarity between the partial and the total‐SDMs was almost always statistically significant and increased through time. SDMs calibrated from single time frames gave different results when projected to current climate, providing evidence of a change in the species realized niches through time. Moreover, they predicted limited climate suitability when compared with the total‐SDMs. The same results were obtained when projected to future climates. Main conclusions The realized climatic niche of species differed for current and future climates when SDMs were calibrated considering different past climates. Building the niche as an ensemble through time represents a way forward to a better understanding of a species' range and its ecology in a changing climate.

Long-term development of a cultural landscape: the origins and dynamics of lowland heathland in southern England - Jon A. Groves; Martyn P. Waller; Michael J. Grant; J. Edward Schofield (Vegetation History and Archaeobotany, 2012)

Oxidative stress induced by potassium bromate exposure results in altered tight junction protein expression in renal proximal tubule cells - Alice Limonciel; Anja Wilmes; Lydia Aschauer; Robert Radford; Katarzyna M. Bloch; Tara McMorrow; Walter Pfaller; Joost H. van Delft; Craig Slattery; Michael P. Ryan; Edward A. Lock; Paul Jennings (Archives of Toxicology, 2012)

Adaptation of surround inhibition in the human motor system - P. Kassavetis; T. A. Saifee; A. Sadnicka; I. Pareés; M. Kojovic; J. C. Rothwell; M. J. Edwards (Experimental Brain Research, 2012)

Assimilating GlobColour ocean colour data into a pre-operational physical-biogeochemical model - D. A. Ford; K. P. Edwards; D. Lea; R. M. Barciela; M. J. Martin; J. Demaria (Ocean Science, 2012)
As part of the GlobColour project, daily chlorophyll a observations, derived using remotely sensed ocean colour data from the MERIS, MODIS and SeaWiFS sensors, are produced. The ability of these products to be assimilated into a pre-operational global coupled physical-biogeochemical model has been tested, on both a hindcast and near-real-time basis, and the impact on the system assessed. The assimilation was found to immediately and considerably improve the bias, root mean square error and correlation of modelled surface chlorophyll concentration compared to the GlobColour observations, an improvement which was sustained throughout the year and in every ocean basin. Errors against independent in situ chlorophyll observations were also reduced, both at and beneath the ocean surface. However, the model fit to in situ observations was not consistently better than that of climatology, due to errors in the underlying model. The assimilation scheme used is multivariate, updating all biogeochemical model state variables at all depths. The other variables were not degraded by the assimilation, with annual mean surface fields of nutrients, alkalinity and carbon variables remaining of similar quality compared to climatology. There was evidence of improved representation of zooplankton concentration, and reduced errors were seen against in situ observations of nitrate and pCO2, but too few observations were available to conclude about global model skill. The near-real-time GlobColour products were found to be sufficiently reliable for operational purposes, and of benefit to both operational-style systems and reanalyses.

DNA from soil mirrors plant taxonomic and growth form diversity - N. G. YOCCOZ; K. A. BRÅTHEN; L. GIELLY; J. HAILE; M. E. EDWARDS; T. GOSLAR; H. Von STEDINGK; A. K. BRYSTING; E. COISSAC; F. POMPANON; J. H. SØNSTEBØ; C. MIQUEL; et al. (Molecular Ecology, 2012)
Ecosystems across the globe are threatened by climate change and human activities. New rapid survey approaches for monitoring biodiversity would greatly advance assessment and understanding of these threats. Taking advantage of next‐generation DNA sequencing, we tested an approach we call metabarcoding: high‐throughput and simultaneous taxa identification based on a very short (usually

Holocene climate change and carbon cycling in a groundwater-fed, boreal forest lake: Dune Lake, Alaska - Bruce P. Finney; Nancy H. Bigelow; Valerie A. Barber; Mary E. Edwards (Journal of Paleolimnology, 2012)

Examining the effects of former cannabis use on cerebellum-dependent eyeblink conditioning in humans - Adam B. Steinmetz; Chad R. Edwards; Jennifer M. Vollmer; Molly A. Erickson; Brian F. O’Donnell; William P. Hetrick; Patrick D. Skosnik (Psychopharmacology, 2012)

Removing human immunodeficiency virus (HIV) from human blood using immobilized heparin - Roger A. Nassar; Edward P. Browne; Jianzhu Chen; Alexander M. Klibanov (Biotechnology Letters, 2012)

Assessing trophic position from nitrogen isotope ratios: effective calibration against spatially varying baselines - Paul Woodcock; David P. Edwards; Rob J. Newton; Felicity A. Edwards; Chey Vun Khen; Simon H. Bottrell; Keith C. Hamer (The Science of Nature, 2012)

Navigating the Perfect Storm: Research Strategies for Socialecological Systems in a Rapidly Evolving World - John A. Dearing; Seth Bullock; Robert Costanza; Terry P. Dawson; Mary E. Edwards; Guy M. Poppy; Graham M. Smith (Environmental Management, 2012)

Transcriptomic alterations induced by Ochratoxin A in rat and human renal proximal tubular in vitro models and comparison to a rat in vivo model - Paul Jennings; Christina Weiland; Alice Limonciel; Katarzyna M. Bloch; Robert Radford; Lydia Aschauer; Tara McMorrow; Anja Wilmes; Walter Pfaller; Hans J. Ahr; Craig Slattery; Edward A. Lock; et al. (Archives of Toxicology, 2012)

The regional abundance and size distribution of lakes and reservoirs in the United States and implications for estimates of global lake extent - Cory P. McDonald; Jennifer A. Rover; Edward G. Stets; Robert G. Striegl (Limnology and Oceanography, 2012)
We analyzed complete geospatial data for the 3.5 million lakes and reservoirs larger than 0.001 km 2 , with a combined surface area of 131,000 km 2 , in the contiguous United States (excluding the Laurentian Great Lakes) and identified their regional distribution characteristics. For Alaska, we also analyzed (1) incomplete data that suggest that the state contains 1–2.5 million lakes larger than 0.001 km 2 covering over 50,000 km 2 and (2) localized high‐resolution (5 m) data that suggest that the number of very small water bodies ( 2 ) may be comparable with the number of lakes > 0.001 km 2 in some areas. The Pareto distribution cannot accurately describe the lake abundance‐size relationship across the entire size spectrum, and extrapolation of this density function to small size classes has likely resulted in the overestimation of the number of small lakes in the world. While small water bodies dominate in terms of numbers, they are not numerous enough to dominate in terms of surface area, as has been previously suggested. Extending our results to the global scale suggests that there are on the order of 64 million water bodies larger than 0.001 km 2 in the world, with a total surface area of approximately 3.8 million km 2 .

The rate of permafrost carbon release under aerobic and anaerobic conditions and its potential effects on climate - Hanna Lee; Edward A. G. Schuur; Kanika S. Inglett; Martin Lavoie; Jeffrey P. Chanton (Global Change Biology, 2012)
Recent observations suggest that permafrost thaw may create two completely different soil environments: aerobic in relatively well‐drained uplands and anaerobic in poorly drained wetlands. The soil oxygen availability will dictate the rate of permafrost carbon release as carbon dioxide ( CO 2 ) and as methane ( CH 4 ), and the overall effects of these emitted greenhouse gases on climate. The objective of this study was to quantify CO 2 and CH 4 release over a 500‐day period from permafrost soil under aerobic and anaerobic conditions in the laboratory and to compare the potential effects of these emissions on future climate by estimating their relative climate forcing. We used permafrost soils collected from A laska and S iberia with varying organic matter characteristics and simultaneously incubated them under aerobic and anaerobic conditions to determine rates of CO 2 and CH 4 production. Over 500 days of soil incubation at 15 °C, we observed that carbon released under aerobic conditions was 3.9–10.0 times greater than anaerobic conditions. When scaled by greenhouse warming potential to account for differences between CO 2 and CH 4 , relative climate forcing ranged between 1.5 and 7.1. Carbon release in organic soils was nearly 20 times greater than mineral soils on a per gram soil basis, but when compared on a per gram carbon basis, deep permafrost mineral soils showed carbon release rates similar to organic soils for some soil types. This suggests that permafrost carbon may be very labile, but that there are significant differences across soil types depending on the processes that controlled initial permafrost carbon accumulation within a particular landscape. Overall, our study showed that, independent of soil type, permafrost carbon in a relatively aerobic upland ecosystems may have a greater effect on climate when compared with a similar amount of permafrost carbon thawing in an anaerobic environment, despite the release of CH 4 that occurs in anaerobic conditions.

New Choices and Challenges for Regulated Private Forests: The “Alternate Plan” Option - Roje S. Gootee; Keith A. Blatner; Matthew S. Carroll; David M. Baumgartner; Edward P. Weber (Journal of Forestry, 2011)
The state of Washington has developed a policy instrument that substantially amends traditional “top-down” private forest regulation. Called the “Alternate Plan” option, it gives landowners unusual new flexibility in designing forest management projects for their property. Projects may depart from any of the state's established Forest Practices Rules, if the property owner can satisfactorily show that a customized proposal would provide equivalent environmental protection. The state provides a prompt review and decision and then supervises project implementation and monitors compliance with the approved project specifications. We interviewed 109 stakeholders involved in the design, use, and implementation of this innovative program. From this data we evaluate the functional advantages and challenges inherent in this new regulatory approach, suggest modifications to improve its effectiveness, and discuss policymaking implications.

Equitable regulation of private forests - Roje S. Gootee; Keith A. Blatner; David M. Baumgartner; Matthew S. Carroll; Edward P. Weber (Small-scale Forestry, 2011)

Hybridisation of Australian chickpea cultivars with wild Cicer spp. increases resistance to root-lesion nematodes (Pratylenchus thornei and P. neglectus) - John P. Thompson; Roslyn A. Reen; Timothy G. Clewett; Jason G. Sheedy; Alison M. Kelly; Beverley J. Gogel; Edward J. Knights (Australasian Plant Pathology, 2011)

High frequency variability of the Atlantic meridional overturning circulation - B. Balan Sarojini; J. M. Gregory; R. Tailleux; G. R. Bigg; A. T. Blaker; D. R. Cameron; N. R. Edwards; A. P. Megann; L. C. Shaffrey; B. Sinha (Ocean Science, 2011)
We compare the variability of the Atlantic meridional overturning circulation (AMOC) as simulated by the coupled climate models of the RAPID project, which cover a wide range of resolution and complexity, and observed by the RAPID/MOCHA array at about 26° N. We analyse variability on a range of timescales, from five-daily to interannual. In models of all resolutions there is substantial variability on timescales of a few days; in most AOGCMs the amplitude of the variability is of somewhat larger magnitude than that observed by the RAPID array, while the time-mean is within about 10 % of the observational estimate. The amplitude of the simulated annual cycle is similar to observations, but the shape of the annual cycle shows a spread among the models. A dynamical decomposition shows that in the models, as in observations, the AMOC is predominantly geostrophic (driven by pressure and sea-level gradients), with both geostrophic and Ekman contributions to variability, the latter being exaggerated and the former underrepresented in models. Other ageostrophic terms, neglected in the observational estimate, are small but not negligible. The time-mean of the western boundary current near the latitude of the RAPID/MOCHA array has a much wider model spread than the AMOC does, indicating large differences among models in the simulation of the wind-driven gyre circulation, and its variability is unrealistically small in the models. In many RAPID models and in models of the Coupled Model Intercomparison Project Phase 3 (CMIP3), interannual variability of the maximum of the AMOC wherever it lies, which is a commonly used model index, is similar to interannual variability in the AMOC at 26° N. Annual volume and heat transport timeseries at the same latitude are well-correlated within 15–45° N, indicating the climatic importance of the AMOC. In the RAPID and CMIP3 models, we show that the AMOC is correlated over considerable distances in latitude, but not the whole extent of the North Atlantic; consequently interannual variability of the AMOC at 50° N, where it is particularly relevant to European climate, is not well-correlated with that of the AMOC at 26° N, where it is monitored by the RAPID/MOCHA array.

Motivation and movement: the effect of monetary incentive on performance speed - Pablo Mir; Iris Trender-Gerhard; Mark J. Edwards; Susanne A. Schneider; Kailash P. Bhatia; Marjan Jahanshahi (Experimental Brain Research, 2011)

Cerebellar brain inhibition is decreased in active and surround muscles at the onset of voluntary movement - Panagiotis Kassavetis; Britt S. Hoffland; Tabish A. Saifee; Kailash P. Bhatia; Bart P. van de Warrenburg; John C. Rothwell; Mark J. Edwards (Experimental Brain Research, 2011)

Abundance and distribution of major groups of diazotrophic cyanobacteria and their potential contribution to N 2 fixation in the tropical Atlantic Ocean - Nicole L. Goebel; Kendra A. Turk; Katherine M. Achilles; Ryan Paerl; Ian Hewson; Amanda E. Morrison; Joseph P. Montoya; Christopher A. Edwards; Jonathan P. Zehr (Environmental Microbiology, 2010)
Summary The abundances of six N 2 ‐fixing cyanobacterial phylotypes were profiled at 22 stations across the tropical Atlantic Ocean during June 2006, and used to model the contribution of the diazotrophs to N 2 fixation. Diazotroph abundances were measured by targeting the nifH gene of Trichodesmium , unicellular groups A, B, C (UCYN‐A, UCYN‐B and UCYN‐C), and diatom‐cyanobiont symbioses Hemiaulus–Richelia , Rhizosolenia–Richelia and Chaetoceros–Calothrix . West to east gradients in temperature, salinity and nutrients [NO 3 ‐ + NO 2 ‐ , PO 4 3− , Si(OH) 4 ] showed the influence of the Amazon River plume and its effect on the distributions of the diazotrophs. Trichodesmium accounted for more than 93% of all nifH genes detected, dominated the warmer waters of the western Atlantic, and was the only diazotroph detected at the equatorial upwelling station. UCYN‐A was the next most abundant (> 5% of all nifH genes) and dominated the cooler waters of the eastern Atlantic near the Cape Verde Islands. UCYN‐C was found at a single depth (200 m) of high salinity and low temperature and nutrients, whereas UCYN‐B cells were widespread but in very low abundance (6.1 × 10 1 ± 4.6 × 10 2 gene copies l −1 ). The diatom‐cyanobionts were observed primarily in the western Atlantic within or near the high Si(OH) 4 input of the Amazon River plume. Overall, highest diazotroph abundances were observed at the surface and declined with depth, except for some subsurface peaks in Trichodesmium , UCYN‐B and UCYN‐A. Modelled contributions of Trichodesmium , UCYN‐B and UCYN‐A to total N 2 fixation suggested that Trichodesmium had the largest input, except for the potential of UCYN‐A at the Cape Verde Islands.

Pooled analyses of 13 prospective cohort studies on folate intake and colon cancer - Dong-Hyun Kim; Stephanie A. Smith-Warner; Donna Spiegelman; Shiaw-Shyuan Yaun; Graham A. Colditz; Jo L. Freudenheim; Edward Giovannucci; R. Alexandra Goldbohm; Saxon Graham; Lisa Harnack; Eric J. Jacobs; Michael Leitzmann; et al. (Cancer Causes & Control, 2010)

Factors associated with Type I and Type II endometrial cancer - Ashley S. Felix; Joel L. Weissfeld; Roslyn A. Stone; Robert Bowser; Mamatha Chivukula; Robert P. Edwards; Faina Linkov (Cancer Causes & Control, 2010)

A proposal to change existing virus species names to non-Latinized binomials - Marc H. V. Van Regenmortel; Donald S. Burke; Charles H. Calisher; Ralf G. Dietzgen; Claude M. Fauquet; Said A. Ghabrial; Peter B. Jahrling; Karl M. Johnson; Michael R. Holbrook; Marian C. Horzinek; Günther M. Keil; Jens H. Kuhn; et al. (Archives of Virology, 2010)

Choosing What to Believe About Forests: Differences Between Professional and Non-Professional Evaluative Criteria - Roje S. Gootee; Keith A. Blatner; David M. Baumgartner; Matthew S. Carroll; Edward P. Weber (Small-scale Forestry, 2010)

The Role of the Intestinal Lymphatics in the Absorption of Two Highly Lipophilic Cholesterol Ester Transfer Protein Inhibitors (CP524,515 and CP532,623) - Natalie L. Trevaskis; Claire L. McEvoy; Michelle P. McIntosh; Glenn A. Edwards; Ravi M. Shanker; William N. Charman; Christopher J. H. Porter (Pharmaceutical Research, 2010)

Historical and paleolimnological evidence for expansion of Lake Athabasca (Canada) during the Little Ice Age - R. Niloshini Sinnatamby; Yi Yi; Michael A. Sokal; Kenneth P. Clogg-Wright; Taro Asada; Sheila R. Vardy; Tammy L. Karst-Riddoch; William M. Last; John W. Johnston; Roland I. Hall; Brent B. Wolfe; Thomas W. D. Edwards (Journal of Paleolimnology, 2010)

Derivation and characterisation of the human embryonic stem cell line, OxF1 - Frances Anne Brook; Sally A. Cowley; Edward P. Evans; Karen Turner; William S. James; Helen J. Mardon (In Vitro Cellular & Developmental Biology - Animal, 2010)

Comparing plasma and faecal measures of steroid hormones in Adelie penguins Pygoscelis adeliae - Calum Edward Ninnes; J. R. Waas; N. Ling; S. Nakagawa; J. C. Banks; D. G. Bell; A. Bright; P. W. Carey; J. Chandler; Q. J. Hudson; J. R. Ingram; K. Lyall; et al. (Journal of Comparative Physiology B, 2010)

Genetic map construction and QTL mapping of resistance to blackleg (Leptosphaeria maculans) disease in Australian canola (Brassica napus L.) cultivars - S. Kaur; N. O. I. Cogan; G. Ye; R. C. Baillie; M. L. Hand; A. E. Ling; A. K. Mcgearey; J. Kaur; C. J. Hopkins; M. Todorovic; H. Mountford; D. Edwards; et al. (Theoretical and Applied Genetics, 2009)

The Value of Rehabilitating Logged Rainforest for Birds - DAVID P. EDWARDS; FELICITY A. ANSELL; ABDUL H. AHMAD; REUBEN NILUS; KEITH C. HAMER (Conservation Biology, 2009)
The recent advent of carbon crediting has led to a rapid rise in biosequestration projects that seek to remove carbon from the atmosphere through afforestation and forest rehabilitation. Such projects also present an important potential opportunity to reverse biodiversity losses resulting from deforestation and forest degradation, but the biodiversity benefits of different forms of biosequestration have not been considered adequately. We captured birds in mist nets to examine the effects of rehabilitation of logged forest on birds in Sabah, Borneo, and to test the hypothesis that rehabilitation restores avian assemblages within regenerating forest to a condition closer to that seen in unlogged forest. Species richness and diversity were similar in unlogged and rehabilitated forest, but significantly lower in naturally regenerating forest. Rehabilitation resulted in a relatively rapid recovery of populations of insectivores within logged forest, especially those species that forage by sallying, but had a marked adverse effect on frugivores and possibly reduced the overall abundance of birds within regenerating forest. In view of these results, we advocate increased management for heterogeneity within rehabilitated forests, but we strongly urge an increased role for forest rehabilitation in the design and implementation of a biodiversity‐friendly carbon‐offsetting market.

Infection and replication of Bartonella species within a tick cell line - Sarah A. Billeter; Pedro Paulo V. P. Diniz; James M. Battisti; Ulrike G. Munderloh; Edward B. Breitschwerdt; Michael G. Levy (Experimental and Applied Acarology, 2009)

Rapid effects of hypoxia on H+ homeostasis in articular chondrocytes - John S. Gibson; David McCartney; Joanna Sumpter; Thomas P. A. Fairfax; Peter I. Milner; Hannah L. Edwards; Robert J. Wilkins (Pflügers Archiv - European Journal of Physiology, 2009)

Characterization of 21 microsatellite marker loci in the silky sifaka (Propithecus candidus) - Susie M. McGuire; George P. Emodi; Gary D. Shore; Rick A. Brenneman; Edward E. Louis (Conservation Genetics, 2009)

Targetable HPMA Copolymer–Aminohexylgeldanamycin Conjugates for Prostate Cancer Therapy - Mark P. Borgman; Abhijit Ray; Rohit B. Kolhatkar; Edward A. Sausville; Angelika M. Burger; Hamidreza Ghandehari (Pharmaceutical Research, 2009)

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Forward and reverse genetics of rapid-cycling Brassica oleracea - Edward Himelblau; Erin J. Gilchrist; Kelly Buono; Colleen Bizzell; Laurie Mentzer; Robert Vogelzang; Thomas Osborn; Richard M. Amasino; Isobel A. P. Parkin; George W. Haughn (Theoretical and Applied Genetics, 2009)

Enhanced discrimination of African swine fever virus isolates through nucleotide sequencing of the p54, p72, and pB602L (CVR) genes - Carmina Gallardo; Dufton M. Mwaengo; Joseph M. Macharia; Marisa Arias; Evans A. Taracha; Alejandro Soler; Edward Okoth; Elena Martín; Jackline Kasiti; Richard P. Bishop (Virus Genes, 2009)

Assessing the extent and diversity of riparian ecosystems in Sonora, Mexico - Michael L. Scott; Pamela L. Nagler; Edward P. Glenn; Carlos Valdes-Casillas; Joseph A. Erker; Elizabeth W. Reynolds; Patrick B. Shafroth; Euduardo Gomez-Limon; Cory L. Jones (Biodiversity and Conservation, 2009)

Photoperiod insensitive Ppd-A1a mutations in tetraploid wheat (Triticum durum Desf.) - Edward P. Wilhelm; Adrian S. Turner; David A. Laurie (Theoretical and Applied Genetics, 2009)

Lemur Diversity in Madagascar - Russell A. Mittermeier; Jörg U. Ganzhorn; William R. Konstant; Kenneth Glander; Ian Tattersall; Colin P. Groves; Anthony B. Rylands; Andreas Hapke; Jonah Ratsimbazafy; Mireya I. Mayor; Edward E. Louis; Yves Rumpler; et al. (International Journal of Primatology, 2008)

Sub‐millennial climate shifts in the western Mediterranean during the last glacial period recorded in a speleothem from Mallorca, Spain - Edward J. Hodge; David A. Richards; Peter L. Smart; Angel Ginés; David P. Mattey (Journal of Quaternary Science, 2008)
Very few high‐resolution and directly dated terrestrial archives of the last glacial period exist for the western Mediterranean region, yet this is a key locality for recording sub‐millennial North Atlantic and Mediterranean climate change. Here, we present evidence of effective precipitation changes based on growth history and δ 13 C of calcite in a Mallorcan stalagmite that grew between 112 and 48 ka. Effective precipitation in Mallorca appears to have been sensitive to proximal sea surface temperature variations and at certain times, ca. 76 ka for example, changed rapidly from moist to arid conditions in only a few centuries. A sea‐level highstand during Marine Isotope Stage (MIS) 5a interrupted growth. Regrowth started promptly after this, but effective precipitation decreased markedly for much of the later part of MIS 5a, and also for shorter periods correlative with Heinrich events H8 (ca. 90 ka) and H6 (ca. 65 ka), with growth ceasing during H5 (ca. 48 ka). Arid episodes in Mallorca appear to be expressions of extremely cold periods recorded further north in Europe and occur contemporaneously with rapid decreases in Greenland temperature. Copyright © 2008 John Wiley & Sons, Ltd.

Preparation of Active Proteins, Vaccines and Pharmaceuticals as Fine Powders using Supercritical or Near-Critical Fluids - Stephen P. Cape; Joseph A. Villa; Edward T. S. Huang; Tzung-Horng Yang; John F. Carpenter; Robert E. Sievers (Pharmaceutical Research, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Upgrades to the Boundary-Layer Scheme in the Met Office Numerical Weather Prediction Model - A. R. Brown; R. J. Beare; J. M. Edwards; A. P. Lock; S. J. Keogh; S. F. Milton; D. N. Walters (Boundary-Layer Meteorology, 2008)

Carbon allocation in boreal black spruce forests across regions varying in soil temperature and precipitation - JASON G. VOGEL; BEN P. BOND‐LAMBERTY; EDWARD A. G. SCHUUR; STITH T. GOWER; MICHELLE C. MACK; KARI E. B. O'CONNELL; DAVID W. VALENTINE; ROGER W. RUESS (Global Change Biology, 2008)
A common hypothesis for northern ecosystems is that low soil temperatures inhibit plant productivity. To address this hypothesis, we reviewed how separate components of ecosystem carbon (C) cycling varied along a soil temperature gradient for nine well‐drained, relatively productive boreal black spruce ( Picea mariana Mill. [B.S.P.]) forests in Alaska, USA, and Saskatchewan and Manitoba, Canada. Annual soil temperature [expressed as soil summed degree days (SDD)] was positively correlated with aboveground net primary productivity (ANPP), while negatively correlated with total belowground carbon flux (TBCF). The partitioning of C to ANPP at the expense of root processes represented a nearly 1 : 1 tradeoff across the soil temperature gradient, which implied that the amount of C cycling through these black spruce ecosystems was relatively insensitive to variation in SDD. Moreover, the rate at which C accumulated in the ecosystem since the last stand replacing fire was unrelated to SDD, but SDD was positively correlated to the ratio of spruce‐biomass : forest‐floor‐mass. Thus, plant partitioning of C and the distribution of ecosystem C were apparently affected by soil temperature, although across regions, precipitation co‐varied with soil temperature. These two factors likely correlated with one another because of precipitation's influence on soil heat balance, suggesting that a soil temperature–precipitation interaction could be responsible for the shifts in C allocation. Nonetheless, our results highlight that for this boreal ecosystem, ANPP and TBCF can be negatively correlated. In tropical and temperate forests, TBCF and ANPP have been reported as positively correlated, and our results may reflect the unique interactions between soil temperature, forest floor accumulation, rooting depth, and nutrient availability that characterize the black spruce forest type.

Dispersal of black sea bass ( Centropristis striata ) larvae on the southeast U.S. continental shelf: results of a coupled vertical larval behavior – 3D circulation model - K. P. EDWARDS; J. A. HARE; F. E. WERNER (Fisheries Oceanography, 2008)
In the marine environment, pelagic dispersal is important for determining the distribution and abundance of populations, as well as providing connections among populations. Estimates of larval dispersal from spawning grounds are important to determining temporal and spatial patterns in recruitment that may have significant influences on the dynamics of the population. We present a case study of the dispersal of Centropristis striata (black sea bass) larvae on the southeast U.S. continental shelf. We use a coupled larval behavior – 3D circulation model to compare the effects of the timing and location of spawning against that of larval vertical migration on larval dispersal. Using the results of field data on larval vertical distributions, we compare the dispersal of virtual ‘larvae’ which have ontogenetic changes in vertical behavior with that of particles fixed near the surface and near the bottom. Larvae were released at potential spawning sites four times throughout the spawning season (February through May) for 3 yr (2002–04) and tracked for the assumed larval duration (from 27 to 37 days including the egg stage). Results indicate that adult behavior, in the form of spawning time and location, may be more important than larval vertical behavior in determining larval dispersal on the inner‐ and mid‐ continental shelves of this region.

Evaluation of a urine screen for acetaminophen - Daniel M. Ingram; George M. Bosse; Edward P. Womack; Saeed A. Jortani (Journal of Medical Toxicology, 2008)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Simulating complex flow and transport dynamics in an integrated surface-subsurface modeling framework - Edward A. Sudicky; Jon P. Jones; Young-Jin Park; Andrea E. Brookfield; Dennis Colautti (Geosciences Journal, 2008)

The plant availability of auto-cast platinum group elements - P. S. Hooda; A. Miller; A. C. Edwards (Environmental Geochemistry and Health, 2008)

Multi-species spawning of corals in north-western Philippines - K. C. Vicentuan; J. R. Guest; M. V. Baria; P. C. Cabaitan; R. M. Dizon; R. D. Villanueva; P. M. Aliño; A. J. Edwards; E. D. Gomez; A. J. Heyward (Coral Reefs, 2008)

An investigation into the use of human papillomavirus type 16 virus-like particles as a delivery vector system for foreign proteins: N- and C-terminal fusion of GFP to the L1 and L2 capsid proteins - Oliver P. Windram; Brandon Weber; Mohamed A. Jaffer; Edward P. Rybicki; Dionne N. Shepherd; Arvind Varsani (Archives of Virology, 2008)

Prediction uncertainty of environmental change effects on temperate European biodiversity - Carsten F. Dormann; Oliver Schweiger; P. Arens; I. Augenstein; St. Aviron; Debra Bailey; J. Baudry; R. Billeter; R. Bugter; R. Bukácek; F. Burel; M. Cerny; et al. (Ecology Letters, 2008)
Observed patterns of species richness at landscape scale (gamma diversity) cannot always be attributed to a specific set of explanatory variables, but rather different alternative explanatory statistical models of similar quality may exist. Therefore predictions of the effects of environmental change (such as in climate or land cover) on biodiversity may differ considerably, depending on the chosen set of explanatory variables. Here we use multimodel prediction to evaluate effects of climate, land‐use intensity and landscape structure on species richness in each of seven groups of organisms (plants, birds, spiders, wild bees, ground beetles, true bugs and hoverflies) in temperate Europe. We contrast this approach with traditional best‐model predictions, which we show, using cross‐validation, to have inferior prediction accuracy. Multimodel inference changed the importance of some environmental variables in comparison with the best model, and accordingly gave deviating predictions for environmental change effects. Overall, prediction uncertainty for the multimodel approach was only slightly higher than that of the best model, and absolute changes in predicted species richness were also comparable. Richness predictions varied generally more for the impact of climate change than for land‐use change at the coarse scale of our study. Overall, our study indicates that the uncertainty introduced to environmental change predictions through uncertainty in model selection both qualitatively and quantitatively affects species richness projections.

Atlantic reef fish biogeography and evolution - S. R. Floeter; L. A. Rocha; D. R. Robertson; J. C. Joyeux; W. F. Smith‐Vaniz; P. Wirtz; A. J. Edwards; J. P. Barreiros; C. E. L. Ferreira; J. L. Gasparini; A. Brito; J. M. Falcón; et al. (Journal of Biogeography, 2008)
Aim To understand why and when areas of endemism (provinces) of the tropical Atlantic Ocean were formed, how they relate to each other, and what processes have contributed to faunal enrichment. Location Atlantic Ocean. Methods The distributions of 2605 species of reef fishes were compiled for 25 areas of the Atlantic and southern Africa. Maximum‐parsimony and distance analyses were employed to investigate biogeographical relationships among those areas. A collection of 26 phylogenies of various Atlantic reef fish taxa was used to assess patterns of origin and diversification relative to evolutionary scenarios based on spatio‐temporal sequences of species splitting produced by geological and palaeoceanographic events. We present data on faunal (species and genera) richness, endemism patterns, diversity buildup (i.e. speciation processes), and evaluate the operation of the main biogeographical barriers and/or filters. Results Phylogenetic (proportion of sister species) and distributional (number of shared species) patterns are generally concordant with recognized biogeographical provinces in the Atlantic. The highly uneven distribution of species in certain genera appears to be related to their origin, with highest species richness in areas with the greatest phylogenetic depth. Diversity buildup in Atlantic reef fishes involved (1) diversification within each province, (2) isolation as a result of biogeographical barriers, and (3) stochastic accretion by means of dispersal between provinces. The timing of divergence events is not concordant among taxonomic groups. The three soft (non‐terrestrial) inter‐regional barriers (mid‐Atlantic, Amazon, and Benguela) clearly act as ‘filters’ by restricting dispersal but at the same time allowing occasional crossings that apparently lead to the establishment of new populations and species. Fluctuations in the effectiveness of the filters, combined with ecological differences among provinces, apparently provide a mechanism for much of the recent diversification of reef fishes in the Atlantic. Main conclusions Our data set indicates that both historical events (e.g. Tethys closure) and relatively recent dispersal (with or without further speciation) have had a strong influence on Atlantic tropical marine biodiversity and have contributed to the biogeographical patterns we observe today; however, examples of the latter process outnumber those of the former.

Circulation in Carr Inlet, Puget Sound, during Spring 2003 - Kathleen A. Edwards; Mitsuhiro Kawase; Christian P. Sarason (Estuaries and Coasts, 2007)

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

Modelling the vertical distribution of Prochlorococcus and Synechococcus in the North Pacific Subtropical Ocean - Sophie Rabouille; Christopher A. Edwards; Jonathan P. Zehr (Environmental Microbiology, 2007)
Summary A simple model was developed to examine the vertical distribution of Prochlorococcus and Synechococcus ecotypes in the water column, based on their adaptation to light intensity. Model simulations were compared with a 14‐year time series of Prochlorococcus and Synechococcus cell abundances at Station ALOHA in the North Pacific Subtropical Gyre. Data were analysed to examine spatial and temporal patterns in abundances and their ranges of variability in the euphotic zone, the surface mixed layer and the layer in the euphotic zone but below the base of the mixed layer. Model simulations show that the apparent occupation of the whole euphotic zone by a genus can be the result of a co‐occurrence of different ecotypes that segregate vertically. The segregation of ecotypes can result simply from differences in light response. A sensitivity analysis of the model, performed on the parameter α (initial slope of the light‐response curve) and the DIN concentration in the upper water column, demonstrates that the model successfully reproduces the observed range of vertical distributions. Results support the idea that intermittent mixing events may have important ecological and geochemical impacts on the phytoplankton community at Station ALOHA.

Effects of atmospheric dynamics and ocean resolution on bi-stability of the thermohaline circulation examined using the Grid ENabled Integrated Earth system modelling (GENIE) framework - T. M. Lenton; R. Marsh; A. R. Price; D. J. Lunt; Y. Aksenov; J. D. Annan; T. Cooper-Chadwick; S. J. Cox; N. R. Edwards; S. Goswami; J. C. Hargreaves; P. P. Harris; et al. (Climate Dynamics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Exploration of Ellsworth Subglacial Lake: a concept paper on the development, organisation and execution of an experiment to explore, measure and sample the environment of a West Antarctic subglacial lake - M.J. Siegert; A. Behar; M. Bentley; D. Blake; S. Bowden; P. Christoffersen; C. Cockell; H. Corr; D. C. Cullen; H. Edwards; A. Ellery; C. Ellis-Evans; et al. (Reviews in Environmental Science and Bio/Technology, 2007)

Comparative genomics reveals functional transcriptional control sequences in the Prop1 gene - Robert D. Ward; Shannon W. Davis; MinChul Cho; Constance Esposito; Robert H. Lyons; Jan-Fang Cheng; Edward M. Rubin; Simon J. Rhodes; Lori T. Raetzman; Timothy P. L. Smith; Sally A. Camper (Mammalian Genome, 2007)

Psychiatric safety of ketamine in psychopharmacology research - Edward B. Perry; Joyce A. Cramer; Hyun-Sang Cho; Ismene L. Petrakis; Laurence P. Karper; Angelina Genovese; Elizabeth O’Donnell; John H. Krystal; D. Cyril D’Souza (Psychopharmacology, 2007)

GPS sidereal filtering: coordinate- and carrier-phase-level strategies - A. E. Ragheb; P. J. Clarke; S. J. Edwards (Journal of Geodesy, 2007)

Above- and belowground biomass measurements in an unthinned stand of Sitka spruce (Picea sitchensis (Bong) Carr.) - Carly Green; Brian Tobin; Michael O’Shea; Edward P. Farrell; Kenneth A. Byrne (European Journal of Forest Research, 2007)

A high resolution green area index for modelling the seasonal dynamics of CO2 exchange in peatland vascular plant communities - David Wilson; Jukka Alm; Terhi Riutta; Jukka Laine; Kenneth A. Byrne; Edward P. Farrell; Eeva-Stiina Tuittila (Plant Ecology, 2007)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

Progress in isotope paleohydrology using lake sediment cellulose - Brent B. Wolfe; Matthew D. Falcone; Ken P. Clogg-Wright; Cherie L. Mongeon; Yi Yi; Bronwyn E. Brock; Natalie A. St. Amour; William A. Mark; Thomas W. D. Edwards (Journal of Paleolimnology, 2007)

Improving Data Reliability Using a Non-Compliance Detection Method versus Using Pharmacokinetic Criteria - Smita A. Kshirsagar; Terrence F. Blaschke; Lewis B. Sheiner; M. Krygowski; Edward P. Acosta; Davide Verotta (Journal of Pharmacokinetics and Pharmacodynamics, 2007)

Bottom‐up forcing and the decline of Steller sea lions ( Eumetopias jubatus ) in Alaska: assessing the ocean climate hypothesis - ANDREW W. TRITES; ARTHUR J. MILLER; HERBERT D. G. MASCHNER; MICHAEL A. ALEXANDER; STEVEN J. BOGRAD; JOHN A. CALDER; ANTONIETTA CAPOTONDI; KENNETH O. COYLE; EMANUELE DI LORENZO; BRUCE P. FINNEY; EDWARD J. GREGR; CHESTER E. GROSCH; et al. (Fisheries Oceanography, 2007)
Declines of Steller sea lion ( Eumetopias jubatus ) populations in the Aleutian Islands and Gulf of Alaska could be a consequence of physical oceanographic changes associated with the 1976–77 climate regime shift. Changes in ocean climate are hypothesized to have affected the quantity, quality, and accessibility of prey, which in turn may have affected the rates of birth and death of sea lions. Recent studies of the spatial and temporal variations in the ocean climate system of the North Pacific support this hypothesis. Ocean climate changes appear to have created adaptive opportunities for various species that are preyed upon by Steller sea lions at mid‐trophic levels. The east–west asymmetry of the oceanic response to climate forcing after 1976–77 is consistent with both the temporal aspect (populations decreased after the late 1970s) and the spatial aspect of the decline (western, but not eastern, sea lion populations decreased). These broad‐scale climate variations appear to be modulated by regionally sensitive biogeographic structures along the Aleutian Islands and Gulf of Alaska, which include a transition point from coastal to open‐ocean conditions at Samalga Pass westward along the Aleutian Islands. These transition points delineate distinct clusterings of different combinations of prey species, which are in turn correlated with differential population sizes and trajectories of Steller sea lions. Archaeological records spanning 4000 yr further indicate that sea lion populations have experienced major shifts in abundance in the past. Shifts in ocean climate are the most parsimonious underlying explanation for the broad suite of ecosystem changes that have been observed in the North Pacific Ocean in recent decades.

Pink eye is an unusual periderm disorder characterized by aberrant suberization: A cytological analysis - Edward C. Lulai; John J. Weiland; Jeffrey C. Suttle; Robert P. Sabba; A. J. Bussan (American Journal of Potato Research, 2006)

Sensitivity of Marine‐Reserve Design to the Spatial Resolution of Socioeconomic Data - ELIZABETH A. RICHARDSON; MICHEL J. KAISER; GARETH EDWARDS‐JONES; HUGH P. POSSINGHAM (Conservation Biology, 2006)
Socioeconomic considerations should have an important place in reserve design. Systematic reserve‐selection tools allow simultaneous optimization for ecological objectives while minimizing costs but are seldom used to incorporate socioeconomic costs in the reserve‐design process. The sensitivity of this process to biodiversity data resolution has been studied widely but the issue of socioeconomic data resolution has not previously been considered. We therefore designed marine reserves for biodiversity conservation with the constraint of minimizing commercial fishing revenue losses and investigated how economic data resolution affected the results. Incorporating coarse‐resolution economic data from official statistics generated reserves that were only marginally less costly to the fishery than those designed with no attempt to minimize economic impacts. An intensive survey yielded fine‐resolution data that, when incorporated in the design process, substantially reduced predicted fishery losses. Such an approach could help minimize fisher displacement because the least profitable grounds are selected for the reserve. Other work has shown that low‐resolution biodiversity data can lead to underestimation of the conservation value of some sites, and a risk of overlooking the most valuable areas, and we have similarly shown that low‐resolution economic data can cause underestimation of the profitability of some sites and a risk of inadvertently including these in the reserve. Detailed socioeconomic data are therefore an essential input for the design of cost‐effective reserve networks.

Neuronal Network Models of Phase Separation Between Limb CPGs of Digging Sand Crabs - A. Hodge; R. Edwards; D. H. Paul; P. van den Driessche (Biological Cybernetics, 2006)

Stand age‐related effects on soil respiration in a first rotation Sitka spruce chronosequence in central Ireland - GUSTAVO SAIZ; KENNETH A. BYRNE; KLAUS BUTTERBACH‐BAHL; RALF KIESE; VIOREL BLUJDEA; EDWARD P. FARRELL (Global Change Biology, 2006)
The effect of stand age on soil respiration and its components was studied in a first rotation Sitka spruce chronosequence composed of 10‐, 15‐, 31‐, and 47‐year‐old stands established on wet mineral gley in central Ireland. For each stand age, three forest stands with similar characteristics of soil type and site preparation were used. There were no significant differences in total soil respiration among sites of the same age, except for the case of a 15‐year‐old stand that had lower soil respiration rates due to its higher productivity. Soil respiration initially decreased with stand age, but levelled out in the older stands. The youngest stands had significantly higher respiration rates than more mature sites. Annual soil respiration rates were modelled by means of temperature‐derived functions. The average Q 10 value obtained treating all the stands together was 3.8. Annual soil respiration rates were 991, 686, 556, and 564 g C m −2 for the 10‐, 15‐, 31‐, and 47‐year‐old stands, respectively. We used the trenching approach to separate soil respiration components. Heterotrophic respiration paralleled soil organic carbon dynamics over the chronosequence, decreasing with stand age to slightly increase in the oldest stand as a result of accumulated aboveground litter and root inputs. Root respiration showed a decreasing trend with stand age, which was explained by a decrease in fine root biomass over the chronosequence, but not by nitrogen concentration of fine roots. The decrease in the relative contribution of autotrophic respiration to total soil CO 2 efflux from 59.3% in the youngest stand to 49.7% in the oldest stand was explained by the higher activity of the root system in younger stands. Our results show that stand age should be considered if simple temperature‐based models to predict annual soil respiration in afforestation sites are to be used.

Stand age-related effects on soil respiration in a first rotation Sitka spruce chronosequence in central Ireland - GUSTAVO SAIZ; KENNETH A. BYRNE; KLAUS BUTTERBACH-BAHL; RALF KIESE; VIOREL BLUJDEA; EDWARD P. FARRELL (Global Change Biology, 2006)

Two-locus genome-wide linkage scan for prostate cancer susceptibility genes with an interaction effect - Bao-Li Chang; Ethan M. Lange; Latchezar Dimitrov; Christopher J. Valis; Elizabeth M. Gillanders; Leslie A. Lange; Kathleen E. Wiley; Sarah D. Isaacs; Fredrik Wiklund; Agnes Baffoe-Bonnie; Carl D Langefeld; S. Lilly Zheng; et al. (Human Genetics, 2006)

Oracle-based optimization applied to climate model calibration - Cesar Beltran; N. R. Edwards; A. B. Haurie; J.-P. Vial; D. S. Zachary (Environmental Modeling & Assessment, 2006)

Transgenic Plants for Insect Pest Control: A Forward Looking Scientific Perspective - N. Ferry; M. G. Edwards; J. Gatehouse; T. Capell; P. Christou; A. M. R. Gatehouse (Transgenic Research, 2006)

Case Study Part 2: Probabilistic Modelling of Long-term Effects of Pesticides on Individual Breeding Success in Birds and Mammals - W. ROELOFS; D.R. CROCKER; R.F. SHORE; D.R.J. MOORE; G.C. SMITH; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; et al. (Ecotoxicology, 2005)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

Mental maze solving: directional fMRI tuning and population coding in the superior parietal lobule - Pavlos Gourtzelidis; Charidimos Tzagarakis; Scott M. Lewis; David A. Crowe; Edward Auerbach; Trenton A. Jerde; Kâmil Uğurbil; Apostolos P. Georgopoulos (Experimental Brain Research, 2005)

Development of baroreflex and endocrine responses to hypotensive stress in newborn foals and lambs - S. J. O’Connor; D. S. Gardner; J. C. Ousey; N. Holdstock; P. Rossdale; C. M. B. Edwards; A. L. Fowden; D. A. Giussani (Pflügers Archiv - European Journal of Physiology, 2005)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

Dietary Influences on the Bioaccumulation of Pollutants by the Annelid, Lumbriculus variegatus: Experiments Comparing Artificial Particles and Natural Sediments - P. A. Edwards; K. Simkiss (Bulletin of Environmental Contamination and Toxicology, 2005)

NMI-1182, a gastro-protective cyclo-oxygenase-inhibiting nitric oxide donor - James L. Ellis; Michael E. Augustyniak; Edward D. Cochran; Richard A. Earl; David S. Garvey; Laura J. Gordon; David R. Janero; Subhash P. Khanapure; L. Gordon Letts; Terry L. Melim; Madhavi G. Murty; David J. Schwalb; et al. (Inflammopharmacology, 2005)

Relationship between the incidences of ear and spikelet infection of Fusarium ear blight in wheat - X.-m. Xu; D.W. Parry; S.G. Edwards; B.M. Cooke; F.M. Doohan; A. Maanen; J.M. Brennan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; L. Hornok; et al. (European Journal of Plant Pathology, 2004)

Single Particle Analysis: A new approach to solving the 3D structure of myosin filaments - Hind A. Al-Khayat; Edward P. Morris; John M. Squire (Journal of Muscle Research and Cell Motility, 2004)

Mapping Ds insertions in barley using a sequence-based approach - L. D. Cooper; L. Marquez-Cedillo; J. Singh; A. K. Sturbaum; S. Zhang; V. Edwards; K. Johnson; A. Kleinhofs; S. Rangel; V. Carollo; P. Bregitzer; P. G. Lemaux; et al. (Molecular Genetics and Genomics, 2004)

Toxicological Evaluation and QSAR Modelling of Aromatic Amines to Chlorella vulgaris - T. I. Netzeva; J. C. Dearden; R. Edwards; A. D. P. Worgan; M. T. D. Cronin (Bulletin of Environmental Contamination and Toxicology, 2004)

Qualification of analytical instruments for use in the pharmaceutical industry: A scientific approach - Surendra K. Bansal; Thomas Layloff; Ernest D. Bush; Marta Hamilton; Edward A. Hankinson; John S. Landy; Stephen Lowes; Moheb M. Nasr; Paul A. St. Jean; Vinod P. Shah (AAPS PharmSciTech, 2004)

Qualification of analytical instruments for use in the pharmaceutical industry: A scientific approach - Surendra K. Bansal; Thomas Layloff; Ernest D. Bush; Marta Hamilton; Edward A. Hankinson; John S. Landy; Stephen Lowes; Moheb M. Nasr; Paul A. St. Jean; Vinod P. Shah (AAPS PharmSciTech, 2004)

Precision of Dialysis (Peeper) Sampling of Cadmium in Marine Sediment Interstitial Water - J. R. Serbst; R. M. Burgess; A. Kuhn; P. A. Edwards; M. G. Cantwell; M. C. Pelletier; W. J. Berry (Archives of Environmental Contamination and Toxicology, 2003)

Wind strength and biological productivity in upwelling systems: an idealized study - Louis W. Botsford; Cathryn A. Lawrence; Edward P. Dever; Alan Hastings; John Largier (Fisheries Oceanography, 2003)
Biological production in wind‐driven coastal upwelling systems is of global importance. To understand better how wind speed and shelf width affect productivity, we formulated a simple model of cross‐shelf transport that included the dynamics of one potential mechanism: increasing nutrients with increasing winds, with possible loss of productivity due to off‐shelf Ekman transport. We used this model to determine how shelf productivity would depend on wind speed and shelf width using several ecosystem (Nutrient–Phytoplankton–Zooplankton, NPZ) models that reflect different trophic pathways and differences in model stability. For constant wind speeds, shelf productivity for all of the NPZ models declined beyond a certain wind speed. The shelf transit time beyond which productivity declines can be determined graphically from the time course of cumulative production in the NPZ model. Shelf width and latitude then determine the corresponding wind speed. The predicted points of decline in productivity with wind‐speed were consistent with data from local observations of higher trophic levels on the central California coast. Only shelf productivity of the NPZ model reflecting new production was dome‐shaped. Shelf productivity of models of regenerated production remained constant with wind speed at low winds. Artificial instability in NPZ models can lead to an inaccurate dependence of productivity on wind. Our model of coastal upwelling, which represents production as cross‐shelf transport of parcels containing developing NPZ models, exhibits a different dependence on wind forcing than previous models that represented upwelling production as a fully mixed shelf. The relative degree of mixing versus transport in upwelling systems is a critical factor underlying the dependence of productivity on wind.

Reduced hybrid cluster proteins (HCP) from Desulfovibrio desulfuricans ATCC 27774 and Desulfovibrio vulgaris (Hildenborough): X-ray structures at high resolution using synchrotron radiation - David Aragão; Sofia Macedo; Edward P. Mitchell; Célia V. Romão; Ming Y. Liu; Carlos Frazão; Lígia M. Saraiva; António V. Xavier; Jean LeGall; Walter M. A. M. van Dongen; Wilfred R. Hagen; Miguel Teixeira; et al. (JBIC Journal of Biological Inorganic Chemistry, 2003)

Genetic mapping of grapevine (Vitis vinifera L.) applied to the detection of QTLs for seedlessness and berry weight - A. Doligez; A. Bouquet; Y. Danglot; F. Lahogue; S. Riaz; C. Meredith; K. Edwards; P. This (Theoretical and Applied Genetics, 2002)

SNPs in putative regulatory regions identified by human mouse comparative sequencing and transcription factor binding site data - Poulabi Banerjee; Melanie Bahlo; Jody R. Schwartz; Gabriela G. Loots; Kathryn A. Houston; Inna Dubchak; Terence P. Speed; Edward M. Rubin (Mammalian Genome, 2002)

Genetic mapping of 66 new microsatellite (SSR) loci in bread wheat - P. Gupta; H. Balyan; K. Edwards; P. Isaac; V. Korzun; M. Röder; M.–F. Gautier; P. Joudrier; A. Schlatter; J. Dubcovsky; R. De la Pena; M. Khairallah; et al. (Theoretical and Applied Genetics, 2002)

Dry matter production and boron concentrations of vegetative and reproductive tissues of canola and sunflower plants grown in nutrient solution - A. Asad; F. P. C. Blamey; D. G. Edwards (Plant and Soil, 2002)

Hybrid cluster proteins (HCPs) from Desulfovibrio desulfuricans ATCC 27774 and Desulfovibrio vulgaris (Hildenborough): X-ray structures at 1.25 Å resolution using synchrotron radiation - Sofia Macedo; Edward P. Mitchell; Célia V. Romão; Serena J. Cooper; Ricardo Coelho; Ming Y. Liu; António V. Xavier; Jean LeGall; Susan Bailey; David C. Garner; Wilfred R. Hagen; Miguel Teixeira; et al. (JBIC Journal of Biological Inorganic Chemistry, 2002)

The C1 locus in maize (Zea mays L.): effect on gene expression - J. Edwards; D. Stoltzfus; P. A. Peterson (Theoretical and Applied Genetics, 2001)

Genetic, physical, and phenotypic characterization of the Del(13)Svea36H mouse - Ruth M. Arkell; Matthew Cadman; Tracy Marsland; Anne Southwell; Caroline Thaung; Jennifer R. Davies; Toni Clay; Colin V. Beechey; Edward P. Evans; Mark A. Strivens; Steve D.M. Brown; Paul Denny (Mammalian Genome, 2001)

Availability of medicines in the European Union: results from the EURO-Medicines project - Folino-Gallo P.; Walley T.; Frolich J.; Carvajal A.; Edwards I. (European Journal of Clinical Pharmacology, 2001)

Unprecedented bleaching-induced mortality in Porites spp. at Rangiroa Atoll, French Polynesia - Mumby P.; Chisholm J.; Edwards A.; Clark C.; Roark E.; Andrefouet S.; Jaubert J. (Marine Biology, 2001)

A Multivariate Analysis of Biophysical Parameters of Tallgrass Prairie Among Land Management Practices and Years - Jerry A. Griffith; Kevin P. Price; Edward A. Martinko (Environmental Monitoring and Assessment, 2001)

Proteomic analysis reveals a novel set of cell wall proteins in a transformed tobacco cell culture that synthesises secondary walls as determined by biochemical and morphological parameters - Kristopher A. Blee; Edward R. Wheatley; Victoria A. Bonham; Geoffrey P. Mitchell; Duncan Robertson; Antoni R. Slabas; Michael M. Burrell; Przemyslaw Wojtaszek; G. Paul Bolwell (Planta, 2001)

Assessing anthropogenic impact on Mediterranean sand dunes from aerial digital photography - R. H. F. Curr; A. Koh; E. Edwards; A. T. Williams; P. Davies (Journal of Coastal Conservation, 2000)

Microsatellites for Barren Brome ( Anisantha sterilis ) - J. M. Green; K. J. Edwards; S. L. Usher; J. H. A. Barker; E. J. P. Marshall; R. J. Froud‐Williams; A. Karp (Molecular Ecology, 2000)

Construction and analysis of bacterial artificial chromosome libraries from a marine microbial assemblage - Oded Béjà; Marcelino T. Suzuki; Eugene V. Koonin; L. Aravind; Andrew Hadd; Linh P. Nguyen; Rachel Villacorta; Mojgan Amjadi; Corey Garrigues; Stevan B. Jovanovich; Robert A. Feldman; Edward F. DeLong (Environmental Microbiology, 2000)
Cultivation‐independent surveys of ribosomal RNA genes have revealed the existence of novel microbial lineages, many with no known cultivated representatives. Ribosomal RNA‐based analyses, however, often do not provide significant information beyond phylogenetic affiliation. Analysis of large genome fragments recovered directly from microbial communities represents one promising approach for characterizing uncultivated microbial species better. To assess further the utility of this approach, we constructed large‐insert bacterial artificial chromosome (BAC) libraries from the genomic DNA of planktonic marine microbial assemblages. The BAC libraries we prepared had average insert sizes of ≈ 80 kb, with maximal insert sizes > 150 kb. A rapid screening method assessing the phylogenetic diversity and representation in the library was developed and applied. In general, representation in the libraries agreed well with previous culture‐independent surveys based on polymerase chain reaction (PCR)‐amplified rRNA fragments. A significant fraction of the genome fragments in the BAC libraries originated from as yet uncultivated microbial species, thought to be abundant and widely distributed in the marine environment. One entire BAC insert, derived from an uncultivated, surface‐dwelling euryarchaeote, was sequenced completely. The planktonic euryarchaeal genome fragment contained some typical archaeal genes, as well as unique open reading frames (ORFs) suggesting novel function. In total, our results verify the utility of BAC libraries for providing access to the genomes of as yet uncultivated microbial species. Further analysis of these BAC libraries has the potential to provide significant insight into the genomic potential and ecological roles of many indigenous microbial species, cultivated or not.

Geochemistry and tectonic significance of peridotites from the South Sandwich arc-basin system, South Atlantic - J. A. Pearce; P. F. Barker; S. J. Edwards; I. J. Parkinson; P. T. Leat (Contributions to Mineralogy and Petrology, 2000)

Pollen‐based biomes for Beringia 18,000, 6000 and 0 14 C yr bp † - M. E. Edwards; P. M. Anderson; L. B. Brubaker; T. A. Ager; A. A. Andreev; N. H. Bigelow; L. C. Cwynar; W. R. Eisner; S. P. Harrison; F.‐S. Hu; D. Jolly; A. V. Lozhkin; et al. (Journal of Biogeography, 2000)
The objective biomization method developed by Prentice et al . (1996) for Europe was extended using modern pollen samples from Beringia and then applied to fossil pollen data to reconstruct palaeovegetation patterns at 6000 and 18,000 14 C yr bp . The predicted modern distribution of tundra, taiga and cool conifer forests in Alaska and north‐western Canada generally corresponds well to actual vegetation patterns, although sites in regions characterized today by a mosaic of forest and tundra vegetation tend to be preferentially assigned to tundra. Siberian larch forests are delimited less well, probably due to the extreme under‐representation of Larix in pollen spectra. The biome distribution across Beringia at 6000 14 C yr bp was broadly similar to today, with little change in the northern forest limit, except for a possible northward advance in the Mackenzie delta region. The western forest limit in Alaska was probably east of its modern position. At 18,000 14 C yr bp the whole of Beringia was covered by tundra. However, the importance of the various plant functional types varied from site to site, supporting the idea that the vegetation cover was a mosaic of different tundra types.

Effects of supplemental α-tocopherol and β-carotene on colorectal cancer: results from a controlled trial (Finland) - Demetrius Albanes; Nea Malila; Philip R. Taylor; Jussi K. Huttunen; Jarmo Virtamo; Brenda K. Edwards; Matti Rautalahti; Anne M. Hartman; Michael J. Barrett; Pirjo Pietinen; Terryl J. Hartman; Pentti Sipponen; et al. (Cancer Causes & Control, 2000)

Abstracts of presentations on selected topics at the XIVth international plant protection congress (IPPC) July 25–30, 1999 - R. Hull; H. A. Kuiper; Maryvon Y. Noordam; Marjorie A. Hoy; Jenny S. Cory; A. C. Fereres; P. Gonzalez; F. Meins; Y. Elkind; Benedicte Charrier; P. Meyer; M. Metzlaff; et al. (Phytoparasitica, 1999)

Mazeno Pass Pluton and Jutial Pluton, Pakistan Himalaya: age and implications for entrapment mechanisms of two granites in the Himalaya - D. A. Schneider; M. A. Edwards; P. K. Zeitler; C. D. Coath (Contributions to Mineralogy and Petrology, 1999)

A microsatellite marker associated with a QTL for grain protein content on chromosome arm 2DL of bread wheat - M. Prasad; R. K. Varshney; A. Kumar; H. S. Balyan; P. C. Sharma; K. J. Edwards; H-Singh; H. S. Dhaliwal; J. K. Roy; P. K. Gupta (Theoretical and Applied Genetics, 1999)

Abundance and polymorphism of microsatellite markers in the tea tree (Melaleuca alternifolia, Myrtaceae) - M. Rossetto; A. McLauchlan; F. C. L. Harriss; R. J. Henry; P. R. Baverstock; L. S. Lee; T. L. Maguire; K. J. Edwards (Theoretical and Applied Genetics, 1999)

Higher plant tyrosine-specific protein phosphatases (PTPs) contain novel amino-terminal domains: expression during embryogenesis - Anthony P. Fordham-Skelton; Mark Skipsey; I. Marta Eveans; Robert Edwards; John A. Gatehouse (Plant Molecular Biology, 1999)

Correlation between Waardenburg syndrome phenotype and genotype in a population of individuals with identified PAX3 mutations - Anita L. DeStefano; L. Adrienne Cupples; Kathleen S. Arnos; J. H. Jr. Asher; Clinton T. Baldwin; Susan Blanton; Melisa L. Carey; Elias O. da Silva; T. B. Friedman; Jacquie Greenberg; Anil K. Lalwani; Aubrey Milunsky; et al. (Human Genetics, 1998)

A cluster of stearoyl CoA desaturase genes, Scd1 and Scd2, on mouse Chromosome 19 - D. E. Tabor; Y. -R. Xia; M. Mehrabian; P. A. Edwards; A. J. Lusis (Mammalian Genome, 1998)

Digital analysis of multispectral airborne imagery of coral reefs - P. J. Mumby; E. P. Green; C. D. Clark; A. J. Edwards (Coral Reefs, 1998)

Coral reef habitat mapping: how much detail can remote sensing provide? - P. J. Mumby; E. P. Green; A. J. Edwards; C. D. Clark (Marine Biology, 1997)

Withdrawal reactions with selective serotonin re-uptake inhibitors as reported to the WHO system - M. M. S. Stahl; M. Lindquist; M. Pettersson; I. R. Edwards; J. H. Sanderson; N. F. A. Taylor; A. P. Fletcher; J. S. Schou (European Journal of Clinical Pharmacology, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Diet and feeding ecology of the diving petrels Pelecanoides georgicus and P. urinatrix at South Georgia - K. Reid; J. P. Croxall; T. M. Edwards; H. J. Hill; P. A. Prince (Polar Biology, 1997)

Dislodgeable residues of ethion in Florida citrus and relationships to weather variables - H. N. Nigg; J. C. Allen; R. F. Brooks; G. J. Edwards; N. P. Thompson; Roy W. King; A. H. Blagg (Archives of Environmental Contamination and Toxicology, 1977)

Eleven undescribedArizona serotypes isolated from man - P. R. Edwards; Mary A. Fife (Antonie van Leeuwenhoek, 1962)

Eight newArizona serotypes isolated from reptiles - E. H. Kampelmacher; P. A. M. Guinée; Mary A. Fife; P. R. Edwards (Antonie van Leeuwenhoek, 1962)

Ten newArizona serotypes isolated from animals and animal food products - Mary A. Fife; Alma C. McWhorter; P. R. Edwards (Antonie van Leeuwenhoek, 1962)

Seven newArizona serotypes isolated from reptiles - P. R. Edwards; E. H. Kampelmacher; Mary A. Fife; P. A. M. Guinée (Antonie van Leeuwenhoek, 1961)

A newSalmonella type:Salmonella utrecht - E. H. Kampelmacher; Mary A. Fife; P. R. Edwards (Antonie van Leeuwenhoek, 1959)

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)